Accelerated climate-induced risks of nitrogen-loss from agricultural catchments: Empirical modelling of extreme weather events using climate change scenarios - G. Ezzati; P. Mellander; J. Ortega; B. Fan; C. Murphy (Water Research, 2027)

Navigating uncertainty and competing objectives: Spring chinook salmon recovery in the upper Willamette river - Claire E. Couch; J. Rose Wallick; James T. Peterson; Bailey A. Morgan; Matthew L. Keefer; Christopher C. Caudill; Kathleen G. O’Malley; Christina A. Murphy; James S. White; Jake R. Kelley; Dalton J. Hance; Gabriel S. Hansen; et al. (Reviews in Fish Biology and Fisheries, 2026)

SDG14 assessment of progress against sustaining life below water: a case study from Torres Strait - Éva Plagányi; Nicole Murphy; Roy Aijun Deng; Laura K. Blamey; Stephanie Brodie; Leo X. C. Dutra; Steven Edgar; Denham Parker; Kinam Salee; Mark Tonks; Sharon A. Appleyard (Reviews in Fish Biology and Fisheries, 2026)

Managing the Unmanageable: Understanding the Competing Effects of Salinity and Nutrient Loading on Estuarine Water Quality - Marcus W. Beck; Edward T. Sherwood; Rebecca R. Murphy; Kerry Flaherty-Walia; Qian Zhang; Blake A. Simmons; Maya C. Burke (Estuaries and Coasts, 2026)
Changing climatic conditions that can alter physical characteristics of surface waters may limit the effectiveness of conventional approaches to nutrient management. This study evaluated the competing effects of nutrient loads and changing salinity on chlorophyll-a dynamics in Tampa Bay (Florida, USA). This estuary has demonstrated long-term recovery of water quality primarily through wastewater infrastructure improvements, whereas a gradual freshening of the bay over the last few decades may compromise future management efforts to protect water quality. The relative effects of loading and salinity over a forty-year time period were evaluated using normalized predictions from Generalized Additive Models (GAMs). All bay segments showed a gradually increasing influence of reduced salinity on chlorophyll-a. Old Tampa Bay in the northwest also showed an increasing influence of nutrient loading. Simulation scenarios using the GAMs assessed the relative likelihood of exceeding regulatory chlorophyll-a standards under future salinity conditions. All bay segments showed an increased likelihood of exceeding regulatory standards, particularly in Old Tampa Bay where likelihood increased by ~ 16% over a fifty-year simulation. The results suggested that current nutrient loads should be substantially reduced below the federally-recognized Total Maximum Daily Load to maintain likelihood of meeting regulatory chlorophyll-a standards in the future that is similar to present. By understanding the effects of largely unmanageable characteristics of the bay, water quality managers can reassess efforts on limiting factors they can control relative to those they cannot.

Fifty years of riverine harmful algal bloom modeling: A global synthesis of approaches, challenges, and opportunities - Jennifer C. Murphy; Rebecca M. Gorney; Lisa V. Lucas; Jacob A. Zwart; Jennfier L. Graham (Water Research, 2026)

Placental toxic metal concentrations and preterm birth: Modification by social stressors - Ruohan Liao; Adriana C. Vidal; James Harrington; John Thorp; David Skaar; Yukun Liu; Susan K. Murphy; David W. Sosnowski; Sara B. Johnson; Gang Peng; Jung-Ying Tzeng; Cathrine Hoyo (Reproductive Toxicology, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Embedding Community Engagement in Underrepresented Student Cancer Research Training Programs: A Preliminary Report - Dennis R. Trinidad; Dahlia I. Sandoval; Kirti Ghei; Tanya E. Penn; Mercedes A. Mendoza; Jill Dumbauld Nery; Valesca Largaespada; Jesse N. Nodora; Noe C. Crespo; Ricardo M. Zayas; Richard M. Cripps; James Murphy; et al. (Journal of Cancer Education, 2026)
Training programs designed to increase participation of underrepresented students in cancer-related careers rarely include structured community engagement components. We describe the design and pilot of the Field Experience in Cancer Outreach and Engagement (FECOE), a program developed as part of the CREATE Partnership (Cancer Research and Education to Advance HealTh Excellence), a National Cancer Institute-funded grant to San Diego State University (SDSU) and University of California San Diego (UCSD). Scholars were situated within the UCSD Moores Cancer Center Community Outreach and Engagement (COE) component and completed 20 h of field and product-development activities from May-August 2025. A focus group was conducted at the conclusion of the program. Three SDSU Undergraduate Scholars and one UCSD Medical Student Scholar completed the pilot. Scholars reported gaining skills in health communication, community engagement, and cultural humility. Scholars described the experience as “connected” and “eye-opening,” and reported gains in career clarity. Feedback included improving tracking of hours, event preparation, and networking. The pilot FECOE demonstrates the feasibility of embedding a community outreach field experience within a cancer research training program. The COE-embedded model offers a scalable, sustainable approach that benefits Scholars and the host institution’s outreach mission. Lessons learned will inform refinements for future iterations.

“I got a completely new perspective about how they do their jobs”: A mixed methods evaluation of a short film to promote nursing and midwifery as career options - John Goodwin; Rachel Gough; Jan Cattoni; Ciara Chambers; Sinead Cronin; Clare Crowley; Margaret Curtin; Caroline Dalton; Marie-Therese Keating; Patricia Leahy-Warren; Anne-Marie Martin; Geraldine McLoughlin; et al. (Next Research, 2026)

Genomic insights into the evolutionary history and cryptic diversity of two-toed sloths (Choloepus) in Amazonia - Larissa S. Arantes; Luísa S. Marins; Linda Hagberg; Radarane Santos Sena; Benoit de Thoisy; Marta Svartman; Mariluce Rezende Messias; Cláudia R. Silva; Nicole M. Foley; William J. Murphy; Camila C. Ribas; Fabrício R. Santos; et al. (Molecular Phylogenetics and Evolution, 2026)

“Persistent ecological impacts related to West Nile virus revealed using community science and vector surveillance data” - Brock Geary; Adam C. Smith; Lisa Williams; Sean P. Murphy; Brandon P.M. Edwards; Nicole L. Michel; Timothy D. Meehan; Roderick B. Gagne (Biological Conservation, 2026)

Impacts of Quaternary Climate History on the Biogeography of Specialized Butterflies in the Great Basin of North America - Sarah B. Bialik; Joseph S. Wilson; Michelle Sneck; Dennis D. Murphy; James A. Fordyce; Katherine L. Bell; Matthew L. Forister; Chris C. Nice (Journal of Biogeography, 2026)
Aim Dramatic Quaternary climate fluctuations impacted the evolutionary history and contemporary biogeography of many residents of the Great Basin Desert of western North America. This study investigates the historical biogeographic processes that shaped the contemporary distribution of genetic variation in a polytypic group of specialized butterflies that are residents of unique dune and playa habitats. Many of the subspecies are considered to be threatened and this study uses high‐resolution SNP data to understand their history and quantify patterns of differentiation to inform conservation. Location Great Basin, western North America. Taxon The pallid dotted blue butterfly complex ( Euphilotes pallescens , Lycaenidae). Methods We constructed reduced‐representation genomic libraries to generate population genomics data that were used in clustering, ordination, and phylogenetic analyses. Pairwise differentiation between localities was quantified and the relationship between genomic differentiation and geography was analysed using a linear model. In addition, an estimated effective migration surface illustrated geographic patterns of genomic variation. Results Euphilotes pallescens populations were clearly differentiated from congeneric species and several subspecies, especially in the northwestern portion of the sampled range, were identifiable from genomic variation. When geographic distance was controlled, genetic differentiation was greatest between populations of Eu. pallescens compared to congeners, and within Eu. pallescens , northwestern populations were more differentiated than southern populations. The estimated effective migration surface also showed greater areas of reduced gene flow in the northwestern region. Main Conclusions Euphilotes pallescens comprises isolated populations on dune habitats in the Great Basin. Populations in the northwestern region are especially isolated and their patterns of genetic variation are consistent with the history of climate change and ancient pluvial lakes that occupied much of this region at intervals during the Quaternary. These butterflies are members of unique, localized communities whose persistence requires protections from anthropogenic threats, especially habitat loss including from recreation and off‐road vehicles in sensitive habitats.

Genetic sibship and parental reconstruction shed light on the mating systems and larval dispersal of an iconic Australian freshwater fish - J. E. O'Dwyer; K. A. Harrisson; Z. Tonkin; J. Lyon; B. Zampatti; W. Koster; S. Raymond; D. Dawson; C. Bice; N. Murphy (Journal of Fish Biology, 2026)
Mating systems shape the population dynamics of species, influencing attributes such as effective population size and population persistence. Traditionally, genetic analysis of mating systems includes the genotyping of putative parents to determine parentage. However, for cryptic or migratory species, and those with large populations, comprehensive sampling of adults is often not feasible. One underutilised alternative is to reconstruct parental genotypes from sibling relationships (i.e., sibship). We develop a generalisable sibship workflow for delineating types of first‐ and second‐ order kinship classifications in medium‐/low‐density SNP marker datasets and apply it to investigate the mating systems of the iconic Australian freshwater fish, Murray cod ( Maccullochella peelii ) using larvae collected over five breeding seasons and three breeding locations. We explored the relative occurrences of monogamous and polygamous pairings within and across breeding seasons along with larval dispersal patterns, and connectivity among breeding locations. Whilst monogamy was the most common mating strategy identified within each breeding season, only a single instance of multi‐year pair‐bonding was detected. Across seasons, 18% of putative adults were redetected and bred with a new partner, and within‐season polygynandry was detected in all three study reaches. Larval kin were found up to 71 km apart over only a few weeks of sampling and kin pairs were detected across two of the breeding locations (120–150 km apart) over seasons. Relatively high rates of polygynandry in wild Murray cod may promote the maintenance of genetic diversity and reduce vulnerability to recruitment disruptions in a climatically variable river system. Our study provides a valuable case study demonstrating that sibship analysis can provide insights into mating systems and dispersal potential of species where sampling adults is logistically difficult compared with collecting offspring.

Marine Isotope Stage 4 glaciation in northern England, UK: Evidence from Victoria Cave, North Yorkshire - Tom C. Lord; Peter Wilson; Joyce Lundberg; Adrian P. Palmer; Matt W. Telfer; Rhiannon E. Stevens; Phillip J. Murphy; Mark Lewis (Journal of Quaternary Science, 2026)
Victoria Cave, north Yorkshire, England, contains a long sequence of Pleistocene clastic sediments and calcite flowstones. Earlier work, using U–Th dating, established that the flowstone units formed in interglacial stages corresponding to Marine Isotope Stages (MIS) 13, 11, 9, 7 and 5. The intervening laminated sediments were therefore assigned to glacial stages (MIS 12, 10, 6 and 2) and regarded as rhythmites that settled from ponded glacial meltwater in the cave. Victoria Cave is a rare instance of cave rhythmites that formed over a number of glacial–interglacial cycles. The macro‐ and micromorphologies of the rhythmites support the above interpretation, and the mineralogy demonstrates that the sediments probably derive from rock types within the local area. An OSL age of 66 ± 8.4 ka from the uppermost unit of the rhythmites and two 14 C ages of 46.1–54.9 cal. ka BP and 48.9–>55.0 cal. ka BP, for horse and reindeer, respectively, from the overlying Bone‐bearing Cave Earth provide a new chronology for these Late Pleistocene sediments. Together, these results indicate that the youngest rhythmites in Victoria Cave formed during MIS 4 and not MIS 2 as previously assumed. This provides strong support for more widespread glaciation in northern England in MIS 4 (~71–59 ka) than has previously been recognised. The MIS 4 rhythmites represent the most tightly constrained cave rhythmites in Britain and the first terrestrial‐based evidence from this area for glaciation at that time.

Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

A Coast-to-Coast Assessment of Cumulative Impacts and Protection Potential in Canadian Marine Conservation Networks - Grace E. P. Murphy; Selina Agbayani; Jocelyn C. Nelson; Emily M. Rubidge; Ryan R. E. Stanley; Cathryn C. Murray; Noreen E. Kelly (Environmental Management, 2026)
The effectiveness of marine conservation networks depends on their ability to manage and safeguard against the many overlapping human activities and stressors influencing marine ecosystems. Cumulative impact mapping (CIM) combines information on the intensity and location of stressors with the spatial extent and vulnerability of marine habitats to generate a single, relative cumulative impact (CI) score. Despite its potential benefits to inform management and conservation efforts, CIM is not commonly incorporated into conservation network planning. Here, we combine published CIMs from the Canadian Atlantic and Pacific bioregions with existing marine conservation areas (MCAs) to compare impacts inside each MCA against regional impacts. We then conduct a scenario analysis to quantify potential reduction in cumulative impacts in two bioregion’s proposed marine conservation networks by modeling the removal of prohibited activities (bottom contact fishing, dredging, disposal at sea) in alignment with the Canadian Marine Protection Standard. Both regions exhibited similar distributions in current CI scores, with approximately half of MCAs scoring significantly above the regional mean, and the other half below. The scenario analysis predicted a 7% mean decrease (range 0–36%) in cumulative impacts across the Scotian Shelf and 2% mean decrease (range 0–17%) across the Northern Shelf networks. We identified 17 MCAs in the Scotian Shelf and 8 in the Northern Shelf as having high protection potential, which can be a valuable decision support tool for conservation planners. We discuss how CIM can be operationalized for conservation network planning and management.

Top‐Down and Bottom‐Up Effects on Insect Herbivores Under Global Change—A Meta‐Analysis - Mayra C. Vidal; Mattheau S. Comerford; Billie Maguire; Shannon M. Murphy (Ecology Letters, 2026)
Global environmental change is driving widespread insect declines, yet underlying mechanisms remain poorly understood, particularly when mediated by trophic interactions. Many studies purportedly test global change stressors on insect herbivores mediated via their host plants (bottom‐up) and natural enemies (top‐down), but we lack a comprehensive understanding of overall effects. Here, we performed a meta‐analysis of 246 papers testing 18 distinct global change stressors impacting insect herbivores via trophic interactions. We found variable, often opposing impacts of global change stressors on herbivore fitness when herbivores and their host plants were exposed, while the only detected significant effect involving natural enemies was a reduced herbivore fitness under warming, potentially due to increased enemy attacks. Notably, generalists exhibited greater vulnerability to global change than specialists, challenging assumptions that dietary generalists are more resilient. Insect herbivores tested in agricultural systems were more prone to be benefited by global change, whereas closed experimental systems amplified negative outcomes. Our results underscore the importance of considering trophic interactions and context‐specific dynamics in predicting ecological responses to environmental change. By integrating bottom‐up and top‐down mechanisms, our study provides a nuanced quantitative understanding of how global change influences insect herbivores, with important implications for biodiversity conservation in the Anthropocene.

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Temporal Biomarker Profiles Following Non-Surgical Spinal Cord Concussion - Taylor M. Dickson; Anastasiya Loos; Malaika Amin; Juliana Vivas Lopez; Susan F. Murphy; Pamela J. VandeVord; Kelly C. S. Roballo (Journal of Molecular Neuroscience, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

A blueprint of initial LCA in Agri-food production systems: Practical recommendations for crop and livestock production systems - Indika Thushari; Asma Jebari; Alison Carswell; Thomas C. Ponsioen; Stephen Morse; Richard Murphy; Conor Walsh (Agricultural Systems, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Diameter, height, and volume as macroscopic predictors of photocarcinogenesis in UV-induced SKH1 papules - Mehdi Boostani; Alaina F. Carman; Erin C. Tracy; Sean P. Murphy; Rhea Carmel Glen Rodrigues; Katalin Ferenczi; Gillian Weston; Olayemi Sokumbi; Gyorgy Paragh; Wendy J. Huss (Journal of Photochemistry and Photobiology B: Biology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Proceedings of the 2024 FDA-CRCG Workshop: Scientific and Regulatory Considerations for Assessment of Immunogenicity Risk for Generic Peptide and Oligonucleotide Drug Products - Jennifer K. Lee; Ha-Na Lee; Sudhir Agrawal; Joseph A. Balsamo; Andrew Clerman; Sofie Denies; Anne De Groot; Jeremy Fry; Nicolas Gaudenzio; Andrew J. Graves; Kristina E. Howard; SuJin Hwang; et al. (The AAPS Journal, 2026)

Acute UV response of early erythema and late edema in SKH1 mice - Szabolcs Bozsányi; Rhea Carmel Glen Rodrigues; Ruby Acquah; Erin C. Tracy; Sean P. Murphy; Jocelyn Tracy; Li Yan; Mehdi Boostani; Hamid-Reza Rezvani; Wendy J. Huss; Gyorgy Paragh (Journal of Photochemistry and Photobiology B: Biology, 2026)

Seascape diversity and configuration shape habitat selection across multiple coastal ecosystems - Jesse D. Mosman; Hayden P. Borland; Ashley J. Rummell; Christopher J. Henderson; Sam Allan; Alec Bannam; Stacy L. Bierwagen; Michael J. Bradley; Alex B. Carter; Daniela M. Ceccarelli; Robert Coles; Michael J. Emslie; et al. (Biological Conservation, 2026)

Correction: Large-scale to local factors influencing Sumatra squalls affecting Singapore - Hanh Nguyen; Muhammad E. Hassim; Jia Yan Huan; Xin Rong Chua; Chen Chen; Matthew C. Wheeler; Bradley F. Murphy; Sandeep Sahany; Aurel F. Moise; Simon C. Peatman (Climate Dynamics, 2026)

Fine-scale patterns and drivers of ploidy state in lentic and lotic macrophyte assemblages across the world - Tatiana Lobato-de Magalhães; Kevin Murphy; Thomas A. Davidson; Jorge García-Girón; Andrey Efremov; Victor Chepinoga; Eugenio Molina-Navarro; Celeste Franceschini; Roger P. Mormul; Hui Fu; Rossano Bolpagni; Juri Nascimbene; et al. (Aquatic Botany, 2026)

The potential for unwanted genetic rescue in invasive fallow deer populations - Lauren C. White; Erin Hill; Eliane D. McCarthy; Andrew J. Bengsen; Sebastien Comte; Sandie Czarka; David M. Forsyth; Catherine E. Grueber; Jake Haddad; Jordan O. Hampton; Michelle Hanslow; Scott Jennings; et al. (Biological Invasions, 2026)

Biogeography and hidden diversity in the coffee snake species complex Ninia atrata (Dipsadinae) from South America and the Lesser Antilles - Michael J. Jowers; Oriana C. Dempster Ortigoza; Teddy Angarita-Sierra; John C. Murphy; AmaËl Borzée; Gilson A. Rivas; Richard M. Lehtinen; Matthew J. Ingrasci; Eric N. Smith (Systematics and Biodiversity, 2025)

An approach to prioritize urban tree planting to mitigate heat and advance equity in New Haven - Shijuan Chen; Erin Shives; Katie Lund; Colleen Murphy-Dunning; Karen C. Seto (Urban Forestry & Urban Greening, 2025)

Development of a genetic reference flock: Benchmarking of industry and U.S. Sheep Experiment Station Rambouillet sires - Carrie S. Wilson; J. Bret Taylor; Thomas W. Murphy; Ronald M. Lewis; Whitney C. Stewart; David R. Notter (Small Ruminant Research, 2025)

Mid‐Holocene drying of K'gari lakes (subtropical eastern Australia) necessitates re‐evaluation of the El Niño–Southern Oscillation climate links and future drying risk - John Tibby; Haidee Cadd; Matthew Harris; Jonathan C. Marshall; Jonathan Tyler; Cameron Barr; Francesca McInerney; Patrick Moss; Claire Murphy; Patricia S. Gadd; Geraldine E. Jacobsen; Mathew Raven; et al. (Journal of Quaternary Science, 2025)
The Holocene history of Australia's climate is surprisingly poorly understood. This is, in part, because of the relatively weak forcing of Holocene climate versus that of the late Pleistocene. However, it is commonly suggested that eastern Australia dried during the mid‐ to late‐Holocene and that this was in response to increased activity in the El Niño–Southern Oscillation (ENSO), in particular, the intensification of the El Niño phase of ENSO. While this has been inferred from numerous locations, data from K'gari (a subtropical sand island adjacent to the east coast) was amongst the first used to develop this hypothesis and features heavily in the discussion of ENSO intensification. This study examines published and new data from three ≥4.5 m deep K'gari lakes that demonstrate a strong drying event during the middle Holocene (from 7640 to 5600 cal a BP), followed by a wetter late Holocene climate. This contrasts somewhat with previous arguments about K'gari's history that suggest a late Holocene drying. In turn, this indicates a need to re‐evaluate the notion that ENSO intensification drove late‐Holocene drying in the region. It also indicates that even large, deep lakes on K'gari, which are iconic landmarks with substantial cultural, ecological and economic values, are vulnerable to drying.

Rapid cross-generational changes in morphology and mate choice following an extreme climatic event - Andrew D. Cronin; Ryan C. Taylor; Rachel A. Page; Michael J. Ryan; Megan A. Murphy; Kimberly L. Hunter (Evolutionary Ecology, 2025)

Disentangling global geochemical signals from local diagenetic alteration in shallow-water marine carbonates during OAE1a - Matthew D. Nadeau; Jack G. Murphy; Cedric J. Hagen; Ziman Wu; Alliya A. Akhtar; Anne-Sofie Ahm; Daniel A. Stolper; Adam C. Maloof; John A. Higgins (Earth and Planetary Science Letters, 2025)

Anything you can eat, I can eat better: Evidence of generalism from species to individual level in an insect herbivore - Mattheau S. Comerford; William Maguire; Leah Murphy; Emma Schneider; Mayra C. Vidal (Ecology, 2025)
Most insect herbivores specialize on a few host plants; however, there are a minority of highly generalized species capable of feeding on hundreds of hosts. Generalism could emerge as a property of the species as a whole, while individuals would still exhibit greater specialization at more specific organizational levels. Yet, we lack studies with generalist insect herbivores directly testing this prediction. Here, we test if the highly generalized fall webworm ( Hyphantria cunea ) maintains its broad diet through specialization at the population, maternal genotype, or individual level. We reared two populations and multiple matrilines on either a static or rotating diet of four host plants. We found that both populations survived and pupated on all hosts, suggesting population‐level generalization. We found evidence for generalization at the genotype level, as maternal genotypes did not vary in performance rankings across host plants. Finally, we found generalism at the individual level, as individuals reared on a rotating diet had no difference or showed intermediate performance to those reared on static diets. Overall, we found support for the maintenance of generalism across all levels, suggesting that generalist species need not be locally specialized to maintain their extremely broad diet.

Record of seismic slip in carbonates: Insights from the Venere Fault during the 1915 Avezzano earthquake (Mw 7.0), Central Italy - Nina Zamani; Sara Satolli; Michael Murphy; Francois Demory; Bruno Pace; Jérôme Gattacceca; Ján Kaňuk; Michaela Nováková; Raphael Gottardi; Eric C. Ferré (Journal of Structural Geology, 2025)

Harvest legacies and climate change interact to shape forest structure and biomass through time - Lucien Fitzpatrick; Bailey A. Murphy; Meghan G. Midgley; Ankur R. Desai; Michael C. Dietze; Kurt Dreisilker; Christine R. Rollinson (Journal of Environmental Management, 2025)

Responses of small mammals to prescribed low-intensity fire: Genetic insights from a northern Australian fire experiment - Alexander R. Carey; Georgina Neave; Teigan Cremona; Hugh F. Davies; Brett P. Murphy; Geoffrey J. Cary; Tiwi Rangers; Toby Barton; Sam C. Banks (Biological Conservation, 2025)

Granulomatous enteritis due to Mycobacterium avium subsp avium in an alpaca - D. Murphy; C. Brady; P. Norton; A. Morgan; D. O’Brien; D. Bochynska; S. Alessandro Mignacca (Journal of Comparative Pathology, 2025)

Large-scale to local factors influencing Sumatra squalls affecting Singapore - Hanh Nguyen; Muhammad E. Hassim; Jia Yan Huan; Xin Rong Chua; Chen Chen; Matthew C. Wheeler; Bradley F. Murphy; Sandeep Sahany; Aurel F. Moise; Simon C. Peatman (Climate Dynamics, 2025)
The climate of the Maritime Continent, including Singapore, is influenced by a wide range of tropical drivers including the El-Niño Southern Oscillation (ENSO), the Indian Ocean Dipole (IOD), the Madden–Julian Oscillation (MJO), and equatorial wave activity. In Singapore, the rainfall pattern is often marked by episodes of short intense rainfall bursts, primarily driven by mesoscale convective systems, such as Sumatra squall lines. These episodes often result in local flash floods and strong wind bursts. Here we analyse 33 years of Sumatra squalls affecting Singapore and investigate the potential impact of the main modes of climate variability and atmospheric equatorial tropical waves. Highlighted results are that, on average, Sumatra squalls originate from Sumatra and the Strait of Malacca, make landfall over Singapore primarily in the morning and last about 2 h, and are more frequent from April to November. These squalls tend to be more frequent under La Niña conditions, which are associated with locally warm sea surface temperature anomalies and favourable atmospheric anomalies over the Maritime Continent region. On intraseasonal scale, the MJO may play a role in setting the westerlies and enhancing convective conditions favorable for the squalls to intensify and propagate eastward. Convectively-coupled Kelvin waves are important for the initiation and eastward propagation of the squalls over Sumatra and the Strait of Malacca, while equatorial Rossby, and mixed Rossby gravity waves influence their meridional propagation toward Singapore.

Seasonal Trends in Water Retention of Atlantic Sea Cucumber (Cucumaria frondosa): A Modeling Approach - Pete Brown; Heather J. Burke; Juran C. Goyali; Wade Murphy; Deepika Dave (Fishes, 2025)
Sea cucumbers are widely consumed as a delicacy or in eastern medicine across many Asian countries. Due to the depletion of traditional stocks, new species are increasingly harvested, including the Atlantic sea cucumber (Cucumaria frondosa), the most abundant, cold-water species found in the North Atlantic. This species is harvested in NAFO subdivision 3Ps off the south coast of Newfoundland and Labrador, Canada. As part of their respiration, stress response, and locomotion, sea cucumbers draw and retain oxygenated water within their body cavity, resulting in significant water content at landing. Historically, Fisheries and Oceans Canada (DFO) have applied a 23% deduction to the landed weight to account for this water retention. To validate this deduction, the authors conducted experiments across thirteen sampling events in 2019 and 2020. Randomized samples were collected during offloading and were categorized into three sizes of bin—small (x ≤ 150 g), medium (150 g 250 g)—and water loss was measured. Water loss was analyzed in relation to multiple factors, including processor, unloading method, year, license, month, fishing area, hold location, size, and processing method. Key findings included the following: (a) sea cucumbers typically contained more than 23% free water; (b) large and medium-sized specimens, which dominated landings, retained more free water; (c) water loss was highest for the samples collected from the top of the hold; (d) the unloading method influenced free water retention, as did the processing method used to cut the sea cucumbers; (e) license, processor, and fishing area had strong collinearity with other factors or were not found to be statistically significant; and (f) water loss appeared higher in 2020 than 2019, largely due to the increased use of vacuum transfer methods. Based on these findings, DFO revised the water retention allowance to 34%.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Potential of blended byproduct caps for management of bauxite residues: How do texture and weathering impact geochemistry? - Golam Taki; Pauline F. Grierson; Helen E.A. Brand; Daniel V. Murphy; Talitha C. Santini (Resources, Conservation and Recycling, 2025)

Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Trinidad and Tobago geogenomics: Exploring connections between geology and vicariance and dispersal biogeography — a review and synthesis - John C. Weber; Jeanette C. Arkle; Laurent de Verteuil; John C. Murphy; Nigel C. Noriega; David N. Reznick; Michael J. Jowers (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Environmental contaminants assessment for frequently harvested migratory waterfowl in the Northeast Atlantic flyway - David B. Dayan; Brenda J. Hanley; Joshua Stiller; Wayne Richter; Ian D. Gregg; Nate R. Huck; Min T. Huang; Theodore C. Nichols; Henry M. Spliethoff; Jesse C. Becker; Lisa A. Murphy; Krysten L. Schuler (Science of The Total Environment, 2025)

Toxicity of additives present in conventional and biodegradable plastics on soil fauna: a case study of the root lesion nematode Pratylenchus neglectus - Samantha J. Viljoen; Francesca L. Brailsford; Daniel V. Murphy; Frances C. Hoyle; Davey L. Jones; David J. Henry; John Fosu-Nyarko (Journal of Hazardous Materials, 2025)

Environmental life cycle assessment of producing sorbitol and maltitol from wheat starch using process simulation: The SWEET project - J. Suckling; G. Brussino; E. Koukouna; N. Misailidis; A. Koulouris; D. Petrides; S. Morse; M. Raats; J. Scholten; C. Westbroek; J.C.G. Halford; J.A. Harrold; et al. (Journal of Cleaner Production, 2025)

Drivers of forest productivity in two regions of the United States: Relative impacts of management and environmental variables - Hazhir Karimi; Michael Binford; William Kleindl; Gregory Starr; Bailey A. Murphy; Ankur R. Desai; Chiung-Shiuan Fu; Michael C. Dietze; Christina Staudhammer (Journal of Environmental Management, 2025)

Environmental life cycle assessment of drink and yoghurt products using non-nutritive sweeteners and sweetness enhancers in place of added sugar: the SWEET project - J. Suckling; S. Morse; R. Murphy; M. Raats; S. Astley; A. Ciruelos; A. Crespo; J. C. G. Halford; J. A. Harrold; A. Le-Bail; E. Koukouna; H. Musinovic; et al. (The International Journal of Life Cycle Assessment, 2025)
Purpose There are increasing concerns regarding detrimental health effects of added sugar in food and drink products. Non-nutritive sweeteners (NNS) and sweetness enhancers (SE) are seen as viable alternatives. Much work has been done on health and safety of NNS&SE when consumed in place of sugar, but very little on their sustainability. This work aims to bridge that gap with an environmental study of replacing added sugar with NNS&SE in the context of drink and yoghurt. Methods A life cycle assessment (LCA) approach was used to compare environmental impact of a drink and yoghurt, sweetened with sucrose, to those sweetened with NNSs or an SE: stevia rebaudioside A, sucralose, aspartame, neotame, and thaumatin. Primary ingredients data were taken from preparation of foodstuffs for clinical trials. Results are reported via the ReCiPe 2016 (H) method, with focus on land use, global warming potential (GWP), marine eutrophication, mineral resource scarcity, and water consumption. Impacts are reported in terms of 1 kg product. Scenarios explore sensitivity of the LCA results to change in background processes, functional unit, and sweetener type. This research was conducted as part of the EU Horizon 2020 project SWEET (sweeteners and sweetness enhancers: impact on health, obesity, safety, and sustainability). Results and discussion Replacing sugar with an NNS or part-replacing with an SE is shown to reduce environmental impact across most impact categories, for example, on a mass basis, GWP for a drink reduces from 0.61 to approx. 0.51 kgCO 2 -eq/kg and for a yoghurt from 4.15 to approx. 3.73 kgCO 2 -eq/kg. Variability in environmental impact is shown to be relatively small between the NNSs, indicating that choice of NNS is less important than the reformulation changes required to accommodate the loss of sugar. Reporting impact in terms of calorie density, instead of mass, shows greater reduction in environmental impact when using an NNS or SE and shows how important functional unit is when reporting impact of these products. Conclusion This study is the first to compare food or drink products sweetened with sugar, NNS, or SE. Results show that there is great potential to reduce environmental impact of sweetened drinks and yoghurts. Moreover, the choice of NNS does not greatly affect the environmental impact of either product. Therefore, this research shows that choices relating to replacing added sugar may be based more upon health or formulation needs and less on environmental concerns.

Curcumin Improves Hippocampal Cell Bioenergetics, Redox and Inflammatory Markers, and Synaptic Proteins, Regulating Mitochondrial Calcium Homeostasis - Claudia Jara; Angie K. Torres; Han S. Park-Kang; Lisette Sandoval; Claudio Retamal; Alfonso Gonzalez; Micaela Ricca; Sebastián Valenzuela; Michael P. Murphy; Nibaldo C. Inestrosa; Cheril Tapia-Rojas (Neurotoxicity Research, 2025)

Rectifying a century of misidentifications: a taxonomic re-evaluation of sipo snakes (Colubridae: Chironius ) on Trinidad - Robert C. Jadin; Michael J. Jowers; Christopher Blair; Rickaela K. Ludwig; Xabier Salgado-Irazabal; John C. Murphy (Systematics and Biodiversity, 2024)

Experimental constraints on the role of temperature and pyrogenic mineral assemblage in wildfire-induced major and trace element mobilisation - Kristy Guerin; David Murphy; Stefan C. Löhr; Luke Nothdurft (Geochimica et Cosmochimica Acta, 2024)

Ecological but Not Biological Traits of European Riverine Invertebrates Respond Consistently to Anthropogenic Impacts - James S. Sinclair; Rachel Stubbington; Ralf B. Schäfer; Libuše Barešová; Núria Bonada; Zoltán Csabai; J. Iwan Jones; Aitor Larrañaga; John F. Murphy; Petr Pařil; Marek Polášek; Jes J. Rasmussen; et al. (Global Ecology and Biogeography, 2024)
Aim To determine which riverine invertebrate traits respond consistently to anthropogenic impacts across multiple biogeographic regions. Location Europe. Time Period 1981–2021. Major Taxa Studied Riverine invertebrates. Methods We compiled a database of riverine invertebrate community time series for 673 sites across six European countries spanning six freshwater ecoregions. We compared trait responses to anthropogenic impacts (quantified as changes in ‘ecological quality’) among regions for seven ‘ecological’ traits, which reflect habitat preferences, and nine ‘biological’ traits (e.g., morphology or life history), which represent taxon‐specific attributes that can influence ecosystem processes. Results Four ecological traits (current, microhabitat, salinity and trophic preferences) and one biological trait (dispersal mode) responded consistently across regions. These responses were primarily driven by spatial differences among poorer to better quality sites. Responses to temporal changes in quality were comparable but less pronounced. Main Conclusions Consistent responses to anthropogenic impacts across multiple ecological traits indicate these traits may improve broader scale measurements, comparisons and predictions of community responses. However, we could not use ecological traits to identify the actions of specific stressors because multiple traits always responded as a group. Inconsistent responses across almost all biological traits indicated that these traits may be less predictive of impacts across regions. Predictions of how biological traits, and associated ecosystem processes, respond to anthropogenic impacts may be most effective at regional scales where responses are more consistent.

Association between prenatal air pollutant exposure and autism spectrum disorders in young children: A matched case-control study in Canada - Malia SQ. Murphy; Kasim E. Abdulaziz; Éric Lavigne; Erica Erwin; Yanfang Guo; Alysha LJ. Dingwall-Harvey; David Stieb; Mark C. Walker; Shi Wu Wen; Hwashin Hyun Shin (Environmental Research, 2024)

Comparing SEER and NCDB: a case study using colorectal cancer - Po-Hong Liu; Sandi L. Pruitt; Amit G. Singal; Caitlin C. Murphy (Cancer Causes & Control, 2024)

Testing molecular date estimates using an ecological and vicariant case study in treefrogs: The Geological‐Ecological Molecular Calibration - Michael J. Jowers; Jesús Muñoz Pajares; John Weber; Jeanette Arkle; Salvador Arenas‐Castro; Simon Y. W. Ho; Gilson A. Rivas; John C. Murphy; Amaël Borzée; R. Alexander Pyron; Marcos Perez‐Losada; Mayke De Freitas; et al. (Journal of Biogeography, 2024)
Aim To date a vicariant event through the mutualistic relationship of a hylid frog and its bromeliad host found across two isolated mountain ranges as part of an island–continental split and to use this information to calibrate a molecular dating analysis of hylids. Location South America. Time Period Pliocene. Major Taxa Studied Treefrogs, Arboranae. Methods Pliocene tectonic movements sank a portion of a mountain range that connected present‐day Trinidad (island) and northern Venezuela, eventually isolating populations of the golden tree frog Phytotriades auratus and its host bromeliad Glomeropitcairnia erectiflora on both sides of a saltwater barrier. We estimated the submersion rate timing of the vicariant event, then employed ecological niche modelling to establish the distribution of the frog and its host to the Pliocene. We generated nucleotide sequence data for the hylid on each side of the marine barrier and proposed a biogeographic calibration for the split between populations. Using Bayesian phylogenetic analysis, we evaluated the impact of incorporating this biogeographic calibration on estimates of treefrog divergence times. Results A relatively continuous, high‐elevation mountain range existed before the Pliocene and the opening of the Gulf of Paria (4.45 ± 0.85 Ma). Phytotriades auratus and G. erectiflora would have been distributed across the Paria and Northern Range mountains as a single population since the Pliocene. Divergence times among treefrogs (Arboranae) were older than those inferred using fossil calibrations alone, with mean age estimates for subfamilies and genera being ~2 and ~1.2 million years older, respectively. Main Conclusions Our study presents a biogeographic calibration based on a vicariant model that connects the evolution of the populations of a hylid through geology and ecological data. The implementation of this date as a molecular clock calibration reduces the uncertainty in date estimates for the shallower nodes in the phylogeny of Arboranae.

Range‐wide phylogeographic structure of the endangered Irrawaddy dolphin ( Orcaella brevirostris ) using expanded sampling from contemporary and historical specimens - Michael R. McGowen; Susana Caballero; Mary Faith C. Flores; Katherine R. Murphy; Frederick I. Archer; Sam Ayyagari; Isabel Beasley; C. Sarah Cohen; M. Louella L. Dolar; Chalatip Junchompoo; Patcharaporn Kaewmong; Worata Klinsawat; et al. (Marine Mammal Science, 2024)
The Irrawaddy dolphin ( Orcaella brevirostris ) is an endangered cetacean that ranges throughout much of Southeast Asia and lives in coastal, estuarine, and riverine habitats including three river systems: Ayeyarwady, Mekong, and Mahakam. Many populations face risks from human interference, but overall rangewide diversity and connectivity is not well‐understood. Here we sequenced 77 complete mitogenomes from across the range of the Irrawaddy dolphin including all obligate riverine populations; eighteen of these were sequenced from historical museum specimens. Phylogenetic analysis showed haplotypes from each riverine population formed separate clades nested within the wider species implying each river system was separately invaded only once. All Irrawaddy dolphin mitogenomes were dated to a last common ancestor ~764 kya. Most lineages appeared after inundation cycles of the Sunda Shelf were initiated ~400 kya. Despite the lack of monophyly among many haplotypes from the same population, no population shared any haplotypes. Rangewide nucleotide diversity was average compared to other odontocetes, but riverine populations were especially low. Differentiation was significant among all populations analyzed with the most divergence occurring between isolated riverine populations. These analyses add more evidence for the necessity of conservation efforts directed towards riverine and other isolated populations of the Irrawaddy dolphin.

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

Novel oil‐associated bacteria in Arctic seawater exposed to different nutrient biostimulation regimes - Francisco D. Davila Aleman; María A. Bautista; Janine McCalder; Kaiden Jobin; Sean M. C. Murphy; Brent Else; Casey R. J. Hubert (Environmental Microbiology, 2024)
The Arctic Ocean is an oligotrophic ecosystem facing escalating threats of oil spills as ship traffic increases owing to climate change‐induced sea ice retreat. Biostimulation is an oil spill mitigation strategy that involves introducing bioavailable nutrients to enhance crude oil biodegradation by endemic oil‐degrading microbes. For bioremediation to offer a viable response for future oil spill mitigation in extreme Arctic conditions, a better understanding of the effects of nutrient addition on Arctic marine microorganisms is needed. Controlled experiments tracking microbial populations revealed a significant decline in community diversity along with changes in microbial community composition. Notably, differential abundance analysis highlighted the significant enrichment of the unexpected genera Lacinutrix , Halarcobacter and Candidatus Pseudothioglobus . These groups are not normally associated with hydrocarbon biodegradation, despite closer inspection of genomes from closely related isolates confirming the potential for hydrocarbon metabolism. Co‐occurrence analysis further revealed significant associations between these genera and well‐known hydrocarbon‐degrading bacteria, suggesting potential synergistic interactions during oil biodegradation. While these findings broaden our understanding of how biostimulation promotes enrichment of endemic hydrocarbon‐degrading genera, further research is needed to fully assess the suitability of nutrient addition as a stand‐alone oil spill mitigation strategy in this sensitive and remote polar marine ecosystem.

P10-21 Spinosad – mode of action and human relevance assessment of dystocia in rats - M. Corvaro; K. Johnson; M. Himmelstein; E. Bianchi; R. Mingoia; M.J. Bartels; J. Domoradzki; R. Reiss; A. Williams; E. Richmond; C. Terry; J. LaRocca; et al. (Toxicology Letters, 2024)

Associations of neighborhood greenspace, and active living environments with autism spectrum disorders: A matched case-control study in Ontario, Canada - Éric Lavigne; Kasim E. Abdulaziz; Malia SQ. Murphy; Cristina Stanescu; Alysha LJ. Dingwall-Harvey; David M. Stieb; Mark C. Walker; Shi Wu Wen; Hwashin Hyun Shin (Environmental Research, 2024)

New evidence for the sensorimotor mismatch theory of weight perception and the size-weight illusion - Jarrod W. C. Harris; Elizabeth J. Saccone; Rebecca Chong; Gavin Buckingham; Melanie J. Murphy; Philippe A. Chouinard (Experimental Brain Research, 2024)
The size-weight illusion is a phenomenon where a smaller object is perceived heavier than an equally weighted larger object. The sensorimotor mismatch theory proposed that this illusion occurs because of a mismatch between efferent motor commands and afferent sensory feedback received when lifting large and small objects (i.e., the application of too little and too much lifting force, respectively). This explanation has been undermined by studies demonstrating a separation between the perceived weight of objects and the lifting forces that are applied on them. However, this research suffers from inconsistencies in the choice of lifting force measures reported. Therefore, we examined the contribution of sensorimotor mismatch in the perception of weight in the size-weight illusion and in non-size-weight illusion stimuli and evaluated the use of a lifting force aggregate measure comprising the four most common lifting force measures used in previous research. In doing so, the sensorimotor mismatch theory was mostly supported. In a size-weight illusion experiment, the lifting forces correlated with weight perception and, contrary to some earlier research, did not adapt over time. In a non-size-weight illusion experiment, switches between lifting light and heavy objects resulted in perceiving the weight of these objects differently compared to no switch trials, which mirrored differences in the manner participants applied forces on the objects. Additionally, we reveal that our force aggregate measure can allow for a more sensitive and objective examination of the effects of lifting forces on objects.

Using parentage-based tagging to estimate survival of Chinook salmon fry in a large storage reservoir - Adam C. Pope; Tobias J. Kock; Russell W. Perry; Karen M. Cogliati; Kathleen G. O’Malley; Christina A. Murphy; Dalton J. Hance; Scott D. Fielding (Environmental Biology of Fishes, 2024)

Description of serum symmetric dimethylarginine concentration and of urinary SDS-AGE pattern in dogs with ACTH dependent hyperadrenocorticism - M. Menard; M. Kurtz; A. Duclos; J. Vial; C. Maurey; M. Canonne-Guibert; V. Fabrès; D. Rosenberg; M. Coyne; R. Murphy; C. Trumel; R. Lavoué; et al. (The Veterinary Journal, 2024)

Herbal leys have no effect on soil porosity, earthworm abundance, and microbial community composition compared to a grass-clover ley in a sheep grazed grassland after 2-years - Emily C. Cooledge; Craig J. Sturrock; Brian S. Atkinson; Sacha J. Mooney; Francesca L. Brailsford; Daniel V. Murphy; Jonathan R. Leake; David R. Chadwick; Davey L. Jones (Agriculture, Ecosystems & Environment, 2024)

Corrigendum to “Why, and where, is commercial fishing gear lost? A global review and case study of Pacific Canada” [Mar. Pollut. Bull. 196 (2023) 1–12 (115528)] - Caitlin Frenkel; Megan Eadie; Adrienne Murphy; Josephine C. Iacarella; Natalie C. Ban (Marine Pollution Bulletin, 2024)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

Rethinking atoll futures: local resilience to global challenges - Sebastian Steibl; Paul S. Kench; Hillary S. Young; Alex S. Wegmann; Nick D. Holmes; Nancy Bunbury; Teurumereariki Hinano Teavai-Murphy; Neil Davies; Frank Murphy; James C. Russell (Trends in Ecology & Evolution, 2024)

Global patterns of allochthony in stream–riparian meta‐ecosystems - Daniel C. Allen; James Larson; Christina A. Murphy; Erica A. Garcia; Kurt E. Anderson; Michelle H. Busch; Alba Argerich; Alice M. Belskis; Kierstyn T. Higgins; Brooke E. Penaluna; Veronica Saenz; Jay Jones; et al. (Ecology Letters, 2024)
Ecosystems that are coupled by reciprocal flows of energy and nutrient subsidies can be viewed as a single “meta‐ecosystem.” Despite these connections, the reciprocal flow of subsidies is greatly asymmetrical and seasonally pulsed. Here, we synthesize existing literature on stream–riparian meta‐ecosystems to quantify global patterns of the amount of subsidy consumption by organisms, known as “allochthony.” These resource flows are important since they can comprise a large portion of consumer diets, but can be disrupted by human modification of streams and riparian zones. Despite asymmetrical subsidy flows, we found stream and riparian consumer allochthony to be equivalent. Although both fish and stream invertebrates rely on seasonally pulsed allochthonous resources, we find allochthony varies seasonally only for fish, being nearly three times greater during the summer and fall than during the winter and spring. We also find that consumer allochthony varies with feeding traits for aquatic invertebrates, fish, and terrestrial arthropods, but not for terrestrial vertebrates. Finally, we find that allochthony varies by climate for aquatic invertebrates, being nearly twice as great in arid climates than in tropical climates, but not for fish. These findings are critical to understanding the consequences of global change, as ecosystem connections are being increasingly disrupted.

Predictions of PFAS regional-scale atmospheric deposition and ambient air exposure - Emma L. D'Ambro; Benjamin N. Murphy; Jesse O. Bash; Robert C. Gilliam; Havala O.T. Pye (Science of The Total Environment, 2023)

Environmental life cycle assessment of production of the non-nutritive sweetener sucralose (E955) derived from cane sugar produced in the United States of America: The SWEET project - E. Blenkley; J. Suckling; S. Morse; R. Murphy; M. Raats; S. Astley; J. C. G. Halford; J. A. Harrold; A. Le-Bail; E. Koukouna; H. Musinovic; A. Raben; et al. (The International Journal of Life Cycle Assessment, 2023)
Purpose There is increasing concern about the detrimental health effects of added sugar in food and drink products. Sweeteners are seen as a viable alternative. Much work has been done on health and safety of using sweeteners as a replacement for added sugar, but very little on their sustainability. This work aims to bridge that gap with a life cycle assessment (LCA) of sucralose derived from cane sugar grown in the United States of America (USA). Methods An attributional, cradle-to-gate LCA was conducted on sucralose production in the USA. Primary data were derived from literature for the chlorination process, and all other data from background sources. Results are reported via the ReCiPe 2016 (H) method, with focus given to land use, global warming potential (GWP), marine eutrophication, mineral resource scarcity, and water consumption. Because sucralose has a much greater perceived sweetness than sugar, impacts are expressed both in absolute terms of 1 kg mass and in relative sweetness equivalence terms to 1 kg sugar. Scenario modelling explores the sensitivity of the LCA results to change in key parameters. This research was conducted as part of the EU Horizon 2020 project SWEET (Sweeteners and sweetness enhancers: Impact on health, obesity, safety and sustainability). Results and discussion GWP for 1 kg sucralose was calculated to be 71.83 kgCO 2 -eq/kg (sugar from sugarcane is 0.77 kgCO 2 -eq/kg). However, on a sweetness equivalence basis, GWP of sucralose reduces to 0.12 kgCO 2 -eq/kg SE . Production of reagents was the main contributor to impact across most impact categories. Sugar (starting material for sucralose production) was not a majority contributor to any impact category, and changing the source of sugar has little effect upon net impact (average 2.0% variation). Instead, uncertainty in reference data is a greater source of variability: reagent use optimization reduces average impact of sucralose production by approximately 45.4%. In general, sucralose has reduced impact compared to sugar on an equivalent sweetness basis, however, due to data uncertainty, the reduction is not significant for all impact categories. Conclusion This LCA is the first for sucralose produced from cane sugar produced in the USA. Results indicate that sucralose has the potential to reduce the environmental impact of replacing the sweet taste of sugar. However, data were derived from literature and future collaboration with industry would help in reducing identified uncertainties. Accounting for functional use of sucralose in food and drink formulations is also necessary to fully understand the entire life cycle impact.

Why, and where, is commercial fishing gear lost? A global review and case study of Pacific Canada - Caitlin Frenkel; Megan Eadie; Adrienne Murphy; Josephine C. Iacarella; Natalie C. Ban (Marine Pollution Bulletin, 2023)

Advancing our understanding of biological invasions with long-term biomonitoring data - Phillip J. Haubrock; Laís Carneiro; Rafael L. Macêdo; Paride Balzani; Ismael Soto; Jes Jessen Rasmussen; Peter Wiberg-Larsen; Zoltan Csabai; Gábor Várbíró; John Francis Murphy; J. Iwan Jones; Ralf C. M. Verdonschot; et al. (Biological Invasions, 2023)
The use of long-term datasets is crucial in ecology because it provides a comprehensive understanding of natural fluctuations, changes in ecosystems over extended periods of time, and robust comparisons across geographical scales. This information is critical in detecting and analysing trends and patterns in species populations, community dynamics, and ecosystem functioning, which in turn helps in predicting future changes and impacts of human activities. Additionally, long-term data sets allow for the evaluation of the effectiveness of conservation efforts and management strategies, enabling scientists and decision makers to make evidence-based decisions for biodiversity conservation. Although the use of long-term data is recognized as highly important in several scientific disciplines, its usage remains undervalued regarding questions in invasion science. Here, we used four regional subsets (i.e. England, Hungary, Denmark and the Dutch-German-Luxembourg) of a recently collated long-term time series database to investigate the abundance and dynamics of occurring non-native species over space and time in Europe. While we found differences in the numbers of non-native species across the studied regions (Dutch-German-Luxembourg region = 37; England = 17, Hungary = 34; Denmark = 3), non-native species detection rates were continuous over time. Our results further show that long-term monitoring efforts at large spatial scales can substantially increase the accuracy and rate at which non-native species are detected. This information can inform management endeavours dealing with non-native species, underlining the need for invasion scientists and authorities-stakeholders to make more effort in collecting, analysing and making available long-term datasets at broader geographic ranges.

Climate and human mortality in Virginia, 2005–2020 - Robert E. Davis; Patrick C. Roney; Melanie M. Pane; Murphy C. Johnson; Hannah V. Leigh; William Basener; Amber L. Curran; Bryan DeMarcy; Jungyun Jang; Christian Schroeder; Pamela B. DeGuzman; Wendy M. Novicoff (Science of The Total Environment, 2023)

Environmental life cycle assessment of production of the non-nutritive sweeteners aspartame (E951) and neotame (E961) from chemical processes: The SWEET project - J. Suckling; S. Morse; R. Murphy; M. Raats; S. Astley; J.C.G. Halford; J.A. Harrold; A. Le-Bail; E. Koukouna; H. Musinovic; A. Raben; M. Roe; et al. (Journal of Cleaner Production, 2023)

Temporal and spatial evolution of the 2021 eruption in the Tajogaite volcano (Cumbre Vieja rift zone, La Palma, Canary Islands) from geophysical and geodetic parameter analyses - M. B. Benito; G. E. Alvarado; M. Marchamalo; J. G. Rejas; P. Murphy; R. Franco; D. Castro; C. Garcia-Lanchares; J. Sanchez (Natural Hazards, 2023)
The eruption of the Tajogaite volcano in 2021, in the Cumbre Vieja rift zone (La Palma, Canary Islands), is the most recent but also the most damaging and longest-lasting eruption on the island since historical records began. We analyzed geophysical parameters (seismicity, surface deformation, thermal anomalies, and volcanic activity) with the aim of reconstructing the temporal development of the magma plumbing system. The seismic sequence (> 9000 events, mbLg ≤ 5.0) can be grouped into nine distinct phases, which correspond to well-separated spatial clusters and distinct earthquake regimes. A strong premonitory thermal anomaly was calculated on July 2021 in the South of La Palma. The source of the magma was within the upper mantle (40–20 km depth). A second magma budget (< 15 km depth) indicated a short-term stagnation of alkaline magma within the lower crust, near the Moho. The outline of these earthquakes delineates the magma pathway. Just before and immediately after the eruption (phases 2 and 3), the high-frequency seismicity in the mantle disappeared completely, reappearing ten days after the eruption started. The pattern of deformation began before the eruption with a breakpoint around September 11, after which, deformation accelerated sharply, followed by stabilization in phase 3 and a decrease in the following phases. The level of deformation suggested that a shallow magma intrusion was established. Based on the historical eruptive pattern, it is possible to infer two possible hazard-forecast scenarios: (a) the volcano could enter a prolonged phase of tranquility for more than one century or, (b) a new eruption could occur between ca. 2045 and 2065, with a slightly shorter duration than this recent one. Therefore, if the more pessimistic scenario is assumed, appropriate territorial planning is required.

Insights into plasma-catalytic nitrogen fixation from catalyst microanalysis and chemical kinetics modelling - Jing Sun; Tianqi Zhang; Jungmi Hong; Rusen Zhou; Hassan Masood; Renwu Zhou; Anthony B. Murphy; Kostya Ken Ostrikov; Patrick J. Cullen; Emma C. Lovell; Rose Amal; Ali Rouhollah Jalili (Chemical Engineering Journal, 2023)

The faunal Ponto-Caspianization of central and western European waterways - Ismael Soto; Ross N. Cuthbert; Anthony Ricciardi; Danish A. Ahmed; Florian Altermatt; Ralf B. Schäfer; Gaït Archambaud-Suard; Núria Bonada; Miguel Cañedo-Argüelles; Zoltán Csabai; Thibault Datry; Jaimie T. A. Dick; et al. (Biological Invasions, 2023)
As alien invasive species are a key driver of biodiversity loss, understanding patterns of rapidly changing global species compositions depends upon knowledge of invasive species population dynamics and trends at large scales. Within this context, the Ponto-Caspian region is among the most notable donor regions for aquatic invasive species in Europe. Using macroinvertebrate time series collected over 52 years (1968–2020) at 265 sites across 11 central and western European countries, we examined the occurrences, invasion rates, and abundances of freshwater Ponto-Caspian fauna. We examined whether: (i) successive Ponto-Caspian invasions follow a consistent pattern of composition pioneered by the same species, and (ii) Ponto-Caspian invasion accelerates subsequent invasion rates. In our dataset, Ponto-Caspian macroinvertebrates increased from two species in 1972 to 29 species in 2012. This trend was parallelled by a non-significant increasing trend in the abundances of Ponto-Caspian taxa. Trends in Ponto-Caspian invader richness increased significantly over time. We found a relatively uniform distribution of Ponto-Caspian macroinvertebrates across Europe without any relation to the distance to their native region. The Ponto-Caspian species that arrived first were often bivalves (46.5% of cases), particularly Dreissena polymorpha , followed secondarily by amphipods (83.8%; primarily Chelicorophium curvispinum and Dikerogammarus villosus ) . The time between consecutive invasions decreased significantly at our coarse regional scale, suggesting that previous alien establishments may facilitate invasions of subsequent taxa. Should alien species continue to translocate from the Ponto-Caspian region, our results suggest a high potential for their future invasion success highly connected central and western European waters. However, each species’ population may decline after an initial ‘boom’ phase or after the arrival of new invasive species, resulting in different alien species dominating over time.

Life cycle assessment of the sweetness enhancer thaumatin (E957) produced from Thaumatococcus daniellii fruit foraged from West Africa: The SWEET project - J. Suckling; S. Morse; R. Murphy; S. Astley; C. Boy; J.C.G. Halford; J.A. Harrold; A. Le-Bail; E. Koukouna; H. Musinovic; A. Raben; M. Roe; et al. (Journal of Cleaner Production, 2023)

Blending bauxite residues with multiple byproducts improves capping materials for tailings storage facilities - Golam Taki; Pauline F. Grierson; Grace Scullett-Dean; Helen E.A. Brand; Daniel V. Murphy; Talitha C. Santini (Journal of Environmental Management, 2023)

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

Reconstructing mechanisms of extinctions to guide mammal conservation biogeography - Sean Tomlinson; Mark V. Lomolino; John C. Z. Woinarski; Brett P. Murphy; Elizabeth Reed; Chris N. Johnson; Sarah Legge; Kristofer M. Helgen; Stuart C. Brown; Damien A. Fordham (Journal of Biogeography, 2023)
An emerging research program on population and geographic range dynamics of Australia's mammals illustrates an approach to better understand and respond to geographic range collapses of threatened wildlife in general. In 1788, Europeans colonized an Australia with a diverse and largely endemic mammal fauna, where many species that are now extinct or threatened were common and widespread. Subsequent population declines, range collapses and extinctions were caused by introduced predators and herbivores, altered land use, modified fire regimes and the synergies between these threats. Declines in population and range size continue for many Australian mammals despite legislative protection and conservation interventions. Here, we propose an approach that integrates museum data and other historical records into process‐explicit macroecological models to better resolve mammal distributions and abundances as they were at European arrival. We then illustrate how this integrative approach can identify the likely synergistic mechanisms causing mammal population declines across these and other landscapes. This emerging research approach, undertaken with fine temporal and spatial resolution, but at large geographic scales, will provide valuable insights into the different pathways to, and drivers of, extinction. Such insights may, in turn, underpin conservation strategies based on a process‐explicit understanding of population decline and range collapse under alternative scenarios of impending climate and environmental change. Given that similar information is available for other regional biotas, the approach we describe here can be adapted to conserve threatened wildlife in other regions across the globe.

Data on vegetation across forest edges from the FERN ( F orest E dge R esearch N etwork) - Karen A. Harper; Logan Gray; S. Ellen Macdonald; Daniel Lesieur; Danielle DeFields; Pavel Dodonov; Caroline Mary Adrianne Franklin; Sean R. Haughian; Liliana Mascarúa López; Alexandra Heathcote; Krista Jager; Renee Yang; et al. (Ecology, 2023)
Many studies have focused on vegetation across forest edges to study impacts of edges created by human activities on forest structure and composition, or patterns of vegetation at inherent natural edges. Our objective was to create a database of plant‐related variables across different types of edges from various studies (mainly from across Canada, but also in Brazil and Belize) to facilitate edge research. We compiled data on vegetation along more than 300 transects perpendicular to forest edges adjacent to clear‐cuts, burned areas, bogs, lakes, barrens, insect disturbances, and riparian areas from 24 studies conducted over the past three decades. Data were compiled for more than 400 plant species and forest structure variables (e.g., trees, logs, canopy cover). All data were collected with a similar sampling design of quadrats along transects perpendicular to forest edges, but with varying numbers of transects and quadrats, and distances from the edge. The purpose for most of the studies was either to determine the distance of edge influence (edge width) or to explore the pattern of vegetation along the edge to interior gradient. We provide data tables for the cover of plant species and functional groups, the species and size of live and dead trees, the density of saplings, maximum height of functional groups and shrub species, and the cover of functional groups at different heights (vertical distribution of vegetation). The Forest Edge Research Network (FERN) database provides extensive data on many variables that can be used for further study including meta‐analyses and can assist in answering questions important to conservation efforts (e.g., how is distance of edge influence from created edges affected by different factors?). We plan to expand this database with subsequent studies from the authors and we invite others to contribute to make this a more global database. The data are released under a CC0 license. When using these data, we ask that you cite this data paper and any relevant publications listed in our metadata file. We also encourage you to contact the first author if you are planning to use or contribute to this database.

More PEAS Please! Teaching Teachers How to Integrate Food-based Learning Into Preschool Science - Virginia C. Stage; Jessica Resor; Jocelyn Dixon; Archana V. Hegde; Lucía I. Méndez; Tammy Lee; Raven Breinholt; L. Suzanne Goodell; Valerie J. McMillan; Evon Murphy Gilliam (Journal of Nutrition Education and Behavior, 2023)

Pyrodiversity trade-offs: A simulation study of the effects of fire size and dispersal ability on native mammal populations in northern Australian savannas - Hugh F. Davies; Casey Visintin; Brett P. Murphy; Euan G. Ritchie; Sam C. Banks; Ian D. Davies; David M.J.S. Bowman (Biological Conservation, 2023)

Initial impacts of the COVID-19 pandemic on Australian fisheries production, research organisations and assessment: shocks, responses and implications for decision support and resilience - Emily M. Ogier; David C. Smith; Sian Breen; Caleb Gardner; Daniel J. Gaughan; Harry K. Gorfine; Alistair J. Hobday; Natalie Moltschaniwskyj; Ryan Murphy; Thor Saunders; Mike Steer; James Woodhams (Reviews in Fish Biology and Fisheries, 2023)
Australia’s fisheries have experience in responding individually to specific shocks to stock levels (for example, marine heatwaves, floods) and markets (for example, global financial crisis, food safety access barriers). The COVID-19 pandemic was, however, novel in triggering a series of systemic shocks and disruptions to the activities and operating conditions for all Australia’s commercial fisheries sectors including those of the research agencies that provide the information needed for their sustainable management. While these disruptions have a single root cause—the public health impacts and containment responses to the COVID-19 pandemic—their transmission and effects have been varied. We examine both the impacts on Australian fisheries triggered by measures introduced by governments both internationally and domestically in response to the COVID-19 pandemic outbreak, and the countermeasures introduced to support continuity in fisheries and aquaculture production and supply chains. Impacts on fisheries production are identified by comparing annual and monthly catch data for Australia’s commercial fisheries in 2020 with averages for the last 4–5 years. We combine this with a survey of the short-term disruption to and impacts on research organisations engaged in fisheries monitoring and assessment and the adaptive measures they deployed. The dominant impact identified was triggered by containment measures both within Australia and in export receiving countries which led to loss of export markets and domestic dine-in markets for live or fresh seafood. The most heavily impact fisheries included lobster and abalone (exported live) and specific finfishes (exported fresh or sold live domestically), which experienced short-term reductions in both production and price. At the same time, improved prices and demand for seafood sold into domestic retail channels were observed. The impacts observed were both a function of the disruptions due to the COVID-19 pandemic and the countermeasures and support programs introduced by various national and state-level governments across Australia to at least partly mitigate negative impacts on harvesting activities and supply chains. These included protecting fisheries activities from specific restrictive COVID-19 containment measures, pro-actively re-establishing freight links, supporting quota roll-overs, and introducing wage and businesses support packages. Fisheries research organisations were impacted to various degrees, largely determined by the extent to which their field monitoring activities were protected from specific restrictive COVID-19 containment measures by their state-level governments. Responses of these organisations included reducing fisheries dependent and independent data collection as required while developing strategies to continue to provide assessment services, including opportunistic innovations to harvest data from new data sources. Observed short run impacts of the COVID-19 pandemic outbreak has emphasised both the vulnerability of fisheries dependent on export markets, live or fresh markets, and long supply chains and the resilience of fisheries research programs. We suggest that further and more comprehensive analysis over a longer time period of the long-run impacts of subsequent waves of variants, extended pandemic containment measures, autonomous and planned adaptive responses would be beneficial for the development of more effective counter measures for when the next major external shock affects Australian fisheries.

Spatial and temporal scaling of sub-daily extreme rainfall for data sparse places - R. L. Wilby; C. W. Dawson; D. Yu; Z. Herring; A. Baruch; M. J. Ascott; D. L. Finney; D. M. J. Macdonald; J. H. Marsham; T. Matthews; C. Murphy (Climate Dynamics, 2023)
Global efforts to upgrade water, drainage, and sanitation services are hampered by hydrometeorological data-scarcity plus uncertainty about climate change. Intensity–duration–frequency (IDF) tables are used routinely to design water infrastructure so offer an entry point for adapting engineering standards. This paper begins with a novel procedure for guiding downscaling predictor variable selection for heavy rainfall simulation using media reports of pluvial flooding. We then present a three-step workflow to: (1) spatially downscale daily rainfall from grid-to-point resolutions; (2) temporally scale from daily series to sub-daily extreme rainfalls and; (3) test methods of temporal scaling of extreme rainfalls within Regional Climate Model (RCM) simulations under changed climate conditions. Critically, we compare the methods of moments and of parameters for temporal scaling annual maximum series of daily rainfall into sub-daily extreme rainfalls, whilst accounting for rainfall intermittency. The methods are applied to Kampala, Uganda and Kisumu, Kenya using the Statistical Downscaling Model (SDSM), two RCM simulations covering East Africa (CP4 and P25), and in hybrid form (RCM-SDSM). We demonstrate that Gumbel parameters (and IDF tables) can be reliably scaled to durations of 3 h within observations and RCMs. Our hybrid RCM-SDSM scaling reduces errors in IDF estimates for the present climate when compared with direct RCM output. Credible parameter scaling relationships are also found within RCM simulations under changed climate conditions. We then discuss the practical aspects of applying such workflows to other city-regions.

Modelling parasite impacts of aquaculture on wild fish: The case of the salmon louse (Lepeophtheirus salmonis) on out-migrating wild Atlantic salmon (Salmo salar) smolt - Meadhbh Moriarty; Stephen C. Ives; Joanne M. Murphy; Alexander G. Murray (Preventive Veterinary Medicine, 2023)

Patterns of dreissenid mussel invasions in western US lakes within an integrated gravity model framework - Carra C. Carrillo; Bianca R. Charbonneau; Safra Altman; Jacque A. Keele; Sherri F. Pucherelli; Yale J. Passamaneck; Aaron C. Murphy; Todd M. Swannack (Journal of Environmental Management, 2023)

Environmental life cycle assessment of production of the high intensity sweetener steviol glycosides from Stevia rebaudiana leaf grown in Europe: The SWEET project - J. Suckling; S. Morse; R. Murphy; S. Astley; J. C. G. Halford; J. A. Harrold; A. Le-Bail; E. Koukouna; H. Musinovic; J. Perret; A. Raben; M. Roe; et al. (The International Journal of Life Cycle Assessment, 2023)
Purpose There is an increasing interest in the use of non-nutritive sweeteners to replace added sugar in food and beverage products for reasons of improving consumer health. Much work has been done to understand safety of sweeteners, but very little on sustainability. To address that gap, this study presents the results of a life cycle assessment (LCA) of production of rebaudioside A 60%, 95% pure (RA60) steviol glycoside mix from Stevia rebaudiana leaf grown in Europe. Methods An attributional cradle-to-factory-gate life cycle assessment was conducted on growing of stevia leaves and extraction of steviol glycosides in Europe. Primary data were used from a case study supply chain. Results are reported in impact categories from the ReCiPe 2016 (H) method, with focus given to global warming potential, freshwater eutrophication, water consumption, and land use. Impacts are expressed both in terms of production mass and sweetness equivalence, a common metric for understanding high intensity sweetener potency. Sweetness equivalence of RA60 is typically 200 to 300 times that of sugar. Comparison of environmental impact is made to sugar (sucrose) produced from both cane and beets. The research is part of the EU project SWEET (sweeteners and sweetness enhancers: impact on health, obesity, safety, and sustainability). Results and discussion Global warming potential for production of RA60 was found to be 20.25 kgCO 2 -eq/kg RA60 on a mass basis and 0.081 kgCO 2 -eq/kg SE on a sweetness equivalence basis. Field production of stevia leaves was found to be the main source of impact for most impact categories, and for all four focus categories. Extraction of the RA60 was the main source of impact for the others. Leaf processing and seedling propagation were minor contributors to life cycle impact. Removal of international transport from the supply chain reduced global warming potential by 18.8%. Compared with sugar on a sweetness equivalence basis, RA60 has approximately 5.7% to 10.2% the impact for global warming potential, 5.6% to 7.2% the impact for land use, and is lower across most other impact categories. Conclusion This is the first LCA of steviol glycoside mix RA60 produced from leaf in Europe. The results indicate that RA60 can be used to reduce environmental impact of providing a sweet taste by replacing sugar across all impact categories. However, it is important to note that specific formulations in which RA60 is used will have a bearing on the final environmental impact of any food or beverage products. For solid foods, this requires further research.

Spatial patterns and seasonal timing of increasing riverine specific conductance from 1998 to 2018 suggest legacy contamination in the Delaware River Basin - Christine A. Rumsey; John C. Hammond; Jennifer Murphy; Megan Shoda; Alexander Soroka (Science of The Total Environment, 2023)

Melt-assisted deformation in the lower crust of an active plate boundary, Baja California - R.E. Bernard; E.J. Chin; C. Murphy (Lithos, 2023)

Leaching of phthalate acid esters from plastic mulch films and their degradation in response to UV irradiation and contrasting soil conditions - Samantha J. Viljoen; Francesca L. Brailsford; Daniel V. Murphy; Frances C. Hoyle; David R. Chadwick; Davey L. Jones (Journal of Hazardous Materials, 2023)

Differential response of migratory guilds of birds to park area and urbanization - Michael T. Murphy; David C. Bailey; Nathanael I. Lichti; Laura A. Roberts (Urban Ecosystems, 2023)

Exploring metapopulation‐scale suppression alternatives for a global invader in a river network experiencing climate change - Brian D. Healy; Phaedra Budy; Charles. B. Yackulic; Brendan P. Murphy; Robert C. Schelly; Mark C. McKinstry (Conservation Biology, 2023)
Invasive species can dramatically alter ecosystems, but eradication is difficult, and suppression is expensive once they are established. Uncertainties in the potential for expansion and impacts by an invader can lead to delayed and inadequate suppression, allowing for establishment. Metapopulation viability models can aid in planning strategies to improve responses to invaders and lessen invasive species’ impacts, which may be particularly important under climate change. We used a spatially explicit metapopulation viability model to explore suppression strategies for ecologically damaging invasive brown trout ( Salmo trutta ), established in the Colorado River and a tributary in Grand Canyon National Park. Our goals were to estimate the effectiveness of strategies targeting different life stages and subpopulations within a metapopulation; quantify the effectiveness of a rapid response to a new invasion relative to delaying action until establishment; and estimate whether future hydrology and temperature regimes related to climate change and reservoir management affect metapopulation viability and alter the optimal management response. Our models included scenarios targeting different life stages with spatially varying intensities of electrofishing, redd destruction, incentivized angler harvest, piscicides, and a weir. Quasi‐extinction (QE) was obtainable only with metapopulation‐wide suppression targeting multiple life stages. Brown trout population growth rates were most sensitive to changes in age 0 and large adult mortality. The duration of suppression needed to reach QE for a large established subpopulation was 12 years compared with 4 with a rapid response to a new invasion. Isolated subpopulations were vulnerable to suppression; however, connected tributary subpopulations enhanced metapopulation persistence by serving as climate refuges. Water shortages driving changes in reservoir storage and subsequent warming would cause brown trout declines, but metapopulation QE was achieved only through refocusing and increasing suppression. Our modeling approach improves understanding of invasive brown trout metapopulation dynamics, which could lead to more focused and effective invasive species suppression strategies and, ultimately, maintenance of populations of endemic fishes.

Nitrogen isotopes indicate vehicle emissions and biomass burning dominate ambient ammonia across Colorado's Front Range urban corridor - J. David Felix; Alexander Berner; Gregory A. Wetherbee; Sheila F. Murphy; Ruth C. Heindel (Environmental Pollution, 2023)

Ensuring planetary survival: the centrality of organic carbon in balancing the multifunctional nature of soils - Peter M. Kopittke; Asmeret Asefaw Berhe; Yolima Carrillo; Timothy R. Cavagnaro; Deli Chen; Qing-Lin Chen; Mercedes Román Dobarco; Feike A. Dijkstra; Damien J. Field; Michael J. Grundy; Ji-Zheng He; Frances C. Hoyle; et al. (Critical Reviews in Environmental Science and Technology, 2022)

An interaction of inorganic arsenic exposure with body weight and composition on type 2 diabetes indicators in Diversity Outbred mice - James G. Xenakis; Christelle Douillet; Timothy A. Bell; Pablo Hock; Joseph Farrington; Tianyi Liu; Caroline E. Y. Murphy; Avani Saraswatula; Ginger D. Shaw; Gustavo Nativio; Qing Shi; Abhishek Venkatratnam; et al. (Mammalian Genome, 2022)

Persistence and expansion of cryptic endangered red wolf genomic ancestry along the American Gulf coast - Bridgett M. vonHoldt; Kristin E. Brzeski; Matthew L. Aardema; Christopher J. Schell; Linda Y. Rutledge; Steven R. Fain; Amy C. Shutt; Anna Linderholm; William J. Murphy (Molecular Ecology, 2022)
Admixture and introgression play a critical role in adaptation and genetic rescue that has only recently gained a deeper appreciation. Here, we explored the geographical and genomic landscape of cryptic ancestry of the endangered red wolf that persists within the genome of a ubiquitous sister taxon, the coyote, all while the red wolf has been extinct in the wild since the early 1980s. We assessed admixture across 120,621 single nucleotiode polymorphism (SNP) loci genotyped in 293 canid genomes. We found support for increased red wolf ancestry along a west‐to‐east gradient across the southern United States associated with historical admixture in the past 100 years. Southwestern Louisiana and southeastern Texas, the geographical zone where the last red wolves were known prior to extinction in the wild, contained the highest and oldest levels of red wolf ancestry. Further, given the paucity of inferences based on chromosome types, we compared patterns of ancestry on the X chromosome and autosomes. We additionally aimed to explore the relationship between admixture timing and recombination rate variation to investigate gene flow events. We found that X‐linked regions of low recombination rates were depleted of introgression, relative to the autosomes, consistent with the large X effect and enrichment with loci involved in maintaining reproductive isolation. Recombination rate was positively correlated with red wolf ancestry across coyote genomes, consistent with theoretical predictions. The geographical and genomic extent of cryptic red wolf ancestry can provide novel genomic resources for recovery plans targeting the conservation of the endangered red wolf.

Links across ecological scales: Plant biomass responses to elevated CO 2 - Julia Maschler; Lalasia Bialic‐Murphy; Joe Wan; Louise C. Andresen; Constantin M. Zohner; Peter B. Reich; Andreas Lüscher; Manuel K. Schneider; Christoph Müller; Gerald Moser; Jeffrey S. Dukes; Inger Kappel Schmidt; et al. (Global Change Biology, 2022)
The degree to which elevated CO 2 concentrations (e[CO 2 ]) increase the amount of carbon (C) assimilated by vegetation plays a key role in climate change. However, due to the short‐term nature of CO 2 enrichment experiments and the lack of reconciliation between different ecological scales, the effect of e[CO 2 ] on plant biomass stocks remains a major uncertainty in future climate projections. Here, we review the effect of e[CO 2 ] on plant biomass across multiple levels of ecological organization, scaling from physiological responses to changes in population‐, community‐, ecosystem‐, and global‐scale dynamics. We find that evidence for a sustained biomass response to e[CO 2 ] varies across ecological scales, leading to diverging conclusions about the responses of individuals, populations, communities, and ecosystems. While the distinct focus of every scale reveals new mechanisms driving biomass accumulation under e[CO 2 ], none of them provides a full picture of all relevant processes. For example, while physiological evidence suggests a possible long‐term basis for increased biomass accumulation under e[CO 2 ] through sustained photosynthetic stimulation, population‐scale evidence indicates that a possible e[CO 2 ]‐induced increase in mortality rates might potentially outweigh the effect of increases in plant growth rates on biomass levels. Evidence at the global scale may indicate that e[CO 2 ] has contributed to increased biomass cover over recent decades, but due to the difficulty to disentangle the effect of e[CO 2 ] from a variety of climatic and land‐use‐related drivers of plant biomass stocks, it remains unclear whether nutrient limitations or other ecological mechanisms operating at finer scales will dampen the e[CO 2 ] effect over time. By exploring these discrepancies, we identify key research gaps in our understanding of the effect of e[CO 2 ] on plant biomass and highlight the need to integrate knowledge across scales of ecological organization so that large‐scale modeling can represent the finer‐scale mechanisms needed to constrain our understanding of future terrestrial C storage.

Memantine treatment does not affect compulsive behavior or frontostriatal connectivity in an adolescent rat model for quinpirole-induced compulsive checking behavior - Milou Straathof; Erwin L. A. Blezer; Christel E. Smeele; Caroline van Heijningen; Annette van der Toorn; Jan K. Buitelaar; Jeffrey C. Glennon; Willem M. Otte; Rick M. Dijkhuizen; Jan Buitelaar; Saskia de Ruiter; Jilly Naaijen; et al. (Psychopharmacology, 2022)
Rationale Compulsivity often develops during childhood and is associated with elevated glutamate levels within the frontostriatal system. This suggests that anti-glutamatergic drugs, like memantine, may be an effective treatment. Objective Our goal was to characterize the acute and chronic effect of memantine treatment on compulsive behavior and frontostriatal network structure and function in an adolescent rat model of compulsivity. Methods Juvenile Sprague–Dawley rats received repeated quinpirole, resulting in compulsive checking behavior ( n = 32; compulsive) or saline injections ( n = 32; control). Eight compulsive and control rats received chronic memantine treatment, and eight compulsive and control rats received saline treatment for seven consecutive days between the 10th and 12th quinpirole/saline injection. Compulsive checking behavior was assessed, and structural and functional brain connectivity was measured with diffusion MRI and resting-state fMRI before and after treatment. The other rats received an acute single memantine (compulsive: n = 12; control: n = 12) or saline injection (compulsive: n = 4; control: n = 4) during pharmacological MRI after the 12th quinpirole/saline injection. An additional group of rats received a single memantine injection after a single quinpirole injection ( n = 8). Results Memantine treatment did not affect compulsive checking nor frontostriatal structural and functional connectivity in the quinpirole-induced adolescent rat model. While memantine activated the frontal cortex in control rats, no significant activation responses were measured after single or repeated quinpirole injections. Conclusions The lack of a memantine treatment effect in quinpirole-induced compulsive adolescent rats may be partly explained by the interaction between glutamatergic and dopaminergic receptors in the brain, which can be evaluated with functional MRI.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Long-term Annual Aerial Surveys of Submersed Aquatic Vegetation (SAV) Support Science, Management, and Restoration - Robert J. Orth; William C. Dennison; Cassie Gurbisz; Michael Hannam; Jeni Keisman; J. Brooke Landry; Jonathan S. Lefcheck; Kenneth A. Moore; Rebecca R. Murphy; Christopher J. Patrick; Jeremy Testa; Donald E. Weller; et al. (Estuaries and Coasts, 2022)
Aerial surveys of coastal habitats can uniquely inform the science and management of shallow, coastal zones, and when repeated annually, they reveal changes that are otherwise difficult to assess from ground-based surveys. This paper reviews the utility of a long-term (1984–present) annual aerial monitoring program for submersed aquatic vegetation (SAV) in Chesapeake Bay, its tidal tributaries, and nearby Atlantic coastal bays, USA. We present a series of applications that highlight the program’s importance in assessing anthropogenic impacts, gauging water quality status and trends, establishing and evaluating restoration goals, and understanding the impact of commercial fishing practices on benthic habitats. These examples demonstrate how periodically quantifying coverage of this important foundational habitat answers basic research questions locally, as well as globally, and provides essential information to resource managers. New technologies are enabling more frequent and accurate aerial surveys at greater spatial resolution and lower cost. These advances will support efforts to extend the applications described here to similar issues in other areas.

Madagascar Terrestrial Camera Survey Database 2021: A collation of protected forest camera surveys from 2007–2021 - Erin M. Wampole; Brian D. Gerber; Zach J. Farris; Jean Claude Razafimahaimodison; Mahandry Hugues Andrianarisoa; Claude Jacquot Ralazampirenena; Patricia C. Wright; C. Delaid Rasamisoa; Dean Gibson; Mathias W. Tobler; Timothy M. Eppley; Natalie Vasey; et al. (Ecology, 2022)
Madagascar is a threatened global biodiversity hotspot and conservation priority, yet we lack broad‐scale surveys to assess biodiversity across space and time. To fill this gap, we collated camera trap surveys, capturing species occurrences within Madagascar into a single standardized database. This data set includes nine distinct protected areas of Madagascar and encompasses 13 subprojects, 38 camera arrays, and 1156 sampling units (independent camera site per survey) within two important biodiversity eco‐regions: western dry deciduous forest and eastern humid rainforest. Camera surveys were conducted from June 2007 to January 2021. The final data set includes 17 unique families of mammals (Bovidae, Canidae, Cheirogaleidae, Daubentoniidae, Equidae, Eupleridae, Felidae, Hominidae, Indriidae, Lemuridae, Lepilemuridae, Muridae, Nesomyidae, Pteropodidae, Soricidae, Suidae, Tenrecidae) comprising 45 species and 27 unique families of birds (Accipitridae, Acrocephalidae, Alcedinidae, Bernieridae, Brachypteraciidae, Caprimulgidae, Cisticolidae, Columbidae, Coraciidae, Corvidae, Cuculidae, Dicruridae, Mesitornithidae, Monarchidae, Motacillidae, Muscicapidae, Numididae, Phasianidae, Rallidae, Sarothruridae, Strigidae, Sturnidae, Sulidae, Threskiornithidae, Upupidae, Vangidae, Zosteropidae) comprising 58 species. Images were processed and verified by individual project data set creators and camera operation and species tables were then collated. The final product represents the first broad‐scale freely available standardized formal faunal database for Madagascar. Data are available through this publication and at DOI: 10.5281/zenodo.5801806. These data will be useful for examining species‐level and community‐level trends in occurrence across space or time within Madagascar and globally, evaluating native and invasive species dynamics, and will aid in determining species conservation status and planning for at‐risk species. There are no copyright restrictions; please cite this paper when using the data for publication.

Do CMIP models capture long-term observed annual precipitation trends? - S. M. Vicente-Serrano; R. García-Herrera; D. Peña-Angulo; M. Tomas-Burguera; F. Domínguez-Castro; I. Noguera; N. Calvo; C. Murphy; R. Nieto; L. Gimeno; J. M. Gutierrez; C. Azorin-Molina; et al. (Climate Dynamics, 2022)
This study provides a long-term (1891–2014) global assessment of precipitation trends using data from two station-based gridded datasets and climate model outputs evolved through the fifth and sixth phases of the Coupled Model Intercomparison Project (CMIP5 and CMIP6, respectively). Our analysis employs a variety of modeling groups that incorporate low- and high-top level members, with the aim of assessing the possible effects of including a well-resolved stratosphere on the model’s ability to reproduce long-term observed annual precipitation trends. Results demonstrate that only a few regions show statistically significant differences in precipitation trends between observations and models. Nevertheless, this pattern is mostly caused by the strong interannual variability of precipitation in most of the world regions. Thus, statistically significant model-observation differences on trends (1891–2014) are found at the zonal mean scale. The different model groups clearly fail to reproduce the spatial patterns of annual precipitation trends and the regions where stronger increases or decreases are recorded. This study also stresses that there are no significant differences between low- and high-top models in capturing observed precipitation trends, indicating that having a well-resolved stratosphere has a low impact on the accuracy of precipitation projections.

Barriers to Achieving Conservation Engineering Goals in Commercial Trawl Fisheries - Robert Murphy; Noëlle Yochum; Nathan Wolf; Anita C. Kroska; Bradley P. Harris (Frontiers in Marine Science, 2022)
The advancement of conservation practices in global trawl fisheries has been impeded in part by a lack of a collective understanding of the most relevant and broad-scale knowledge-needs, along with the identification of potential barriers to addressing these knowledge-needs. Using both an online survey and an in-person workshop, we engaged a diversity of fishing industry stakeholders including scientists, technology companies, trawl net makers, and fishermen working with North Pacific, United States, trawl fisheries to identify and prioritize areas in which further knowledge is required for successful implementation of conservation engineering practices. In addition, we identified barriers to addressing these knowledge-needs. Knowledge-needs related to fishing gear performance were identified among the top priorities, including several areas targeted at improving fishing efficiency that could further advance the sustainability of well-managed trawl fisheries. To better understand the composition and behavior of target versus non-target catch, workshop participants identified the importance of closing data and technology gaps. This highlights areas for potential collaboration between fishermen, researchers, and technology companies to address research prioritized by the end-user. Further, results from the workshop emphasized a need for industry-driven training and workshops focused on elevating fishermen skill for newer entrants through peer-learning and knowledge-sharing to achieve objectives like better non-target avoidance and increased fishing efficiency of the target species. Addressing these prioritized knowledge-needs, by first working toward overcoming the industry-identified barriers, may aid in increasing uptake of conservation practices, thereby contributing to the long-term sustainability of these fisheries and associated social-ecological systems.

Return Encounters in Emergency Department Patients Treated with Phenobarbital Versus Benzodiazepines for Alcohol Withdrawal - Jacob A. Lebin; Anita Mudan; Charles E. Murphy; Ralph C. Wang; Craig G. Smollin (Journal of Medical Toxicology, 2022)
Introduction Phenobarbital has been successfully used in the emergency department (ED) to manage symptoms of alcohol withdrawal, but few studies have reported outcomes for ED patients who receive phenobarbital and are discharged. We compared return encounter rates in discharged ED patients with alcohol withdrawal who were treated with benzodiazepines and phenobarbital. Methods This is a retrospective cohort study conducted at a single academic medical center utilizing chart review of discharged ED patients with alcohol withdrawal from July 1, 2016, to June 30, 2019. Patients were stratified according to ED management with benzodiazepines, phenobarbital, or a combination of both agents. The primary outcome was return ED encounter within three days of the index ED encounter. Multivariate logistic regression identified significant covariates of an ED return encounter. Results Of 470 patients who were discharged with the diagnosis of alcohol withdrawal, 235 were treated with benzodiazepines, 133 with phenobarbital, and 102 with a combination of both. Baseline characteristics were similar among the groups. However, patients who received phenobarbital were provided significantly more lorazepam equivalents compared to patients who received benzodiazepines alone. Treatment with phenobarbital, alone or in combination with benzodiazepines, was associated with significantly lower odds of a return ED visit within three days compared with benzodiazepines alone [AOR 0.45 (95% CI 0.23, 0.88) p = 0.02 and AOR 0.33 (95% CI 0.15, 0.74) p = 0.007]. Conclusions Patients who received phenobarbital for alcohol withdrawal were less likely to return to the ED within three days of the index encounter. Despite similar baseline characteristics, patients who received phenobarbital, with or without benzodiazepines, were provided greater lorazepam equivalents the ED.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Responsiveness of Gait and Balance Outcomes to Disease Progression in Friedreich Ataxia - Sarah C. Milne; Seok Hun Kim; Anna Murphy; Jane Larkindale; Jennifer Farmer; Ritchie Malapira; Mary Danoudis; Jessica Shaw; Tyagi Ramakrishnan; Fatemeh Rasouli; Eppie M. Yiu; Nellie Georgiou-Karistianis; et al. (The Cerebellum, 2021)

Untangling local and remote influences in two major petrel habitats in the oligotrophic Southern Ocean - Daniel C. Jones; Filipe R. Ceia; Eugene Murphy; Karine Delord; Robert W. Furness; Ariane Verdy; Matthew Mazloff; Richard A. Phillips; Paul M. Sagar; Jean‐Baptiste Sallée; Ben Schreiber; David R. Thompson; et al. (Global Change Biology, 2021)
Ocean circulation connects geographically distinct ecosystems across a wide range of spatial and temporal scales via exchanges of physical and biogeochemical properties. Remote oceanographic processes can be especially important for ecosystems in the Southern Ocean, where the Antarctic Circumpolar Current transports properties across ocean basins through both advection and mixing. Recent tracking studies have indicated the existence of two large‐scale, open ocean habitats in the Southern Ocean used by grey petrels ( Procellaria cinerea ) from two populations (i.e., Kerguelen and Antipodes islands) during their nonbreeding season for extended periods during austral summer (i.e., October to February). In this work, we use a novel combination of large‐scale oceanographic observations, surface drifter data, satellite‐derived primary productivity, numerical adjoint sensitivity experiments, and output from a biogeochemical state estimate to examine local and remote influences on these grey petrel habitats. Our aim is to understand the oceanographic features that control these isolated foraging areas and to evaluate their ecological value as oligotrophic open ocean habitats. We estimate the minimum local primary productivity required to support these populations to be much

Regional prefrontal cortical atrophy predicts specific cognitive-behavioral symptoms in ALS-FTD - Elena Ratti; Kimiko Domoto-Reilly; Christina Caso; Alyssa Murphy; Michael Brickhouse; Daisy Hochberg; Nikos Makris; Merit E. Cudkowicz; Bradford C. Dickerson (Brain Imaging and Behavior, 2021)

Imitating evolution’s tinkering by protein engineering reveals extension of human galectin-7 activity - Anna-Kristin Ludwig; Malwina Michalak; Adele Gabba; Tanja J. Kutzner; Donella M. Beckwith; Forrest G. FitzGerald; Gabriel García Caballero; Joachim C. Manning; Mark Kriegsmann; Herbert Kaltner; Paul V. Murphy; Maré Cudic; et al. (Histochemistry and Cell Biology, 2021)
Wild-type lectins have distinct types of modular design. As a step to explain the physiological importance of their special status, hypothesis-driven protein engineering is used to generate variants. Concerning adhesion/growth-regulatory galectins, non-covalently associated homodimers are commonly encountered in vertebrates. The homodimeric galectin-7 (Gal-7) is a multifunctional context-dependent modulator. Since the possibility of conversion from the homodimer to hybrids with other galectin domains, i.e. from Gal-1 and Gal-3, has recently been discovered, we designed Gal-7-based constructs, i.e. stable (covalently linked) homo- and heterodimers. They were produced and purified by affinity chromatography, and the sugar-binding activity of each lectin unit proven by calorimetry. Inspection of profiles of binding of labeled galectins to an array-like platform with various cell types, i.e. sections of murine epididymis and jejunum, and impact on neuroblastoma cell proliferation revealed no major difference between natural and artificial (stable) homodimers. When analyzing heterodimers, acquisition of altered properties was seen. Remarkably, binding properties and activity as effector can depend on the order of arrangement of lectin domains (from N- to C-termini) and on the linker length. After dissociation of the homodimer, the Gal-7 domain can build new functionally active hybrids with other partners. This study provides a clear direction for research on defining the full range of Gal-7 functionality and offers the perspective of testing applications for engineered heterodimers.

Disturbance type and species life history predict mammal responses to humans - Justin P. Suraci; Kaitlyn M. Gaynor; Maximilian L. Allen; Peter Alexander; Justin S. Brashares; Sara Cendejas‐Zarelli; Kevin Crooks; L. Mark Elbroch; Tavis Forrester; Austin M. Green; Jeffrey Haight; Nyeema C. Harris; et al. (Global Change Biology, 2021)
Human activity and land use change impact every landscape on Earth, driving declines in many animal species while benefiting others. Species ecological and life history traits may predict success in human‐dominated landscapes such that only species with “winning” combinations of traits will persist in disturbed environments. However, this link between species traits and successful coexistence with humans remains obscured by the complexity of anthropogenic disturbances and variability among study systems. We compiled detection data for 24 mammal species from 61 populations across North America to quantify the effects of (1) the direct presence of people and (2) the human footprint (landscape modification) on mammal occurrence and activity levels. Thirty‐three percent of mammal species exhibited a net negative response (i.e., reduced occurrence or activity) to increasing human presence and/or footprint across populations, whereas 58% of species were positively associated with increasing disturbance. However, apparent benefits of human presence and footprint tended to decrease or disappear at higher disturbance levels, indicative of thresholds in mammal species’ capacity to tolerate disturbance or exploit human‐dominated landscapes. Species ecological and life history traits were strong predictors of their responses to human footprint, with increasing footprint favoring smaller, less carnivorous, faster‐reproducing species. The positive and negative effects of human presence were distributed more randomly with respect to species trait values, with apparent winners and losers across a range of body sizes and dietary guilds. Differential responses by some species to human presence and human footprint highlight the importance of considering these two forms of human disturbance separately when estimating anthropogenic impacts on wildlife. Our approach provides insights into the complex mechanisms through which human activities shape mammal communities globally, revealing the drivers of the loss of larger predators in human‐modified landscapes.

Highlights of the Virtual 2021 North American Agricultural Safety Summit - Barbara C. Lee; Dan M. Hair; Jess McCluer; Dennis J. Murphy; Andrea V.R. Swenson (Journal of Agromedicine, 2021)

Liver injury during rivaroxaban treatment in a patient with AL amyloidosis - Alan Marrinan; L. Shackleton; C. Kelly; M. Lavin; S. Glavey; P. Murphy; J. Quinn (European Journal of Clinical Pharmacology, 2021)

A Decade of Incorporating Social Sciences in the Integrated Marine Biosphere Research Project (IMBeR): Much Done, Much to Do? - Ingrid van Putten; Rachel Kelly; Rachel D. Cavanagh; Eugene J. Murphy; Annette Breckwoldt; Stephanie Brodie; Christopher Cvitanovic; Mark Dickey-Collas; Lisa Maddison; Jess Melbourne-Thomas; Haritz Arrizabalaga; Kumiko Azetsu-Scott; et al. (Frontiers in Marine Science, 2021)
Successful management and mitigation of marine challenges depends on cooperation and knowledge sharing which often occurs across culturally diverse geographic regions. Global ocean science collaboration is therefore essential for developing global solutions. Building effective global research networks that can enable collaboration also need to ensure inter- and transdisciplinary research approaches to tackle complex marine socio-ecological challenges. To understand the contribution of interdisciplinary global research networks to solving these complex challenges, we use the Integrated Marine Biosphere Research (IMBeR) project as a case study. We investigated the diversity and characteristics of 1,827 scientists from 11 global regions who were attendees at different IMBeR global science engagement opportunities since 2009. We also determined the role of social science engagement in natural science based regional programmes (using key informants) and identified the potential for enhanced collaboration in the future. Event attendees were predominantly from western Europe, North America, and East Asia. But overall, in the global network, there was growing participation by females, students and early career researchers, and social scientists, thus assisting in moving toward interdisciplinarity in IMBeR research. The mainly natural science oriented regional programmes showed mixed success in engaging and collaborating with social scientists. This was mostly attributed to the largely natural science (i.e., biological, physical) goals and agendas of the programmes, and the lack of institutional support and push to initiate connections with social science. Recognising that social science research may not be relevant to all the aims and activities of all regional programmes, all researchers however, recognised the (potential) benefits of interdisciplinarity, which included broadening scientists’ understanding and perspectives, developing connections and interlinkages, and making science more useful. Pathways to achieve progress in regional programmes fell into four groups: specific funding, events to come together, within-programme-reflections, and social science champions. Future research programmes should have a strategic plan to be truly interdisciplinary, engaging natural and social sciences, as well as aiding early career professionals to actively engage in such programmes.

Correction to: Unraveling unique island colonization events in Elachistocleis frogs: phylogeography, cryptic divergence, and taxonomical implications - Michael J. Jowers; Siti N. Othman; Amaël Borzée; Gilson A. Rivas; Santiago Sánchez-Ramírez; Renoir J. Auguste; J. Roger Downie; Morley Read; John C. Murphy (Organisms Diversity & Evolution, 2021)

Unraveling unique island colonization events in Elachistocleis frogs: phylogeography, cryptic divergence, and taxonomical implications - Michael J. Jowers; Siti N. Othman; Amaël Borzée; Gilson A. Rivas; Santiago Sánchez-Ramírez; Renoir J. Auguste; J. Roger Downie; Morley Read; John C. Murphy (Organisms Diversity & Evolution, 2021)

Global drivers of recent diversification in a marine species complex - Catarina N.S. Silva; Nicholas P. Murphy; James J. Bell; Bridget S. Green; Guy Duhamel; Andrew C. Cockcroft; Cristián E. Hernández; Jan M. Strugnell (Molecular Ecology, 2021)
Investigating historical gene flow in species complexes can indicate how environmental and reproductive barriers shape genome divergence during speciation. The processes influencing species diversification under environmental change remain one of the central focal points of evolutionary biology, particularly for marine organisms with high dispersal potential. We investigated genome‐wide divergence, introgression patterns and inferred demographic history between species pairs of all six extant rock lobster species ( Jasus spp.), which have a long larval duration of up to two years and have populated continental shelf and seamount habitats around the globe at approximately 40 o S. Genetic differentiation patterns reflected geographic isolation and the environment (i.e. habitat structure). Eastern Pacific species ( J. caveorum and J. frontalis ) were geographically more distant and genetically more differentiated from the remaining four species. Species associated with continental shelf habitats shared a common ancestry, but are geographically distant from one another. Similarly, species associated with island/seamount habitats in the Atlantic and Indian Oceans shared a common ancestry, but are also geographically distant. Benthic temperature was the environmental variable that explained most of the genetic differentiation (F ST ), while controlling for the effects of geographic distance. Eastern Pacific species retained a signal of strict isolation following ancient migration, whereas species pairs from Australia and Africa, and seamounts in the Indian and Atlantic oceans, included events of introgression after secondary contact. Our results reveal important effects of habitat and demographic processes on the recent divergence of species within the genus Jasus , providing one of the first empirical studies of genome‐wide drivers of diversification that incorporates all extant species in a marine genus with long pelagic larval duration.

Not withering on the evolutionary vine: systematic revision of the Brown Vine Snake (Reptilia: Squamata: Oxybelis) from its northern distribution - Robert C. Jadin; Christopher Blair; Sarah A. Orlofske; Michael J. Jowers; Gilson A. Rivas; Laurie J. Vitt; Julie M. Ray; Eric N. Smith; John C. Murphy (Organisms Diversity & Evolution, 2020)

Trait‐based ecology at large scales: Assessing functional trait correlations, phylogenetic constraints and spatial variability using open data - Martin A. Wilkes; François Edwards; J. Iwan Jones; John F. Murphy; Judy England; Nikolai Friberg; Daniel Hering; N. LeRoy Poff; Philippe Usseglio‐Polatera; Wilco C. E. P. Verberk; Jon Webb; Lee E. Brown (Global Change Biology, 2020)
The growing use of functional traits in ecological research has brought new insights into biodiversity responses to global environmental change. However, further progress depends on overcoming three major challenges involving (a) statistical correlations between traits, (b) phylogenetic constraints on the combination of traits possessed by any single species, and (c) spatial effects on trait structure and trait–environment relationships. Here, we introduce a new framework for quantifying trait correlations, phylogenetic constraints and spatial variability at large scales by combining openly available species’ trait, occurrence and phylogenetic data with gridded, high‐resolution environmental layers and computational modelling. Our approach is suitable for use among a wide range of taxonomic groups inhabiting terrestrial, marine and freshwater habitats. We demonstrate its application using freshwater macroinvertebrate data from 35 countries in Europe. We identified a subset of available macroinvertebrate traits, corresponding to a life‐history model with axes of resistance, resilience and resource use, as relatively unaffected by correlations and phylogenetic constraints. Trait structure responded more consistently to environmental variation than taxonomic structure, regardless of location. A re‐analysis of existing data on macroinvertebrate communities of European alpine streams supported this conclusion, and demonstrated that occurrence‐based functional diversity indices are highly sensitive to the traits included in their calculation. Overall, our findings suggest that the search for quantitative trait–environment relationships using single traits or simple combinations of multiple traits is unlikely to be productive. Instead, there is a need to embrace the value of conceptual frameworks linking community responses to environmental change via traits which correspond to the axes of life‐history models. Through a novel integration of tools and databases, our flexible framework can address this need.

Spatio-Temporal Variability of Harbor Porpoise Life History Parameters in the North-East Atlantic - Sinéad Murphy; Marie A. C. Petitguyot; Paul D. Jepson; Rob Deaville; Christina Lockyer; James Barnett; Matthew Perkins; Rod Penrose; Nicholas J. Davison; Cóilín Minto (Frontiers in Marine Science, 2020)
Harbor porpoises exhibit early maturation, relatively short gestation/lactation periods and a faster rate of reproduction as compared to other cetacean species. Intrinsic and extrinsic factors can influence both population vital rates and population structure, which ultimately cause changes in dynamics within and between populations. Here, we undertook a retrospective analysis of mortality data collected over a 24-year period for assessing life history traits of the North-east Atlantic harbor porpoise population. We use time-period specific models for key life history relationships that considered cause of death of individuals (as a proxy for health status), sex and management unit (MU). Sexual variation in asymptotic length, asymptotic age, average length at 50% maturity (L50) and average age at 50% maturity (A50) were observed, with females attaining a larger asymptotic length, larger L50, and delaying attainment of both sexual and physical maturity, compared to males. While females are constrained in their minimum body size due to giving birth to proportionally larger offspring, males exhibited more plasticity in size at sexual maturity, enabling re-allocation of available energy resources toward reproduction. Data were then used to compare biological parameters among two porpoise MUs in United Kingdom waters, both of which in the current study exhibited reduced reproductive rates compared to other geographic regions. In both MUs, females significantly increased their A50 and males significantly declined in their L50. An increase in the age at asymptotic length was also observed in both sexes, along with a significant decline in the Gompertz growth rate parameter that was more apparent in the female data. While availability of suitable prey resources may be a limiting factor, a combination of other factors cannot be ruled out. Porpoises in the Celtic and Irish Seas MU were significantly larger in their maximum length, asymptotic length and L50 compared to porpoises in the North Sea MU throughout the study period, suggesting limited gene flow between these two MUs. These results justify the maintenance of these harbor porpoise MUs or assessment units, as two separate units, within the range of the North-east Atlantic population, and for indicator assessments under the EU’s Marine Strategy Framework Directive.

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

Potential of tropical macroalgae from French Polynesia for biotechnological applications - Mayalen Zubia; Olivier P. Thomas; Stéphanie Soulet; Marina Demoy-Schneider; Denis Saulnier; Solène Connan; Elliot C. Murphy; Florent Tintillier; Valérie Stiger-Pouvreau; Sylvain Petek (Journal of Applied Phycology, 2020)

Influence of protein (human galectin-3) design on aspects of lectin activity - Gabriel García Caballero; Donella Beckwith; Nadezhda V. Shilova; Adele Gabba; Tanja J. Kutzner; Anna-Kristin Ludwig; Joachim C. Manning; Herbert Kaltner; Fred Sinowatz; Mare Cudic; Nicolai V. Bovin; Paul V. Murphy; et al. (Histochemistry and Cell Biology, 2020)
The concept of biomedical significance of the functional pairing between tissue lectins and their glycoconjugate counterreceptors has reached the mainstream of research on the flow of biological information. A major challenge now is to identify the principles of structure–activity relationships that underlie specificity of recognition and the ensuing post-binding processes. Toward this end, we focus on a distinct feature on the side of the lectin, i.e. its architecture to present the carbohydrate recognition domain (CRD). Working with a multifunctional human lectin, i.e. galectin-3, as model, its CRD is used in protein engineering to build variants with different modular assembly. Hereby, it becomes possible to compare activity features of the natural design, i.e. CRD attached to an N-terminal tail, with those of homo- and heterodimers and the tail-free protein. Thermodynamics of binding disaccharides proved full activity of all proteins at very similar affinity. The following glycan array testing revealed maintained preferential contact formation with N -acetyllactosamine oligomers and histo-blood group ABH epitopes irrespective of variant design. The study of carbohydrate-inhibitable binding of the test panel disclosed up to qualitative cell-type-dependent differences in sections of fixed murine epididymis and especially jejunum. By probing topological aspects of binding, the susceptibility to inhibition by a tetravalent glycocluster was markedly different for the wild-type vs the homodimeric variant proteins. The results teach the salient lesson that protein design matters: the type of CRD presentation can have a profound bearing on whether basically suited oligosaccharides, which for example tested positively in an array, will become binding partners in situ . When lectin-glycoconjugate aggregates (lattices) are formed, their structural organization will depend on this parameter. Further testing (ga)lectin variants will thus be instrumental (i) to define the full range of impact of altering protein assembly and (ii) to explain why certain types of design have been favored during the course of evolution, besides opening biomedical perspectives for potential applications of the novel galectin forms.

Correction to: Influence of protein (human galectin-3) design on aspects of lectin activity - Gabriel García Caballero; Donella Beckwith; Nadezhda V. Shilova; Adele Gabba; Tanja J. Kutzner; Anna-Kristin Ludwig; Joachim C. Manning; Herbert Kaltner; Fred Sinowatz; Mare Cudic; Nicolai V. Bovin; Paul V. Murphy; et al. (Histochemistry and Cell Biology, 2020)

Experimental Assessment of Two Non-Contrast MRI Sequences Used for Computational Fluid Dynamics: Investigation of Consistency Between Techniques - C. J. MacDonald; R. Hellmuth; L. Priba; E. Murphy; S. Gandy; S. Matthew; R. Ross; J. G. Houston (Cardiovascular Engineering and Technology, 2020)
Purpose Recent studies have noted a degree of variance between the geometries segmented by different groups from 3D medical images that are used in computational fluid dynamics (CFD) simulations of patient-specific cardiovascular systems. The aim of this study was to determine if the applied sequence of magnetic resonance imaging (MRI) also introduced observable variance in CFD results. Methods Using a series of phantoms MR images of vessels of known diameter were assessed for the time-of-flight and multi-echo data image combination sequences. Following this, patient images of arterio-venous fistulas were acquired using the same sequences. Comparisons of geometry were made using the phantom and patient images, and of wall shear stress quantities using the CFD results from the patient images. Results Phantom images showed deviations in diameter between 0 and 15% between the sequences, depending on vessel diameter. Patient images showed different geometrical features such as narrowings that were not present on both sequences. Distributions of wall shear stress (WSS) quantities differed from simulations between the geometries obtained from the sequences. Conclusion In conclusion, choosing different MRI sequences resulted in slightly different geometries of the same anatomy, which led to compounded errors in WSS quantities from CFD simulation.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

A survey of the oral cavity microbiome of New Zealand fur seal pups ( Arctocephalus forsteri ) - Arsalan Emami‐Khoyi; Isma Benmazouz; James G. Ross; Laura J. Boren; Elaine C. Murphy; Bettine Jansen van Vuuren; Peter R. Teske; Adrian M. Paterson (Marine Mammal Science, 2020)

Metagenomics coupled with biogeochemical rates measurements provide evidence that nitrate addition stimulates respiration in salt marsh sediments - Ashley N. Bulseco; Joseph H. Vineis; Anna E. Murphy; Amanda C. Spivak; Anne E. Giblin; Jane Tucker; Jennifer L. Bowen (Limnology and Oceanography, 2020)
High‐throughput sequencing has enabled robust shotgun metagenomic sequencing that informs our understanding of the genetic basis of important biogeochemical processes. Slower to develop, however, are the application of these tools in a controlled experimental framework that pushes the field beyond exploratory analysis toward hypothesis‐driven research. We performed flow‐through reactor experiments to examine how salt marsh sediments from varying depths respond to nitrate addition and linked biogeochemical processes to this underlying genetic foundation. Understanding the mechanistic basis of carbon and nitrogen cycling in salt marsh sediments is critical for predicting how important ecosystem services provided by marshes, including carbon storage and nutrient removal, will respond to global change. Prior to the addition of nitrate, we used metagenomics to examine the functional potential of the sediment microbial community that occurred along a depth gradient, where organic matter reactivity changes due to decomposition. Metagenomic data indicated that genes encoding enzymes involved in respiration, including denitrification, were higher in shallow sediments, and genes indicative of resource limitation were greatest at depth. After 92 d of nitrate enrichment, we measured cumulative increases in dissolved inorganic carbon production, denitrification, and dissimilatory nitrate reduction to ammonium; these rates correlated strongly with genes that encode essential enzymes in these important pathways. Our results highlight the importance of controlled experiments in linking biogeochemical rates to underlying genetic pathways. Furthermore, they indicate the importance of nitrate as an electron acceptor in fueling microbial respiration, which has consequences for carbon and nitrogen cycling and fate in coastal marine systems.

Significant population methylation divergence and local environmental influence in an invasive ascidian Ciona intestinalis at fine geographical scales - Ping Ni; Kieran J. Murphy; Russell C. Wyeth; Cory D. Bishop; Shiguo Li; Aibin Zhan (Marine Biology, 2019)

Geography is more important than host plant use for the population genetic structure of a generalist insect herbivore - Mayra C. Vidal; Tom W. Quinn; John O. Stireman; Robin M. Tinghitella; Shannon M. Murphy (Molecular Ecology, 2019)
Population divergence can occur due to mechanisms associated with geographic isolation and/or due to selection associated with different ecological niches. Much of the evidence for selection‐driven speciation has come from studies of specialist insect herbivores that use different host plant species; however, the influence of host plant use on population divergence of generalist herbivores remains poorly understood. We tested how diet breadth, host plant species and geographic distance influence population divergence of the fall webworm ( Hyphantria cunea ; FW). FW is a broadly distributed, extreme generalist herbivore consisting of two morphotypes that have been argued to represent two different species: black‐headed and red‐headed. We characterized the differentiation of FW populations at two geographic scales. We first analysed the influence of host plant and geographic distance on genetic divergence across a broad continental scale for both colour types. We further analysed the influence of host plant, diet breadth and geographic distance on divergence at a finer geographic scale focusing on red‐headed FW in Colorado. We found clear genetic and morphological distinction between red‐ and black‐headed FW, and Colorado FW formed a genetic cluster distinct from other locations. Although both geographic distance and host plant use were correlated with genetic distance, geographic distance accounted for up to 3× more variation in genetic distance than did host plant use. As a rare study investigating the genetic structure of a widespread generalist herbivore over a broad geographic range (up to 3,000 km), our study supports a strong role for geographic isolation in divergence in this system.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Changes in local free-living parasite populations in response to cleaner manipulation over 12 years - A. S. Grutter; S. P. Blomberg; S. Box; R. Bshary; O. Ho; E. M. P. Madin; E. C. McClure; M. G. Meekan; J. M. Murphy; M. A. Richardson; P. C. Sikkel; C. A. Sims; et al. (Oecologia, 2019)

Agricultural Youth Injuries: A Review of 2015-2017 Cases from U.S. News Media Reports - Bryan Weichelt; Serap Gorucu; Dennis Murphy; Anita Alves Pena; Marsha Salzwedel; Barbara C. Lee (Journal of Agromedicine, 2019)

Finding plausible and diverse variants of a climate model. Part 1: establishing the relationship between errors at weather and climate time scales - D. M. H. Sexton; A. V. Karmalkar; J. M. Murphy; K. D. Williams; I. A. Boutle; C. J. Morcrette; A. J. Stirling; S. B. Vosper (Climate Dynamics, 2019)

Conserving New Zealand’s native fauna: a review of tools being developed for the Predator Free 2050 programme - Elaine C. Murphy; James C. Russell; Keith G. Broome; Grant J. Ryan; John E. Dowding (Journal of Ornithology, 2019)

Detecting symptoms of Phytophthora cinnamomi infection in Australian native vegetation using reflectance spectrometry: complex effects of water stress and species susceptibility - Z. Newby; R. J. Murphy; D. I. Guest; D. Ramp; E. C. Y Liew (Australasian Plant Pathology, 2019)

The reduced limbed lizards of the genus Bachia (Reptilia, Squamata, Gymnophthalmidae); biogeography, cryptic diversity, and morphological convergence in the eastern Caribbean - John C. Murphy; Daniele Salvi; Joana L. Santos; Alvin L. Braswell; Stevland P. Charles; Amaél Borzée; Michael J. Jowers (Organisms Diversity & Evolution, 2019)

Staphylococcus aureus heme and siderophore-iron acquisition pathways - Brigid S. Conroy; Jason C. Grigg; Maxim Kolesnikov; L. Daniela Morales; Michael E. P. Murphy (BioMetals, 2019)

A glycine transporter SLC6A5 frameshift mutation causes startle disease in Spanish greyhounds - Sarah C. Murphy; Alfredo Recio; Cristian de la Fuente; Ling T. Guo; G. Diane Shelton; Leigh Anne Clark (Human Genetics, 2019)

See how they run: increased ranging behavior counters potential Allee effects in experimentally introduced house mice on an island - J. W. B. MacKay; J. C. Russell; M. N. Clout; E. C. Murphy; M. E. Hauber (Biological Invasions, 2019)

Phylogeography of West Indies Coral snakes ( Micrurus ): Island colonisation and banding patterns - Michael J. Jowers; Juan Luis Garcia Mudarra; Stevland P. Charles; John C. Murphy (Zoologica Scripta, 2019)
In this study, we analyse New World coral snakes in a phylogenetic framework based upon an increased molecular data set, including novel sequences for the only two sympatric species known from an island (Trinidad, West Indies). Their presence in Trinidad and absence in Tobago offers a unique system to study the phylogeography of the region. We assess the tempo and mode of colonisation of Micrurus on the island, in addition to discussing the phylogenetic relationships for the genus Micrurus concerning two phenotypic traits, body and tail banding patterns. These relationships are analysed for the first time on statistical coalescent phylogeographic discrete ancestral reconstruction. We find a robust phylogenetic component in these characteristics, where strongly supported clades are recovered: prior to the onset of the Early Miocene, a triadal and tricolour tail clade composed of species from South America, and a second clade dating to the Middle‐Late‐ Miocene with monadal and bicolour tails widely distributed from North to South America. The divergence between clades dates to the Oligocene and suggests an ancient pre‐isthmus divergence supporting the arrival of the triadal clade into South America, before the connection between Central and South America was established. We find the two coral snakes present in the West Indies, M. diutius and M. circinalis , belong to the triadal and monadal clades, respectively. Guyana and Trinidad Micrurus diutius share the same haplotypes suggesting a Late Pleistocene–Holocene vicariance when sea level rises separated Trinidad from the mainland. A second lineage of diutius ‐like snakes is present in Guyana and is confirmed as M. lemniscatus which is assigned as a voucher and restricts the type locality for M. lemniscatus.

Urinary Gadolinium Levels After Contrast-Enhanced MRI in Individuals with Normal Renal Function: a Pilot Study - Dalia Alwasiyah; Christine Murphy; Paul Jannetto; Melanie Hogg; Michael C. Beuhler (Journal of Medical Toxicology, 2019)

Genetic diversity and structure of the threatened striped legless lizard, Delma impar: management implications for the species and a translocated population - Codie Murphy; Scott Burnett; Gabriel C. Conroy; Brett W. A. Howland; Robert W. Lamont; Joanna Sumner; Steven M. Ogbourne (Conservation Genetics, 2019)

El Niño–Southern Oscillation incidence over long dry sequences and their impact on soil water storage in Argentina - Olga C. Penalba; Vanesa C. Pántano; Liliana B. Spescha; Guillermo M. Murphy (International Journal of Climatology, 2019)
The deficit of daily precipitation, persistent over time (long dry sequences [LDS]), causes economic losses in the east–northeast of Argentina where agriculture production is the main economic activity. For this reason, an improvement in the seasonal prediction of the frequency of precipitation is required. Among several forcings influencing the region of study, El Niño–Southern Oscillation (ENSO) has been identified as responsible for a great part of the inter‐annual variability of precipitation. Therefore, in this study, we assess the ENSO signal on LDS and the response of soil water storage under the different phases. In order to assess this issue, daily data were used from 30 meteorological stations. Based on this information, dry sequences were quantified considering a dry day when the accumulated precipitation of two consecutive days was lower than 5 mm. From the dry sequences, two different thresholds were used to identify LDS. On one hand, the 85th percentile was selected as a spatially variable threshold and, on the other hand, 15‐day length was used as a fixed one. Based on this selection, the severity and the number of LDS were analysed. In general terms, La Niña (El Niño) phase presents higher (lower) severity and higher (lower) probability in the occurrence of more than one LDS per season, except in winter. This result is in concordance with negative (positive) anomalies of accumulated precipitation under La Niña (El Niño) phase. Regarding the impact on the water balance, soil water storage responds to accumulated precipitation anomalies in all the seasons.

Citizen science sampling programs as a technique for monitoring microplastic pollution: results, lessons learned and recommendations for working with volunteers for monitoring plastic pollution in freshwater ecosystems - Shaun A. Forrest; Larissa Holman; Meaghan Murphy; Jesse C. Vermaire (Environmental Monitoring and Assessment, 2019)

Quantitative measure of fitness in tri‐trophic interactions and its influence on diet breadth of insect herbivores - Mayra C. Vidal; Shannon M. Murphy (Ecology, 2018)
Herbivore‐plant interactions should be studied using a tri‐trophic approach, but we lack a quantitative measure of the combined effect of top‐down and bottom‐up forces on herbivore fitness. We propose the combination of the bi‐trophic fitness slopes as a tri‐trophic fitness measure. We use the relationship between fitness associated with top‐down and bottom‐up forces and the frequency of host plant use to calculate the top‐down and bottom‐up fitness slopes, which we then combine to obtain three possible directions of tri‐trophic slopes. A positive tri‐trophic slope indicates that herbivores have overall greater tri‐trophic fitness on the more frequently used hosts. A null tri‐trophic fitness slope indicates that herbivores have similar fitness on all host plants. A negative tri‐trophic slope indicates that herbivores have generally lower fitness on the more frequently used hosts. We tested the explanation power of our method using data from the literature that tested herbivore host shifts and experimentally using a generalist herbivore with variable diet breadth across populations. We found that in host shifts, herbivores have higher tri‐trophic fitness on the novel host, while in generalist populations, herbivores use most frequently the best host available. We present applications in other research areas and consider the limitations of our approach. Our approach is a first step towards a comprehensive model of multiple selective forces acting on the evolution of interactions.

Colorectal cancer incidence among Hispanics and non-Hispanic Whites in the United States - Sandra Garcia; Sandi L. Pruitt; Amit G. Singal; Caitlin C. Murphy (Cancer Causes & Control, 2018)

The acute effects of walking exercise intensity on systemic cytokines and oxidative stress - Malcolm Brown; Conor M. McClean; Gareth W. Davison; John C. W. Brown; Marie H. Murphy (European Journal of Applied Physiology, 2018)

Impact of toll-like receptor 4 stimulation on human neonatal neutrophil spontaneous migration, transcriptomics, and cytokine production - Steven L. Raymond; Russell B. Hawkins; Tyler J. Murphy; Jaimar C. Rincon; Julie A. Stortz; María Cecilia López; Ricardo Ungaro; Felix Ellett; Henry V. Baker; James L. Wynn; Lyle L. Moldawer; Daniel Irimia; et al. (Journal of Molecular Medicine, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Differential Effects of Bivalves on Sediment Nitrogen Cycling in a Shallow Coastal Bay - Ashley R. Smyth; Anna E. Murphy; Iris C. Anderson; Bongkeun Song (Estuaries and Coasts, 2018)

Historical forcings as main drivers of the Atlantic multidecadal variability in the CESM large ensemble - Katinka Bellomo; Lisa N. Murphy; Mark A. Cane; Amy C. Clement; Lorenzo M. Polvani (Climate Dynamics, 2018)

Nutrient- and Climate-Induced Shifts in the Phenology of Linked Biogeochemical Cycles in a Temperate Estuary - Jeremy M. Testa; Rebecca R. Murphy; Damian C. Brady; William M. Kemp (Frontiers in Marine Science, 2018)

Leadership and Funding: Changes Ahead for Agricultural Safety and Health - Dennis J. Murphy; Barbara C. Lee (Journal of Agromedicine, 2018)

Effects of Gestation Pens Versus Stalls and Wet Versus Dry Feed on Air Contaminants in Swine Production - Peter C. Raynor; Shannon Engelman; Darby Murphy; Gurumurthy Ramachandran; Jeffrey B. Bender; Bruce H. Alexander (Journal of Agromedicine, 2018)

Bottom‐up vs. top‐down effects on terrestrial insect herbivores: a meta‐analysis - Mayra C. Vidal; Shannon M. Murphy (Ecology Letters, 2018)
Primary consumers are under strong selection from resource (‘bottom‐up’) and consumer (‘top‐down’) controls, but the relative importance of these selective forces is unknown. We performed a meta‐analysis to compare the strength of top‐down and bottom‐up forces on consumer fitness, considering multiple predictors that can modulate these effects: diet breadth, feeding guild, habitat/environment, type of bottom‐up effects, type of top‐down effects and how consumer fitness effects are measured. We focused our analyses on the most diverse group of primary consumers, herbivorous insects, and found that in general top‐down forces were stronger than bottom‐up forces. Notably, chewing, sucking and gall‐making herbivores were more affected by top‐down than bottom‐up forces, top‐down forces were stronger than bottom‐up in both natural and controlled (cultivated) environments, and parasitoids and predators had equally strong top‐down effects on insect herbivores. Future studies should broaden the scope of focal consumers, particularly in understudied terrestrial systems, guilds, taxonomic groups and top‐down controls (e.g. pathogens), and test for more complex indirect community interactions. Our results demonstrate the surprising strength of forces exerted by natural enemies on herbivorous insects, and thus the necessity of using a tri‐trophic approach when studying insect‐plant interactions.

Perceptuo-motor planning during functional reaching after stroke - Margit Alt Murphy; Melanie C. Baniña; Mindy F. Levin (Experimental Brain Research, 2017)

Assessing how accumulated precipitation and long dry sequences impact the soil water storage - Vanesa C. Pántano; Olga C. Penalba; Liliana B. Spescha; Guillermo M. Murphy (International Journal of Climatology, 2017)
Precipitation or no precipitation persistent over time often became extreme weather conditions with greater regional economic impact. The temporal and spatial variability of these variables, together with the evapotranspiration, is crucial in the east‐northeast of Argentina, where rain‐fed agricultural production is carried out. In this work, the frequency of precipitation was studied from dry spells and complemented with an analysis of the accumulated precipitation and evapotranspiration. In particular, dry sequences longer than 15 days, return period and severity, were the focus of this study. Finally, the impact of the amount and frequency of precipitation on soil water storage was assessed through a decadal analysis. The region of study is characterized by northeast‐southwest gradient in accumulated precipitation and east–west gradient in winter long dry sequences. During summer, higher and more frequent precipitations (lower probability of long dry sequences and lower return period of 15 days and severity) were presented whereas the opposite was found in winter. However, the stations located to the west presented the highest probability of long dry sequences with higher severity and lower accumulated precipitation. This result highlights the vulnerability of the agriculture activity in the western stations. Regarding the impact of long dry sequences over soil water storage, the seasonality of evapotranspiration is also involved. The impact is stronger during austral summer because of higher values of evapotranspiration and it is lower during winter, in spite of the higher probability of long sequences. Decadal analysis suggested that soil water storage responds to precipitation amount or frequency depending on the magnitude of the anomalies. In this sense, the impact of precipitation over soil water storage depends on how it is distributed.

A Synergistic Approach for Evaluating Climate Model Output for Ecological Applications - Rachel D. Cavanagh; Eugene J. Murphy; Thomas J. Bracegirdle; John Turner; Cheryl A. Knowland; Stuart P. Corney; Walker O. Smith; Claire M. Waluda; Nadine M. Johnston; Richard G. J. Bellerby; Andrew J. Constable; Daniel P. Costa; et al. (Frontiers in Marine Science, 2017)

Tooth loss and liver cancer incidence in a Finnish cohort - Baiyu Yang; Jessica L. Petrick; Christian C. Abnet; Barry I. Graubard; Gwen Murphy; Stephanie J. Weinstein; Satu Männistö; Demetrius Albanes; Katherine A. McGlynn (Cancer Causes & Control, 2017)

A 250‐year drought catalogue for the island of Ireland (1765–2015) - S. Noone; C. Broderick; C. Duffy; T. Matthews; R.L. Wilby; C. Murphy (International Journal of Climatology, 2017)
This work created a 250‐year historic drought catalogue by applying the Standardized Precipitation Index ( SPI ) to the Island of Ireland precipitation network (1850–2015) and a reconstructed precipitation series from 1765. Documentary sources from newspaper archives spanning the last 250 years, together with other historical sources are used to (1) add confidence to the quantitative detection of drought episodes and (2) gain insight to the socio‐economic impacts of historic droughts. The results show that Ireland is drought prone but recent decades are unrepresentative of the longer‐term drought climatology. A large decline in 30‐year accumulated SPI ‐12 values is evident from around the 1990s onwards. During the years 1850–2015 seven major drought rich periods were identified with an island‐wide fingerprint in 1854–1860, 1884–1896, 1904–1912, 1921–1923, 1932–1935, 1952–1954 and 1969–1977. These events exhibit substantial diversity in terms of drought development, severity and spatial occurrence. Two exceptionally long events are found in the record: the continuous drought of 1854–1860 and the drought of 1800–1809 (in fact a series of three droughts with brief interludes). Over the last 250 years, droughts have resulted in agricultural hardship, water resource crises and failures and preceded some of the major famines of the eighteenth and nineteenth centuries. This work shows that newspaper archives can be used to trace the progression of drought events and impacts and we thus advocate their wider use in corroborating quantitative assessments. The resulting catalogue challenges prevailing perceptions about drought in Ireland while strengthening the evidence base for future drought and water resource planning across the island.

Mother–infant interactions and regional brain volumes in infancy: an MRI study - Vaheshta Sethna; Inês Pote; Siying Wang; Maria Gudbrandsen; Anna Blasi; Caroline McCusker; Eileen Daly; Emily Perry; Kerrie P. H. Adams; Maria Kuklisova-Murgasova; Paula Busuulwa; Sarah Lloyd-Fox; et al. (Brain Structure and Function, 2017)

New approaches to antibiotic discovery - C. Kealey; C. A. Creaven; C. D. Murphy; C. B. Brady (Biotechnology Letters, 2017)

Evaluation of the BioFire FilmArray® GastrointestinalPanel in a Midwestern Academic Hospital - C. N. Murphy; R. C. Fowler; P. C. Iwen; P. D. Fey (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Teaming up synthetic chemistry and histochemistry for activity screening in galectin-directed inhibitor design - René Roy; Yihong Cao; Herbert Kaltner; Naresh Kottari; Tze Chieh Shiao; Karima Belkhadem; Sabine André; Joachim C. Manning; Paul V. Murphy; Hans-Joachim Gabius (Histochemistry and Cell Biology, 2017)

Diversity and biogeography of larval and juvenile notothenioid fishes in McMurdo Sound, Antarctica - Katherine R. Murphy; Elizabeth A. Kalmanek; C.-H. Christina Cheng (Polar Biology, 2017)

Pilot Trial of Intravenous Lipid Emulsion Treatment for Severe Nifedipine-Induced Shock - Christine M. Murphy; Cliff Williams; Michael E. Quinn; Brian Nicholson; Thomas Shoe; Michael C. Beuhler; William P. Kerns (Journal of Medical Toxicology, 2016)

Hydrous Ferric Oxides in Sediment Catalyze Formation of Reactive Oxygen Species during Sulfide Oxidation - Sarah A. Murphy; Shengnan Meng; Benson M. Solomon; Dewamunnage M. C. Dias; Timothy J. Shaw; John L. Ferry (Frontiers in Marine Science, 2016)

Quantifying the Effects of Commercial Clam Aquaculture on C and N Cycling: an Integrated Ecosystem Approach - Anna E. Murphy; Kyle A. Emery; Iris C. Anderson; Michael L. Pace; Mark J. Brush; Jennie E. Rheuban (Estuaries and Coasts, 2016)

Colistin combination therapy improves microbiologic cure in critically ill patients with multi-drug resistant gram-negative pneumonia - N. L. Parchem; K. A. Bauer; C. H. Cook; J. E. Mangino; C. D. Jones; K. Porter; C. V. Murphy (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Erratum to: New approaches to quantifying bioerosion by endolithic sponge populations: applications to the coral reefs of Grand Cayman - G. N. Murphy; C. T. Perry; P. Chin; C. McCoy (Coral Reefs, 2016)

New approaches to quantifying bioerosion by endolithic sponge populations: applications to the coral reefs of Grand Cayman - G. N. Murphy; C. T. Perry; P. Chin; C. McCoy (Coral Reefs, 2016)

Erratum to: Identifying prey items from New Zealand fur seal (Arctocephalus forsteri) faeces using massive parallel sequencing - Arsalan Emami-Khoyi; David A. Hartley; Adrian M. Paterson; Laura J. Boren; Robert H. Cruickshank; James G. Ross; Elaine C. Murphy; Terry-Ann Else (Conservation Genetics Resources, 2016)

Identifying prey items from New Zealand fur seal (Arctocephalus forsteri) faeces using massive parallel sequencing - Arsalan Emami-Khoyi; David A. Hartley; Adrian M. Paterson; Laura J. Boren; Robert H. Cruickshank; James G. Ross; Elaine C. Murphy; Terry-Ann Else (Conservation Genetics Resources, 2016)

Microbial nitrogen processing in hard clam ( Mercenaria mercenaria ) aquaculture sediments: the relative importance of denitrification and dissimilatory nitrate reduction to ammonium (DNRA) - Anna E. Murphy; Iris C. Anderson; Ashley R. Smyth; Bongkeun Song; Mark W. Luckenbach (Limnology and Oceanography, 2016)

Controls over Ocean Mesopelagic Interior Carbon Storage (COMICS): Fieldwork, Synthesis, and Modeling Efforts - Richard J. Sanders; Stephanie A. Henson; Adrian P. Martin; Tom R. Anderson; Raffaele Bernardello; Peter Enderlein; Sophie Fielding; Sarah L. C. Giering; Manuela Hartmann; Morten Iversen; Samar Khatiwala; Phyllis Lam; et al. (Frontiers in Marine Science, 2016)

The Jebel Ohier deposit—a newly discovered porphyry copper–gold system in the Neoproterozoic Arabian–Nubian Shield, Red Sea Hills, NE Sudan - F. P. Bierlein; S. McKeag; N. Reynolds; C. J. Bargmann; W. Bullen; F. C. Murphy; H. Al-Athbah; C. Brauhart; W. Potma; S. Meffre; S. McKnight (Mineralium Deposita, 2016)

Accelerating research on Spotted Wing Drosophila management using genomic technologies - Katherine A. Murphy; Jessica D. West; Rosanna S. Kwok; Joanna C. Chiu (Journal of Pest Science, 2016)

Comparison of abdominal adiposity and overall obesity in relation to risk of small intestinal cancer in a European Prospective Cohort - Yunxia Lu; Amanda J. Cross; Neil Murphy; Heinz Freisling; Ruth C. Travis; Pietro Ferrari; Verena A. Katzke; Rudolf Kaaks; Åsa Olsson; Ingegerd Johansson; Frida Renström; Salvatore Panico; et al. (Cancer Causes & Control, 2016)

Homogenization and analysis of an expanded long‐term monthly rainfall network for the Island of Ireland (1850–2010) - S. Noone; C. Murphy; J. Coll; T. Matthews; D. Mullan; R. L. Wilby; S. Walsh (International Journal of Climatology, 2016)
Long‐term precipitation series are critical for understanding emerging changes to the hydrological cycle. To this end we construct a homogenized Island of Ireland Precipitation ( IIP ) network comprising 25 stations and a composite series covering the period 1850–2010, providing the second‐longest regional precipitation archive in the British‐Irish Isles. We expand the existing catalogue of long‐term precipitation records for the island by recovering archived data for an additional eight stations. Following bridging and updating of stations HOMogenisation softwarE in R ( HOMER ) homogenization software is used to detect breaks using pairwise and joint detection. A total of 25 breakpoints are detected across 14 stations, and the majority (20) are corroborated by metadata. Assessment of variability and change in homogenized and extended precipitation records reveal positive (winter) and negative (summer) trends. Trends in records covering the typical period of digitization (1941 onwards) are not always representative of longer records. Furthermore, trends in post‐homogenization series change magnitude and even direction at some stations. While cautionary flags are raised for some series, confidence in the derived network is high given attention paid to metadata, coherence of behaviour across the network and consistency of findings with other long‐term climatic series such as England and Wales precipitation. As far as we are aware, this work represents the first application of HOMER to a long‐term precipitation network and bodes well for use in other regions. It is expected that the homogenized IIP network will find wider utility in benchmarking and supporting climate services across the Island of Ireland, a sentinel location in the North Atlantic.

An evaluation of persistent meteorological drought using a homogeneous Island of Ireland precipitation network - R. L. Wilby; S. Noone; C. Murphy; T. Matthews; S. Harrigan; C. Broderick (International Journal of Climatology, 2016)
This paper investigates the spatial and temporal properties of persistent meteorological droughts using the homogeneous Island of Ireland Precipitation ( IIP ) network. Relative to a 1961–1990 baseline period it is shown that the longest observed run of below average precipitation since the 1850s lasted up to 5 years (10 half‐year seasons) at sites in southeast and east Ireland, or 3 years across the network as a whole. Dry spell and wet spell length distributions were represented by a first‐order Markov model which yields realistic runs of below average rainfall for individual sites and IIP series. This model shows that there is relatively high likelihood ( p = 0.125) of a 5‐year dry spell at Dublin, and that near unbroken dry runs of 10 years or more are conceivable. We suggest that the IIP network and attendant rainfall deficit modelling provide credible data for stress testing water supply and drought plans under extreme conditions.

Changes in Dopamine Signalling Do Not Underlie Aberrant Hippocampal Plasticity in a Mouse Model of Huntington’s Disease - Glenn M. Dallérac; Damian M. Cummings; Mark C. Hirst; Austen J. Milnerwood; Kerry P. S. J. Murphy (NeuroMolecular Medicine, 2016)

Shaping species with ephemeral boundaries: the distribution and genetic structure of desert tortoise ( Gopherus morafkai ) in the Sonoran Desert region - Taylor Edwards; Mercy Vaughn; Philip C. Rosen; Cristina Meléndez Torres; Alice E. Karl; Melanie Culver; Robert W. Murphy (Journal of Biogeography, 2016)
Aim We examine the role biogeographical features played in the evolution of Morafka's desert tortoise ( Gopherus morafkai ) and test the hypothesis that G. morafkai maintains genetically distinct lineages associated with different Sonoran Desert biomes. Increased knowledge of the past and present distribution of the Sonoran Desert region's biota provides insight into the forces that drive and maintain its biodiversity. Location Sonoran Desert biogeographical region; Sonora and Sinaloa, Mexico and Arizona, USA. Methods We examined wild tortoises from Mexico ( n = 155) and Arizona ( n = 78), spanning their known distribution. We used mt DNA sequences to reconstruct matrilineal relationships and 25 microsatellite ( STR ) loci for Bayesian analyses of gene flow. We performed clinal analyses on both mt DNA and STR loci to determine the position and amount of introgression where lineages co‐occur. We used GIS to assess the association of genetic structuring with ecological features. We used these data in a hypothesis‐driven approach to assess different models of how genetic diversity is maintained and distributed in G. morafkai . Results Gopherus morafkai was found to comprise genetically and geographically distinct ‘Sonoran’ and ‘Sinaloan’ lineages. Both lineages occurred in a relatively narrow zone of overlap in Sinaloan thornscrub, where it transitions into Sonoran desertscrub. Limited introgression occurred at the contact zone. The best‐fit model suggests that these lineages diverged in parapatry where the distribution of genotypes is environment‐dependent and introgression is inhibited by exogenous selection. Main conclusions The historically shifting ecotone between tropical deciduous forest and Sonoran desertscrub appears to be a boundary that fostered divergence between parapatric lineages of tortoises. The sharp genetic cline between the two lineages suggests that periods of isolation in temporary refugia due to Pleistocene climatic cycling influenced divergence. Despite incomplete reproductive isolation, the Sonoran and Sinaloan lineages of G. morafkai are on separate evolutionary trajectories.

A cyclone climatology of the British‐Irish Isles 1871–2012 - T. Matthews; C. Murphy; R. L. Wilby; S. Harrigan (International Journal of Climatology, 2016)
The British‐Irish Isles ( BI ) lie beneath the North Atlantic storm track year‐round and thus are impacted by the passage of extra‐tropical cyclones. Given recent extreme storminess and projections of enhanced winter cyclone activity for this region, there is much interest in assessing the extent to which the cyclone climate of the region may be changing. We address this by assessing a 142‐year (1871–2012) record of cyclone frequency, intensity and ‘storminess’ derived from the 20th Century Reanalysis V2 ( 20CR ) dataset. We also use this long‐term record to examine associations between cyclone activity and regional hydroclimate. Our results confirm the importance of cyclone frequency in driving seasonal precipitation totals which we find to be greatest during summer months. Cyclone frequency and storminess are characterized by pronounced interannual and multi‐decadal variability which are strongly coupled to atmospheric blocking in the Euro‐Atlantic region, but we detect no evidence of an increasing trend. We observe an upward trend in cyclone intensity for the BI region, which is strongest in winter and consistent with model projections, but promote caution interpreting this given the changing data quality in the 20CR over time. Nonetheless, we assert that long‐term reconstruction is helpful for contextualizing recent storminess and for identifying emerging changes in regional hydroclimate linked to cyclones.

Exercise protects against PCB-induced inflammation and associated cardiovascular risk factors - Margaret O. Murphy; Michael C. Petriello; Sung Gu Han; Manjula Sunkara; Andrew J. Morris; Karyn Esser; Bernhard Hennig (Environmental Science and Pollution Research, 2016)

Farm gate level nitrogen balance and use efficiency changes post implementation of the EU Nitrates Directive - Cathal Buckley; David P. Wall; Brian Moran; Stephen O’Neill; Paul N. C. Murphy (Nutrient Cycling in Agroecosystems, 2016)

Determinants of the t(14;18) translocation and their role in t(14;18)-positive follicular lymphoma - Rachel S. Kelly; Sandrine Roulland; Ester Morgado; Stéphanie Sungalee; Nathalie Jouve; Rosario Tumino; Vittorio Krogh; Salvatore Panico; Silvia Polidoro; Giovanna Masala; María-José Sánchez; Maria-Dolores Chirlaque; et al. (Cancer Causes & Control, 2015)

Evaluation of Cartilage Repair by Mesenchymal Stem Cells Seeded on a PEOT/PBT Scaffold in an Osteochondral Defect - V. Barron; K. Merghani; G. Shaw; C. M. Coleman; J. S. Hayes; S. Ansboro; A. Manian; G. O’Malley; E. Connolly; A. Nandakumar; C. A. van Blitterswijk; P. Habibovic; et al. (Annals of Biomedical Engineering, 2015)

Regional population differentiation in the morphologically diverse, elevationally widespread Nearctic skipper Polites sabuleti - Joshua P. Jahner; Matthew L. Forister; Chris C. Nice; James A. Fordyce; Joseph S. Wilson; Dennis D. Murphy; Zachary H. Marion; Arthur M. Shapiro (Journal of Biogeography, 2015)
Aim To evaluate three phylogeographical models associated with the presence of mountains (montane vicariance, sky island and parapatry) as drivers of intraspecific diversification in the sandhill skipper, Polites sabuleti (Lepidoptera: Hesperiidae), a morphologically variable species found in a variety of habitats from sea level to the alpine zone. Location Western North America. Methods The mitochondrial cytochrome c oxidase subunit II region was sequenced in 189 P. sabuleti individuals. Mitochondrial sequences were used in a spatial analysis of molecular variance ( SAMOVA ) to evaluate geographical population structure. AFLP markers were also generated for 347 individuals in order to estimate admixture proportions and examine population differentiation based on the nuclear genome. Results Twenty‐five mitochondrial haplotypes and 42 anonymous AFLP loci were found across 36 collection localities. Mitochondrial variation suggests a degree of regional population structure, although at least one of the inferred population groups extends over nearly the entire geographical range of the species. Analyses of nuclear data ( AFLP s) identified five genetic clusters, including one restricted to high elevations in the Sierra Nevada. Main conclusions The distribution of genetic variation within Polites sabuleti , a species with a broad elevational range, does not strictly support either mountain‐associated vicariance or ‘sky island’ isolation as the dominant process. Instead, we find complex population structure, including evidence for divergence between high‐ and low‐elevation populations in the Sierra Nevada mountains.

Engineered Fibrin Gels for Parallel Stimulation of Mesenchymal Stem Cell Proangiogenic and Osteogenic Potential - Kaitlin C. Murphy; Marissa L. Hughbanks; Bernard Y. K. Binder; Caroline B. Vissers; J. Kent Leach (Annals of Biomedical Engineering, 2015)

Evaluating the landscape of fear between apex predatory sharks and mobile sea turtles across a large dynamic seascape - Neil Hammerschlag; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark Dodd; Michael G. Frick; Matthew H. Godfrey; Brendan J. Godley; DuBose B. Griffin; Kyra Hartog; Sally R. Murphy; Thomas M. Murphy; et al. (Ecology, 2015)
The “landscape of fear” model has been proposed as a unifying concept in ecology, describing, in part, how animals behave and move about in their environment. The basic model predicts that as an animal's landscape changes from low to high risk of predation, prey species will alter their behavior to risk avoidance. However, studies investigating and evaluating the landscape of fear model across large spatial scales (tens to hundreds of thousands of square kilometers) in dynamic, open, aquatic systems involving apex predators and highly mobile prey are lacking. To address this knowledge gap, we investigated predator–prey relationships between tiger sharks ( Galeocerdo cuvier ) and loggerhead turtles ( Caretta caretta ) in the North Atlantic Ocean. This included the use of satellite tracking to examine shark and turtle distributions as well as their surfacing behaviors under varying levels of home range overlap. Our findings revealed patterns that deviated from our a priori predictions based on the landscape of fear model. Specifically, turtles did not alter their surfacing behaviors to risk avoidance when overlap in shark–turtle core home range was high. However, in areas of high overlap with turtles, sharks exhibited modified surfacing behaviors that may enhance predation opportunity. We suggest that turtles may be an important factor in determining shark distribution, whereas for turtles, other life history trade‐offs may play a larger role in defining their habitat use. We propose that these findings are a result of both biotic and physically driven factors that independently or synergistically affect predator–prey interactions in this system. These results have implications for evolutionary biology, community ecology, and wildlife conservation. Further, given the difficulty in studying highly migratory marine species, our approach and conclusions may be applied to the study of other predator–prey systems.

The OceanFlux Greenhouse Gases methodology for deriving a sea surface climatology of CO 2 fugacity in support of air–sea gas flux studies - L. M. Goddijn-Murphy; D. K. Woolf; P. E. Land; J. D. Shutler; C. Donlon (Ocean Science, 2015)
Climatologies, or long-term averages, of essential climate variables are useful for evaluating models and providing a baseline for studying anomalies. The Surface Ocean CO2 Atlas (SOCAT) has made millions of global underway sea surface measurements of CO2 publicly available, all in a uniform format and presented as fugacity, fCO2. As fCO2 is highly sensitive to temperature, the measurements are only valid for the instantaneous sea surface temperature (SST) that is measured concurrently with the in-water CO2 measurement. To create a climatology of fCO2 data suitable for calculating air–sea CO2 fluxes, it is therefore desirable to calculate fCO2 valid for a more consistent and averaged SST. This paper presents the OceanFlux Greenhouse Gases methodology for creating such a climatology. We recomputed SOCAT's fCO2 values for their respective measurement month and year using monthly composite SST data on a 1° × 1° grid from satellite Earth observation and then extrapolated the resulting fCO2 values to reference year 2010. The data were then spatially interpolated onto a 1° × 1° grid of the global oceans to produce 12 monthly fCO2 distributions for 2010, including the prediction errors of fCO2 produced by the spatial interpolation technique. The partial pressure of CO2 (pCO2) is also provided for those who prefer to use pCO2. The CO2 concentration difference between ocean and atmosphere is the thermodynamic driving force of the air–sea CO2 flux, and hence the presented fCO2 distributions can be used in air–sea gas flux calculations together with climatologies of other climate variables.

Developing the EU Farm Accountancy Data Network to derive indicators around the sustainable use of nitrogen and phosphorus at farm level - Cathal Buckley; David P. Wall; Brian Moran; Paul N. C. Murphy (Nutrient Cycling in Agroecosystems, 2015)

Improving estimates of tropical peatland area, carbon storage, and greenhouse gas fluxes - I. T. Lawson; T. J. Kelly; P. Aplin; A. Boom; G. Dargie; F. C. H. Draper; P. N. Z. B. P. Hassan; J. Hoyos-Santillan; J. Kaduk; D. Large; W. Murphy; S. E. Page; et al. (Wetlands Ecology and Management, 2015)

Investigation of the mechanisms mediating MDMA “Ecstasy”-induced increases in cerebro-cortical perfusion determined by btASL MRI - J Rouine; M. E. Kelly; C. Jennings-Murphy; P. Duffy; I. Gorman; S. Gormley; C. M. Kerskens; Andrew Harkin (Psychopharmacology, 2015)

Community structure and palaeoecological implications of calcareous encrusters on artificial substrates across a Mexican Caribbean reef - L. J. Hepburn; P. Blanchon; G. Murphy; L. Cousins; C. T. Perry (Coral Reefs, 2015)

Trace Element Inhibition of Phytase Activity - T. Santos; C. Connolly; R. Murphy (Biological Trace Element Research, 2015)

Sensitivity of Spatiotemporal Gait Parameters in Measuring Disease Severity in Friedreich Ataxia - Sarah C. Milne; Darren R. Hocking; Nellie Georgiou-Karistianis; Anna Murphy; Martin B. Delatycki; Louise A. Corben (The Cerebellum, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

An ecological comparison of Impatiens glandulifera Royle in the native and introduced range - Robert A. Tanner; Liang Jin; Richard Shaw; Sean T. Murphy; Alan C. Gange (Plant Ecology, 2014)

HPV genotypes and cervical intraepithelial neoplasia in a multiethnic cohort in the southeastern USA - Adriana C. Vidal; Jennifer S. Smith; Fidel Valea; Rex Bentley; Maggie Gradison; Kimberly S. H. Yarnall; Anne Ford; Francine Overcash; Kathy Grant; Susan K. Murphy; Cathrine Hoyo (Cancer Causes & Control, 2014)

Human mesenchymal stem cell spheroids in fibrin hydrogels exhibit improved cell survival and potential for bone healing - Kaitlin C. Murphy; Sophia Y. Fang; J. Kent Leach (Cell and Tissue Research, 2014)

Quantitative resistance in potato leaves to late blight associated with induced hydroxycinnamic acid amides - Kalenahalli N. Yogendra; Doddaraju Pushpa; Kareem A. Mosa; Ajjamada C. Kushalappa; Agnes Murphy; Teresa Mosquera (Functional & Integrative Genomics, 2014)

Comparison of a Stratified and a Single-Layer Laboratory Sand Filter to Treat Dairy Soiled Water from a Farm-Scale Woodchip Filter - Eimear M. Ruane; Paul N. C. Murphy; Padraig French; Mark G. Healy (Water, Air, & Soil Pollution, 2014)

Characterization of Air Contaminants Associated with Type of Swine Production Facilities - Darby Murphy; Shannon Engelman; Peter C. Raynor; Gurumurthy Ramachandran; Bruce H. Alexander (Journal of Agromedicine, 2014)

Identification of Late Blight Resistance-Related Metabolites and Genes in Potato through Nontargeted Metabolomics - Doddaraju Pushpa; Kalenahalli N. Yogendra; Raghavendra Gunnaiah; Ajjamada C. Kushalappa; Agnes Murphy (Plant Molecular Biology Reporter, 2014)

Prepubescent males are less susceptible to neuromuscular fatigue following resistance exercise - Justin R. Murphy; Duane C. Button; Anis Chaouachi; David G. Behm (European Journal of Applied Physiology, 2014)

Modulation of Mcl-1 sensitizes glioblastoma to TRAIL-induced apoptosis - Á. C. Murphy; B. Weyhenmeyer; J. Noonan; S. M. Kilbride; S. Schimansky; K. P. Loh; D. Kögel; A. G. Letai; J. H. M. Prehn; B. M. Murphy (Apoptosis, 2014)

Psychopharmacological prescriptions for people with autism spectrum disorder (ASD): a multinational study - Yingfen Hsia; Angel Y. S. Wong; Declan G. M. Murphy; Emily Simonoff; Jan K. Buitelaar; Ian C. K. Wong (Psychopharmacology, 2014)

Pharmacological treatments prescribed to people with autism spectrum disorder (ASD) in primary health care - Macey L. Murray; Yingfen Hsia; Karen Glaser; Emily Simonoff; Declan G. M. Murphy; Philip J. Asherson; Hanna Eklund; Ian C. K. Wong (Psychopharmacology, 2014)
Rationale Autism spectrum disorders (ASDs) affect 1 % of children, having significant impact on health and social outcomes. Psychotropic medication use by individuals with ASD in the USA increased over time, and polypharmacy occurred in >50 % of those prescribed. In the UK, no psychotropic drugs are approved in ASDs, and little is known about patterns of pharmacological treatment in the ASD population and associated co-morbidities. Methods We used The Health Improvement Network, a nationally representative primary care database, to assess the prevalence of ASD diagnoses, psychotropic drug prescribing and neuropsychiatric co-morbidities of 0–24 year olds between 1992 and 2008. Results ASD prevalence increased 65-fold from 0.01 % (1992) to 0.50 % (2008). Psychotropic drugs were prescribed to 29 % (1,619/5,651) of the ASD cohort; the most prescribed drugs were sleep medication (9.7 % of prescribed patients), psychostimulants (7.9 %) and antipsychotics (7.3 %). More patients were given psychostimulants and sleep medications over time from 1.5–6.3 % and 2.2–5.9 % respectively. Thirty-seven per cent of the cohort had ≥1 record of a neuropsychiatric co-morbidity, the most common being developmental difficulties and learning disabilities (12.6 %), behavioural, conduct and personality disorders (11.1 %) and attention deficit hyperactivity disorder (7.5 %). Conclusions British physicians are more conservative in prescribing practice than American colleagues. However, use of psychostimulants and antipsychotics is much higher in those with ASD than in the general population. Polypharmacy was seen in 34 % of prescribed patients in 2008. Additional studies examining use, efficacy, and long-term safety of antipsychotics and psychostimulants in autistic individuals are warranted.

Endothelial control of vasodilation: integration of myoendothelial microdomain signalling and modulation by epoxyeicosatrienoic acids - David C. Ellinsworth; Scott Earley; Timothy V. Murphy; Shaun L. Sandow (Pflügers Archiv - European Journal of Physiology, 2014)

Cancer risk and genotype–phenotype correlations in PTEN hamartoma tumor syndrome - Marry H. Nieuwenhuis; C. Marleen Kets; Maureen Murphy-Ryan; Helger G. Yntema; D. Gareth Evans; Chrystelle Colas; Pal Møller; Frederik J. Hes; Shirley V. Hodgson; Maran J. W. Olderode-Berends; Stefan Aretz; Karl Heinimann; et al. (Familial Cancer, 2014)

Temporal change in the herbaceous understory community of an old-growth forest: from seasons to decades - Stephen J. Murphy; Brian C. McCarthy (Plant Ecology, 2014)

Evaluation of seven plant species/cultivars for their suitability as banker plants for Orius insidiosus (Say) - M. O. Waite; C. D. Scott-Dupree; M. Brownbridge; R. Buitenhuis; G. Murphy (BioControl, 2014)

CXCR4 pathway associated with family history of melanoma - Wen-Qing Li; Jiali Han; Hans R. Widlund; Mick Correll; Yaoyu E. Wang; John Quackenbush; Martin C. Mihm; Alvaro Laga Canales; Shaowei Wu; Todd Golub; Yujin Hoshida; David J. Hunter; et al. (Cancer Causes & Control, 2014)

Foraging habitats and migration corridors utilized by a recovering subpopulation of adult female loggerhead sea turtles: implications for conservation - DuBose B. Griffin; Sally R. Murphy; Michael G. Frick; Annette C. Broderick; John W. Coker; Michael S. Coyne; Mark G. Dodd; Matthew H. Godfrey; Brendan J. Godley; Lucy A. Hawkes; Thomas M. Murphy; Kristina L. Williams; et al. (Marine Biology, 2013)

Complex evolutionary history of the pallid dotted‐blue butterfly (Lycaenidae: Euphilotes pallescens ) in the Great Basin of western North America - Joseph S. Wilson; Michelle Sneck; Dennis D. Murphy; Chris C. Nice; James A. Fordyce; Matthew L. Forister (Journal of Biogeography, 2013)
Aim The aim of this study was to investigate patterns of genetic isolation associated with populations in discrete habitat patches in a North American cold desert through analysis of the pallid dotted‐blue butterfly, Euphilotes pallescens . This small butterfly is largely restricted to low‐elevation habitats across the Great Basin. The apparent geographical isolation and reported morphological variation among E. pallescens populations makes this species an ideal candidate with which to investigate patterns of genetic isolation and diversification in this arid region. Location Great Basin, western North America. Methods We used sequence data from nuclear and mitochondrial genes to investigate genetic diversity among E. pallescens populations, and among E. pallescens and a number of closely related Euphilotes species, using Bayesian phylogenetic analyses, as well as population genetic analyses. In conjunction with genetic variation, morphological variation was examined in the context of geographical and subspecific differentiation. Results Our genetic and morphological analyses suggest a moderate amount of isolation among populations, consistent with the hypothesis of restricted gene flow among isolated dune habitats, and possibly associated with isolation in distinct Pleistocene refugia. The patterns of diversification within E. pallescens and among closely related species are complicated by discordance among phylogenetic reconstructions based on nuclear and mitochondrial genes. Discordance among gene genealogies suggests a complex evolutionary history, perhaps involving alternating periods of reticulation and divergence in isolation. Main conclusions Although E. pallescens may be a vagile species, we find that persistence on isolated dunes in the Great Basin is associated with appreciable genetic and morphological differentiation among populations. However, genetic, morphological and taxonomic axes of variation are only partially in agreement. More generally, the discordance we find among genetic regions is consistent with the ascendant paradigm in phylogenetic reconstruction: gene genealogies often do not perfectly match species trees. Thus we present Euphilotes as a model for future biogeographical and phylogenetic reconstructions employing larger data sets of independent sequence markers.

Molecular cloning of the trypsin inhibitor from the skin secretion of the Madagascan Tomato Frog, Dyscophus guineti (Microhylidae), and insights into its potential defensive role - Enrico König; Christina Wesse; Anna C. Murphy; Mei Zhou; Lei Wang; Tianbao Chen; Chris Shaw; Olaf R. P. Bininda-Emonds (Organisms Diversity & Evolution, 2013)

ICAM-2 and lipid rafts disappear from the basal plasma membrane of uterine epithelial cells during early pregnancy in rats - L. Lecce; L. Lindsay; Y. Kaneko; C. R. Murphy (Cell and Tissue Research, 2013)

Implications of CMIP3 model biases and uncertainties for climate projections in the western tropical Pacific - Jaclyn N. Brown; Alex Sen Gupta; Josephine R. Brown; Les C. Muir; James S. Risbey; Penny Whetton; Xuebin Zhang; Alexandre Ganachaud; Brad Murphy; Susan E. Wijffels (Climatic Change, 2013)

Evaluation of real-time flash flood forecasts for Haiti during the passage of Hurricane Tomas, November 4–6, 2010 - E. Shamir; K. P. Georgakakos; C. Spencer; T. M. Modrick; M. J. Murphy; R. Jubach (Natural Hazards, 2013)

Florivores prefer white versus pink petal color morphs in wild radish, Raphanus sativus - Andrew C. McCall; Stephen J. Murphy; Colin Venner; Monique Brown (Oecologia, 2013)

Virus species polemics: 14 senior virologists oppose a proposed change to the ICTV definition of virus species - Marc H. V. Van Regenmortel; Hans-Wolfgang Ackermann; Charles H. Calisher; Ralf G. Dietzgen; Marian C. Horzinek; Gunther M. Keil; Brian W. J. Mahy; Giovanni P. Martelli; Frederick A. Murphy; Craig Pringle; Bert K. Rima; Tim Skern; et al. (Archives of Virology, 2013)

“Bath Salts” and “Plant Food” Products: the Experience of One Regional US Poison Center - Christine M. Murphy; Anna R. Dulaney; Michael C. Beuhler; Sherri Kacinko (Journal of Medical Toxicology, 2013)

A Strategy for Prioritizing Threats and Recovery Actions for At-Risk Species - Catherine R. Darst; Philip J. Murphy; Nathan W. Strout; Steven P. Campbell; Kimberleigh J. Field; Linda Allison; Roy C. Averill-Murray (Environmental Management, 2013)

The status of Eurostus dussumierii and Hypsirhina chinensis (Reptilia, Squamata, Serpentes): with comments on the origin of salt tolerance in homalopsid snakes - A. Biju Kumar; Kate L. Sanders; Sanil George; John C. Murphy (Systematics and Biodiversity, 2012)

Evidence of yellow perch, largemouth bass and pumpkinseed metapopulations in coastal embayments of Lake Ontario - Shidan Murphy; Nick C. Collins; Susan E. Doka; Brian J. Fryer (Environmental Biology of Fishes, 2012)

Erratum to: Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Progression of cutaneous melanoma: implications for treatment - Stanley P. L. Leong; Martin C. Mihm; George F. Murphy; Dave S. B. Hoon; Mohammed Kashani-Sabet; Sanjiv S. Agarwala; Jonathan S. Zager; Axel Hauschild; Vernon K. Sondak; Valerie Guild; John M. Kirkwood (Clinical & Experimental Metastasis, 2012)

Estimating rates of biologically driven coral reef framework production and erosion: a new census-based carbonate budget methodology and applications to the reefs of Bonaire - C. T. Perry; E. N. Edinger; P. S. Kench; G. N. Murphy; S. G. Smithers; R. S. Steneck; P. J. Mumby (Coral Reefs, 2012)

A Common View of the Opportunities, Challenges, and Research Actions for Pongamia in Australia - Helen T. Murphy; Deborah A. O’Connell; Gary Seaton; R. John Raison; Luis C. Rodriguez; Andrew L. Braid; Darren J. Kriticos; Tom Jovanovic; Amir Abadi; Michael Betar; Heather Brodie; Malcolm Lamont; et al. (BioEnergy Research, 2012)

Latitudinal variation in blue tit and great tit nest characteristics indicates environmental adjustment - Mark C. Mainwaring; Ian R. Hartley; Stuart Bearhop; Kaat Brulez; Christopher R. du Feu; Gerald Murphy; Kate E. Plummer; Simone L. Webber; S. James Reynolds; D. Charles Deeming (Journal of Biogeography, 2012)
Aim The laying of eggs and the building of a nest structure to accommodate them are two of the defining characteristics of members of the class Aves. Nest structures vary considerably across avian taxa and for many species the structure of the completed nest can have important consequences both for parents and their offspring. While nest characteristics are expected to vary adaptively in response to environmental conditions, large‐scale spatial variation in nest characteristics has been largely overlooked. Here, we examine the effects of latitudinal variation in spring temperatures on nest characteristics, including insulatory properties, and reproductive success of blue tits, Cyanistes caeruleus , and great tits, Parus major . Location Great Britain. Methods Nests and reproductive data were collected from seven study sites, spread over 5° of latitude. The nest insulatory properties were then determined before the nests were separated into nest base material and cup lining material. Results As spring temperatures increased with decreasing latitude, the mass of the nest base material did not vary in either species, while the mass of the cup lining material and nest insulatory properties decreased in both species. This suggests that in response to increasing temperatures the breeding female reduces the mass of the cup lining material, thereby maintaining an appropriate microclimate for incubating and brooding. The mean first egg date of both species advanced with decreasing latitude and increasing spring temperatures, although clutch size and brood size at hatching and fledging did not vary. Main conclusions This is the first study to demonstrate that the nest‐construction behaviour of birds varies in response to large‐scale spatial variation in ambient temperatures. Therefore, nest composition reliably indicates environmental conditions and we suggest that studies of nest structure may be sentinels for the early signs of rapid climate change.

Effects of Lime and Phosphorus Application on Phosphorus Runoff Risk - Paul N. C. Murphy; J. T. Sims (Water, Air, & Soil Pollution, 2012)

Isolating early cortical generators of visual-evoked activity: a systems identification approach - Jeremy W. Murphy; Simon P. Kelly; John J. Foxe; Edmund C. Lalor (Experimental Brain Research, 2012)

Acute morbidity and mortality in invertebrates and fish following exposure to potassium‐deficient saltwater - C A Hadfield; L A Clayton; D K Cohrs; D S Murphy (Journal of Fish Diseases, 2012)

Advancing the use of minirhizotrons in wetlands - C. M. Iversen; M. T. Murphy; M. F. Allen; J. Childs; D. M. Eissenstat; E. A. Lilleskov; T. M. Sarjala; V. L. Sloan; P. F. Sullivan (Plant and Soil, 2012)

Death Following Recreational Use of Designer Drug “Bath Salts” Containing 3,4-Methylenedioxypyrovalerone (MDPV) - Brittany L. Murray; Christine M. Murphy; Michael C. Beuhler (Journal of Medical Toxicology, 2012)

Optimization of a Dual Mechanism Gastrofloatable and Gastroadhesive Delivery System for Narrow Absorption Window Drugs - Caragh Murphy; Viness Pillay; Yahya E. Choonara; Lisa C. du Toit; Valence M. K. Ndesendo; Nthato Chirwa; Pradeep Kumar (AAPS PharmSciTech, 2012)

The biochemical, physiological and psychological consequences of a “1,000 miles in 1,000 hours” walking challenge - M. H. Murphy; G. Breslin; T. Trinick; C. McClean; W. Moore; E. Duly; G. W. Davison (European Journal of Applied Physiology, 2012)

Impulsive behaviour induced by both NMDA receptor antagonism and GABAA receptor activation in rat ventromedial prefrontal cortex - Emily R. Murphy; Anushka B. P. Fernando; Gonzalo P. Urcelay; Emma S. J. Robinson; Adam C. Mar; David E. H. Theobald; Jeffrey W. Dalley; Trevor W. Robbins (Psychopharmacology, 2012)

Preface: Multiscale analysis of the Mt Isa–McArthur region, Northern Australia - F. C. Murphy (Australian Journal of Earth Sciences, 2011)

Mineral system analysis of the Mt Isa–McArthur River region, Northern Australia - F. C. Murphy; L. J. Hutton; J. L. Walshe; J. S. Cleverley; M. A. Kendrick; J. Mclellan; M. J. Rubenach; N.H. S. Oliver; K. Gessner; F. P. Bierlein; B. Jupp; L. Aillères; et al. (Australian Journal of Earth Sciences, 2011)

Anaphylaxis with Latrodectus Antivenin Resulting in Cardiac Arrest - Christine M. Murphy; Jeannie J. Hong; Michael C. Beuhler (Journal of Medical Toxicology, 2011)

Expansion of tubenose gobies Proterorhinus semilunaris into western Lake Erie and potential effects on native species - P. M. Kocovsky; J. A. Tallman; D. J. Jude; D. M. Murphy; J. E. Brown; C. A. Stepien (Biological Invasions, 2011)

Vascular endothelium-specific overexpression of human catalase in cloned pigs - J. J. Whyte; M. Samuel; E. Mahan; J. Padilla; G. H. Simmons; A. A. Arce-Esquivel; S. B. Bender; K. M. Whitworth; Y. H. Hao; C. N. Murphy; E. M. Walters; R. S. Prather; et al. (Transgenic Research, 2011)

Height at diagnosis and birth-weight as risk factors for osteosarcoma - Lisa Mirabello; Ruth Pfeiffer; Gwen Murphy; Najat C. Daw; Ana Patiño-Garcia; Rebecca J. Troisi; Robert N. Hoover; Chester Douglass; Joachim Schüz; Alan W. Craft; Sharon A. Savage (Cancer Causes & Control, 2011)

Entorhinal cortex volume is associated with episodic memory related brain activation in normal aging and amnesic mild cognitive impairment - Mehul A. Trivedi; Travis R. Stoub; Christopher M. Murphy; Sarah George; Leyla deToledo-Morrell; Raj C. Shah; Susan Whitfield-Gabrieli; John D. E. Gabrieli; Glenn T. Stebbins (Brain Imaging and Behavior, 2011)

Evaluation of winter wheat breeding lines for traits related to nitrogen use under organic management - J. C. Dawson; K. M. Murphy; D. R. Huggins; S. S. Jones (Organic Agriculture, 2011)

The proposed release of the yellow fever mosquito, Aedes aegypti containing a naturally occurring strain of Wolbachia pipientis, a question of regulatory responsibility - Paul J. De Barro; Brendan Murphy; Cassie C. Jansen; Justine Murray (Journal of Consumer Protection and Food Safety, 2011)

Alpha-Synuclein Loss in Spinal Muscular Atrophy - Gyula Acsadi; Xingli Li; Kelley J. Murphy; Kathryn J. Swoboda; Graham C. Parker (Journal of Molecular Neuroscience, 2011)

Culturable Rhodobacter and Shewanella species are abundant in estuarine turbidity maxima of the Columbia River - S. L. Bräuer; C. Adams; K. Kranzler; D. Murphy; M. Xu; P. Zuber; H. M. Simon; A. M. Baptista; B. M. Tebo (Environmental Microbiology, 2011)
Summary Measurements of dissolved, ascorbate‐reducible and total Mn by ICP‐OES revealed significantly higher concentrations during estuarine turbidity maxima (ETM) events, compared with non‐events in the Columbia River. Most probable number (MPN) counts of Mn‐oxidizing or Mn‐reducing heterotrophs were not statistically different from that of other heterotrophs (10 3 –10 4 cells ml −1 ) when grown in defined media, but counts of Mn oxidizers were significantly lower in nutrient‐rich medium (13 cells ml −1 ). MPN counts of Mn oxidizers were also significantly lower on Mn(III)‐pyrophosphate and glycerol (21 cells ml −1 ). Large numbers of Rhodobacter spp. were cultured from dilutions of 10 −2 to 10 −5 , and many of these were capable of Mn(III) oxidation. Up to c . 30% of the colonies tested LBB positive, and all 77 of the successfully sequenced LBB positive colonies (of varying morphology) yielded sequences related to Rhodobacter spp. qPCR indicated that a cluster of Rhodobacter isolates and closely related strains (95–99% identity) represented approximately 1–3% of the total Bacteria , consistent with clone library results. Copy numbers of SSU rRNA genes for either Rhodobacter spp. or Bacteria were four to eightfold greater during ETM events compared with non‐events. Strains of a Shewanella sp. were retrieved from the highest dilutions (10 −5 ) of Mn reducers, and were also capable of Mn oxidation. The SSU rRNA gene sequences from these strains shared a high identity score (98%) with sequences obtained in clone libraries. Our results support previous findings that ETMs are zones with high microbial activity. Results indicated that Shewanella and Rhodobacter species were present in environmentally relevant concentrations, and further demonstrated that a large proportion of culturable bacteria, including Shewanella and Rhodobacter spp., were capable of Mn cycling in vitro .

Reproductive correlates of spring arrival date in the Eastern Kingbird Tyrannus tyrannus - Nathan W. Cooper; Michael T. Murphy; Lucas J. Redmond; Amy C. Dolan (Journal of Ornithology, 2011)

Using generalized autoregressive error models to understand fire–vegetation–soil feedbacks in a mulga–spinifex landscape mosaic - Brett P. Murphy; Paolo Paron; Lynda D. Prior; Guy S. Boggs; Donald C. Franklin; David M. J. S. Bowman (Journal of Biogeography, 2010)
Aim To develop a new modelling approach for spatially autocorrelated non‐normal data, and apply it to a case study of the role that fire–vegetation–soil feedbacks play in maintaining boundaries between fire‐sensitive and fire‐promoted plant communities. Location A mulga ( Acacia aneura ) shrubland–spinifex ( Triodia spp.) grassland mosaic, central Australia. Methods Autoregressive error models were extended to non‐normal data by incorporating neighbourhood values of the response and predictor variables into generalized nonlinear models. These models were used to examine the environmental correlates of three response variables: mulga cover; fire frequency in areas free of mulga; and the presence of mulga banding. Mulga cover and mulga banding were assessed visually by overlaying 4477 × 1 km 2 grid cells on both Landsat 7 ETM+ and very high resolution imagery. Fire frequency was estimated from an existing fire history for central Australia, based on remotely sensed fire scars. Results The autoregressive error models explained 27%, 47% and 57% of the null deviance of mulga cover, fire frequency and mulga banding, respectively, with 12%, 15% and 24% of the null deviance being explained by environmental variables alone. These models accounted for virtually all residual spatial autocorrelation. While there was a clear negative relationship between mulga cover and fire frequency, there was little evidence that mulga was being restricted to parts of the landscape with inherently low fire frequencies. Mulga was most abundant at very low slope angles and on red earths, both of which are likely to reflect high site productivity, while fire frequency was not clearly affected by slope angle and was also relatively high on red earths. Main conclusions The modelling approach we have developed provides a much needed way of analysing spatially autocorrelated non‐normal data and can be easily incorporated into an information‐theoretic modelling framework. Using this approach, we provide evidence that mulga and spinifex have a highly antagonistic relationship. In more productive parts of the landscape, mulga suppresses spinifex and fire, while in less productive parts of the landscape, fire and spinifex suppress mulga, leading to the remarkable abruptness of mulga–spinifex boundaries that are maintained via fire–vegetation–soil feedbacks.

Lime and Gypsum as Source Measures to Decrease Phosphorus Loss from Soils to Water - Paul N. C. Murphy; R. J. Stevens (Water, Air, & Soil Pollution, 2010)

Maternal influences on population dynamics: evidence from an exploited freshwater fish - Paul A. Venturelli; Cheryl A. Murphy; Brian J. Shuter; Thomas A. Johnston; Peter J. van Coeverden de Groot; Peter T. Boag; John M. Casselman; Robert Montgomerie; Murray D. Wiegand; William C. Leggett (Ecology, 2010)
We used a field experiment, population modeling, and an analysis of 30 years of data from walleye ( Sander vitreus ; a freshwater fish) in Lake Erie to show that maternal influences on offspring survival can affect population dynamics. We first demonstrate experimentally that the survival of juvenile walleye increases with egg size (and, to a lesser degree, female energy reserves). Because egg size in this species tends to increase with maternal age, we then model these maternal influences on offspring survival as a function of maternal age to show that adult age structure can affect the maximum rate at which a population can produce new adults. Consistent with this hypothesis, we present empirical evidence that the maximum reproductive rate of an exploited population of walleye was approximately twice as high when older females were abundant as compared to when they were relatively scarce. Taken together, these results indicate that age‐ or size‐based maternal influences on offspring survival can be an important mechanism driving population dynamics and that exploited populations could benefit from management strategies that protect, rather than target, reproductively valuable individuals.

CD43 is relocated from the basal to the apical plasma membrane of rat uterine epithelial cells by progesterone - L. Lecce; Y. Kaneko; C. R. Murphy (Histochemistry and Cell Biology, 2010)

Successive bouts of cycling stimulates genes associated with mitochondrial biogenesis - Charles L. Dumke; J. Mark Davis; E. Angela Murphy; David C. Nieman; Martin D. Carmichael; John C. Quindry; N. Travis Triplett; Alan C. Utter; Sarah J. Gross Gowin; Dru A. Henson; Steven R. McAnulty; Lisa S. McAnulty (European Journal of Applied Physiology, 2009)

Maternal characteristics and the production and recruitment of sons in the eastern kingbird (Tyrannus tyrannus) - Amy C. Dolan; Michael T. Murphy; Lucas J. Redmond; Debbie Duffield (Behavioral Ecology and Sociobiology, 2009)

Signatures of vicariance, postglacial dispersal and spawning philopatry: population genetics of the walleye Sander vitreus - C. A. STEPIEN; D. J. MURPHY; R. N. LOHNER; O. J. SEPULVEDA‐VILLET; A. E. HAPONSKI (Molecular Ecology, 2009)
Population genetic relationships reveal the signatures of current processes such as reproductive behaviour and migration, as well as historic events including vicariance and climate change. We analyse population structure of native walleye Sander vitreus across North America, encompassing 10 nuclear DNA microsatellite loci, 26 spawning sites and 921 samples from watersheds across the Great Lakes, Lake Winnipeg, upper Mississippi River, Ohio River and Mobile Bay of the Gulf Coast. Geographical patterning is assessed using phylogenetic trees, pairwise F ST analogues, hierarchical partitioning, Mantel regression, Bayesian assignment and Monmonier geographical networks. Results reveal congruent divergences among population groups, corresponding to historic isolation in glacial refugia, dispersal patterns and basin divisions. Broad‐scale relationships show genetic isolation with geographical distance, but reproductive groups within basins do not – with some having pronounced differences. Greatest divergence distinguishes outlying Gulf Coastal and northwest populations, the latter tracing to dispersal from the Missourian refugium to former glacial Lake Agassiz, and basin isolation ∼7000 ya. Genetic barriers in the Great Lakes separate groups in Lakes Superior, Huron’s Georgian Bay, Erie and Ontario, reflecting contributions from Mississippian and Atlantic refugia, and changes in connectivity patterns. Walleye genetic patterns thus reflect vicariance among watersheds and glacial refugia, followed by re‐colonization pathways and changing drainage connections that established modern‐day northern populations, whose separations are maintained through spawning site fidelity. Conservation management practices should preserve genetic identity and unique characters among these divergent walleye populations.

Investigation of long-term field experiments on response of breeding lines to common scab in a potato breeding program - G. C. C. Tai; A. M. Murphy; Xingyao Xiong (Euphytica, 2009)

Birth of a biome: insights into the assembly and maintenance of the Australian arid zone biota - M. BYRNE; D. K. YEATES; L. JOSEPH; M. KEARNEY; J. BOWLER; M. A. J. WILLIAMS; S. COOPER; S. C. DONNELLAN; J. S. KEOGH; R. LEYS; J. MELVILLE; D. J. MURPHY; et al. (Molecular Ecology, 2008)

Direct effects of diazepam on emotional processing in healthy volunteers - S. E. Murphy; C. Downham; P. J. Cowen; C. J. Harmer (Psychopharmacology, 2008)

Predicting dispersal and recruitment of Miconia calvescens (Melastomataceae) in Australian tropical rainforests - Helen T. Murphy; B. D. Hardesty; C. S. Fletcher; D. J. Metcalfe; D. A. Westcott; S. J. Brooks (Biological Invasions, 2008)

Magnetotelluric soundings and crustal architecture at Century mine, northern Australia - F. C. Murphy; J. Cull; T. J. Lee; S. K. Lee; Y. Song (Australian Journal of Earth Sciences, 2008)

Evaluation of genetic variation of attack and resistance in lodgepole pine in the early stages of a mountain pine beetle outbreak - Alvin D. Yanchuk; John C. Murphy; Kimberly F. Wallin (Tree Genetics & Genomes, 2008)

Decentralized selection and participatory approaches in plant breeding for low-input systems - Julie C. Dawson; Kevin M. Murphy; Stephen S. Jones (Euphytica, 2008)

Microbial response to the addition of glucose in low-fertility soils - F. C. Hoyle; D. V. Murphy; P. C. Brookes (Biology and Fertility of Soils, 2008)

Mapping wetlands: A comparison of two different approaches for New Brunswick, Canada - Paul N. C. Murphy; Jae Ogilvie; Kevin Connor; Paul A. Arp (Wetlands, 2007)

Estrogen receptors inhibit Smad3 transcriptional activity through Ap-1 transcription factors - Tracy Cherlet; Leigh C. Murphy (Molecular and Cellular Biochemistry, 2007)

Late Quaternary paleoenvironments of an ephemeral wetland in North Dakota, USA: relative interactions of ground-water hydrology and climate change - Catherine H. Yansa; Walter E. Dean; Edward C. Murphy (Journal of Paleolimnology, 2007)

Dietary fiber and colorectal cancer risk: the multiethnic cohort study - Abraham M. Y. Nomura; Jean H. Hankin; Brian E. Henderson; Lynne R. Wilkens; Suzanne P. Murphy; Malcolm C. Pike; Loic Le Marchand; Daniel O. Stram; Kristine R. Monroe; Laurence N. Kolonel (Cancer Causes & Control, 2007)

The phylogeography of palm cockatoos, Probosciger aterrimus , in the dynamic Australo‐Papuan region - Stephen A. Murphy; Michael C. Double; Sarah M. Legge (Journal of Biogeography, 2007)
Aims We aimed to investigate the effects of historical land–sea boundary and vegetation dynamics in the Australo‐Papuan region on the genetic structure of palm cockatoo populations. In doing so, we also sought to clarify the intraspecific taxonomic status of palm cockatoos, and to examine the potential conservation implications of our results. Location New Guinea and northern Australia. Methods We examined mtDNA (domain III, control region) genetic structure in 71 palm cockatoos from 17 locations across their Australo‐Papuan range. Results Twenty polymorphic sites over 242‐base pairs defined 12 haplotypes that were arranged in a 95% confidence parsimony network of six one‐step clades. Half of these were linked in one clade that included birds from eastern New Guinea–Australia, and the other half included birds from western New Guinea. Nested clade analyses revealed strong and significant genetic structure between these two clades. The average nucleotide divergence between eastern and western birds is c. 3.3%. Within the western clade there was a non‐random distribution of haplotypes according to sampling location alone, but the locations did not cluster significantly, probably due to low sample sizes. A non‐random distribution of haplotypes emerged within one of the one‐step clades from the east of the range (once rare haplotypes were removed), although the historic mechanism that may have created this pattern is unclear. The underlying low nucleotide divergence (0.39%) among haplotypes within the eastern clade suggests relatively recent common ancestry. Main conclusions Our results suggest genetic isolation of the eastern and western clades sometime during the Pleistocene. The continual reappearance of land bridges associated with Pleistocene glacio‐eustatic cycles within the eastern part of the range provides an explanation for our results. We suggest that the occurrence of two deep marine troughs maintained a narrow mountainous barrier between eastern and western birds throughout much of the Pleistocene at a time when extensive land bridges formed elsewhere in the species’ range, and that this has maintained their genetic distinctiveness. Our results provide little support for the current accepted subspecies; the western clade is roughly congruent with Probosciger aterrimus goliath (with caveats), but the otherwise unstructured small genetic distances cast considerable doubt on the remaining subspecies. The eastern and western lineages are endemic to each area and should therefore be considered for independent conservation status and management.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The impact of time and field conditions on brown bear (Ursus arctos) faecal DNA amplification - Melanie A. Murphy; Katherine C. Kendall; Andrew Robinson; Lisette P. Waits (Conservation Genetics, 2007)

Temporal dynamics of pathogenesis-related metabolites and their plausible pathways of induction in potato leaves following inoculation with Phytophthora infestans - Y. Abu-Nada; A. C. Kushalappa; W. D. Marshall; K. Al-Mughrabi; A. Murphy (European Journal of Plant Pathology, 2007)

Occurrence of Cryptosporidium parvum and Bacterial Pathogens in Faecal Material in the Red Fox (Vulpes vulpes) Population - Y. Nagano; M. B. Finn; C. J. Lowery; T. Murphy; J. Moriarty; E. Power; D. Toolan; A. O’Loughlin; M. Watabe; K. A. McCorry; E. Crothers; J. S. G. Dooley; et al. (Veterinary Research Communications, 2007)

Chromosomal location of Pm35, a novel Aegilops tauschii derived powdery mildew resistance gene introgressed into common wheat (Triticum aestivum L.) - L. M. Miranda; J. P. Murphy; D. Marshall; C. Cowger; S. Leath (Theoretical and Applied Genetics, 2007)

Predicting individual breeding values and making forward selections from open-pollinated progeny test trials for seed orchard establishment of interior Lodgepole Pine (Pinus contorta ssp. latifolia) in British Columbia - C. -Y. Xie; M. R. Carlson; J. C. Murphy (New Forests, 2007)

Immunological evaluation of urinary trypsin inhibitors in blood and urine: Role of N- & O-linked glycoproteins - Michael J. Pugia; Saeed A. Jortani; Manju Basu; Ronald Sommer; Hai-Hang Kuo; Solomon Murphy; Doug Williamson; James Vranish; Patrick J. Boyle; Danny Budzinski; Roland Valdes; Subhash C. Basu (Glycoconjugate Journal, 2007)

Production of endothelial nitric oxide synthase (eNOS) over-expressing piglets - Y. H. Hao; H. Y. Yong; C. N. Murphy; D. Wax; M. Samuel; A. Rieke; L. Lai; Z. Liu; D. C. Durtschi; V. R. Welbern; E. M. Price; R. M. McAllister; et al. (Transgenic Research, 2006)

Experimental infection of big brown bats (Eptesicus fuscus) with Eurasian bat lyssaviruses Aravan, Khujand, and Irkut virus - G. J. Hughes; I. V. Kuzmin; A. Schmitz; J. Blanton; J. Manangan; S. Murphy; C. E. Rupprecht (Archives of Virology, 2006)

Co-expression of interleukin-6 and human growth hormone in apparently normal prostate biopsies that ultimately progress to prostate cancer using low pH, high temperature antigen retrieval - M. D. Slater; C. R. Murphy (Journal of Molecular Histology, 2006)

TAXONOMIC STATUS AND GEOGRAPHICAL CRANIAL VARIATION OF COMMON DOLPHINS ( DELPHINUS ) IN THE EASTERN NORTH ATLANTIC - Sinéad Murphy; Jerry S. Herman; Graham J. Pierce; Emer Rogan; Andrew C. Kitchener (Marine Mammal Science, 2006)
The common dolphin has a widespread distribution and is relatively abundant in the temperate to subtropical waters of the eastern North Atlantic. However, it is not known whether different species, subspecies, or populations occur in this region. We examined 393 common dolphin skulls obtained from both stranded and bycaught individuals collected between 1901 and 2005. The series included skulls of 152 females and 199 males, from animals ranging in body length from 93 to 230 cm and 105 to 244 cm, respectively. The ranges of total body length, skull size, RL/ZGW ratio and maximum upper alveolar (tooth) count of common dolphins in the eastern North Atlantic overlapped with those of both short‐ ( D. delphis ) and long‐beaked ( D. capensis ) species found off the Californian coast. However, in the absence of additional data, the common dolphin in the eastern North Atlantic is regarded here as a large form of Delphinus delphis . Sexual dimorphism and possible sex‐linked characters were identified within the sample. Results of the current study indicate some population differentiation within the eastern North Atlantic, with common dolphins off Portugal showing segregation in morphometric characteristics from common dolphins in other areas.

Distribution of orogenic gold deposits in relation to fault zones and gravity gradients: targeting tools applied to the Eastern Goldfields, Yilgarn Craton, Western Australia - Frank P. Bierlein; Finbarr C. Murphy; Roberto F. Weinberg; Terry Lees (Mineralium Deposita, 2006)

Variability and inheritance of flowering time and duration in Actinidia chinensis (kiwifruit) - C. H. Cheng; A. G. Seal; S. J. Murphy; R. G. Lowe (Euphytica, 2006)

Lack of effects of guanfacine on executive and memory functions in healthy male volunteers - Ulrich Müller; Luke Clark; Minh L. Lam; Rebecca M. Moore; C. Louise Murphy; Nicola K. Richmond; Ranbir S. Sandhu; Ingrid A. Wilkins; David K. Menon; Barbara J. Sahakian; Trevor W. Robbins (Psychopharmacology, 2005)

Microsatellite analysis indicates an absence of population structure among Hippoglossus hippoglossus in the north‐west Atlantic - D. P. Reid; S. Pongsomboon; T. Jackson; C. McGowan; C. Murphy; D. Martin‐Robichaud; M. Reith (Journal of Fish Biology, 2005)
To explore the population structure of Atlantic halibut Hippoglossus hippoglossus , 160 fish from four locations in the north‐west Atlantic (Bay of Fundy, Scotian Shelf, Gulf of St Lawrence and Iceland) were examined for evidence of population structure using 18 microsatellite markers. Pair‐wise F ST and a model‐based cluster analysis revealed no significant differentiation between samples, although uncertainties surrounding Atlantic halibut reproductive behaviour made it difficult to ascertain that only a single breeding population had been sampled at each location

Impact of the European Antimicrobial Resistance Surveillance System on the development of a national programme to monitor resistance in Staphylococcus aureus and Streptococcus pneumoniae in Ireland, 1999–2003 - O. M. Murphy; S. Murchan; D. Whyte; H. Humphreys; A. Rossney; P. Clarke; R. Cunney; C. Keane; L. E. Fenelon; D. O’Flanagan (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

A randomized trial to promote pharmacotherapy use and smoking cessation in a Medicaid population (United States) - Jill M. Murphy; Martin C. Mahoney; K. Michael Cummings; Andrew J. Hyland; Silvana Lawvere (Cancer Causes & Control, 2005)

Cytokine gene polymorphisms in ischaemic heart disease: investigation using family-based tests of association - Paul G. McGlinchey; Mark S. Spence; Chris C. Patterson; Adrian R. Allen; Gillian Murphy; David A. Savage; A. Peter Maxwell; Pascal P. McKeown (Journal of Molecular Medicine, 2004)

Twinning and the Incidence of Breast and Gynecological Cancers (United States) - Rachel E. Neale; David M. Purdie; Michael F. G. Murphy; Geraldine P. Mineau; Timothy Bishop; David C. Whiteman (Cancer Causes & Control, 2004)

The comparative biology of two sympatric paper wasps in Michigan, the native Polistes fuscatus and the invasive Polistes dominulus (Hymenoptera, Vespidae) - G. J. Gamboa; M. A. Noble; M. C. Thom; J. L. Togal; R. Srinivasan; B. D. Murphy (Insectes Sociaux, 2004)

Acetate non-utilizing mutants of Arabidopsis: evidence that organic acids influence carbohydrate perception in germinating seedlings - M. A. Hooks; J. E. Turner; E. C. Murphy; I. A. Graham (Molecular Genetics and Genomics, 2004)

Oceanographic variability and changes in Antarctic krill ( Euphausia superba ) abundance at South Georgia - P. N. Trathan; A. S. Brierley; M. A. Brandon; D. G. Bone; C. Goss; S. A. Grant; E. J. Murphy; J. L. Watkins (Fisheries Oceanography, 2003)
Oceanographic data collected to the north of South Georgia were examined for three consecutive summers (1996/97, 1997/98, 1998/99). The results show the existence of a shelf break front during each period. The most reliable means of defining the front was the potential density anomaly at the near‐surface potential temperature minimum. In each year, off‐shelf waters were separated from on‐shelf waters by water with a potential density anomaly between 27.22 and 27.29 kg m −3 . During 1997/98, the near‐surface potential temperature minimum was much colder and much shallower than in other years and was consistent with waters originating from much further south than South Georgia; these differences were further evident at a single deep off‐shelf station. The oceanographic changes during 1997/98 were consistent with a mesoscale or large‐scale movement of the southern Antarctic Circumpolar Current front. Acoustically determined densities of Antarctic krill, Euphausia superba , at South Georgia showed consistent patterns between years. Densities were substantially higher over the shelf compared with off‐shelf, with the highest densities at the shelf edge; densities were also higher to the east of the island. During 1997/98, acoustic densities of krill were substantially higher than in other years. The coincidence of the elevated acoustic density and the cooler oceanographic conditions was explored. When data from all years were combined and analysed by Generalized Additive Model, an inverse relationship between acoustic density and temperature was apparent. Historical data were also examined and it was noted that the only other occurrence of such a high estimate of krill density at South Georgia, was when oceanographic conditions were also colder.

The influence of diet on faecal DNA amplification and sex identification in brown bears ( Ursus arctos ) - Melanie A. Murphy; Lisette P. Waits; Katherine C. Kendall (Molecular Ecology, 2003)
To evaluate the influence of diet on faecal DNA amplification, 11 captive brown bears ( Ursus arctos ) were placed on six restricted diets: grass ( Trifolium spp., Haplopappus hirtus and Poa pratensis ), alfalfa ( Lupinus spp.), carrots ( Daucus spp.), white‐tailed deer ( Odocoileus virginianus ), blueberries ( Vaccinium spp.) and salmon ( Salmo spp.). DNA was extracted from 50 faecal samples of each restricted diet, and amplification of brown bear DNA was attempted for a mitochondrial DNA (mtDNA) locus and nuclear DNA (nDNA) locus. For mtDNA, no significant differences were observed in amplification success rates across diets. For nDNA, amplification success rates for salmon diet extracts were significantly lower than all other diet extracts ( P

Radiation hybrid mapping of the canine type I and type IV collagen gene subfamilies - Jennifer K. Lowe; Richard Guyon; Melissa L. Cox; Dianne C. Mitchell; Amy L. Lonkar; Frode Lingaas; Catherine Andr; Francis Galibert; Elaine A. Ostrander; Keith E. Murphy (Functional & Integrative Genomics, 2003)

Metal chelate affinity precipitation of RNA and purification of plasmid DNA - Sindhu Balan; Jason Murphy; Igor Galaev; Ashok Kumar; George E. Fox; Bo Mattiasson; Richard C. Willson (Biotechnology Letters, 2003)

Pythium spp. from cavity spot and other root diseases of Australian carrots - E. M. Davison; G. C. MacNish; P. A. Murphy; A. G. McKay (Australasian Plant Pathology, 2003)

The complete nucleotide sequence of Pepper mottle virus -Florida RNA - C. E. Warren; J. F. Murphy (Archives of Virology, 2003)

An evaluation of long-term preservation methods for brown bear (Ursus arctos) faecal DNA samples - Melanie A. Murphy; Lisette P. Waits; Katherine C. Kendall; Samuel K. Wasser; Jerry A. Higbee; Robert Bogden (Conservation Genetics, 2002)

Examination of Ethanol Responsive Liver and Brain Specific Gene Expression, in the Mouse Strains with Variable Ethanol Preferences, Using cDNA Expression Arrays - Brenda C. Murphy; Tillie Chiu; Michelle Harrison; Raihan K. Uddin; Shiva M. Singh (Biochemical Genetics, 2002)

AC Sunbury: A new light yellow-fleshed medium early table potato cultivar with resistance to golden cyst nematode - Agnes Murphy; Richard Tarn; Henry De Jong; Walter Arsenault; George C. C. Tai (American Journal of Potato Research, 2002)

Characterisation of the molecular responses to xenoestrogens using gene expression profiling - Tracy C. Murphy; George Orphanides (Phytochemistry Reviews, 2002)

Development of Multiplexed Fluorescence Microbead Covalent Assays (FMCAs) for Pesticide Biomonitoring - R. E. Biagini; D. M. Murphy; D. L. Sammons; J. P. Smith; C. A. F. Striley; B. A. MacKenzie (Bulletin of Environmental Contamination and Toxicology, 2002)

Assessment of Risks of Brodifacoum to Non-target Birds and Mammals in New Zealand - Charles T. Eason; Elaine C. Murphy; Geoffrey R.G. Wright; Eric B. Spurr (Ecotoxicology, 2002)

Influence of glucose ingestion by humans during recovery from exercise on substrate utilisation during subsequent exercise in a warm environment - Bilzon J.; Murphy J.; Allsopp A.; Wootton S.; Williams C. (European Journal of Applied Physiology, 2002)

Influence of Leaching Protocol Regimes on Losses of Wood Preservative Biocides - J. A. Hingston; A. Bacon; J. Moore; C. D. Collins; R. J. Murphy; J. N. Lester (Bulletin of Environmental Contamination and Toxicology, 2002)

Influence of Leaching Protocol Regimes on Losses of Wood Preservative Biocides - J. A. Hingston; A. Bacon; J. Moore; C. D. Collins; R. J. Murphy; J. N. Lester (Bulletin of Environmental Contamination and Toxicology, 2002)

Release of phosphorus from sediments in Lake Biwa - T. Murphy; A. Lawson; M. Kumagai; C. Nalewajko (Limnology, 2001)

Effects of temperature, and availability of nitrogen and phosphorus on the abundance of Anabaena and Microcystis in Lake Biwa, Japan: an experimental approach - C. Nalewajko; T. P. Murphy (Limnology, 2001)

Sexual size dimorphism in fallow deer (Dama dama): do larger, heavier males gain greater mating success? - Alan G. McElligott; Martin P. Gammell; Hilda C. Harty; Dean R. Paini; Desmond T. Murphy; James T. Walsh; Thomas J. Hayden (Behavioral Ecology and Sociobiology, 2001)

Post-orogenic exhumation of an auriferous terrane: the paleoplacer potential of the Early Carboniferous St. Marys Basin, Canadian Appalachians - L. C. Jennex; J. B. Murphy; A. J. Anderson (Mineralium Deposita, 2000)

Caleosins: Ca2+-binding proteins associated with lipid bodies - Henrik Næsted; Gitte I. Frandsen; Guang-Yuh Jauh; Immaculada Hernandez-Pinzon; Henrik B. Nielsen; Denis J. Murphy; John C. Rogers; John Mundy (Plant Molecular Biology, 2000)

Spatial summation in lateral geniculate nucleus and visual cortex - Helen E. Jones; Ian M. Andolina; Nicola M. Oakely; Penelope C. Murphy; Adam M. Sillito (Experimental Brain Research, 2000)

Monitoring of Particle Mass and Number in Urban Air - N Pomeroy; D Webber; C Murphy (Environmental Monitoring and Assessment, 2000)

Diphenylene iodonium sensitivity of a solubilized membrane enzyme from rose cells - T. M. Murphy; H. Vu; T. Nguyen; C. H. Woo (Protoplasma, 2000)

Microsatellite markers for investigating population structure in Octopus vulgaris (Mollusca: Cephalopoda) - E. C. Greatorex; C. S. Jones; J. Murphy; L. N. Key; A. M. Emery; P. R. Boyle (Molecular Ecology, 2000)

Soluble organic nitrogen in agricultural soils - D. V. Murphy; A. J. Macdonald; E. A. Stockdale; K. W. T. Goulding; S. Fortune; J. L. Gaunt; P. R. Poulton; J. A. Wakefield; C. P. Webster; W. S. Wilmer (Biology and Fertility of Soils, 2000)

Distribution of nitrogen pools in the soil profile of undisturbed and reseeded grasslands - A. Bhogal; D. V. Murphy; S. Fortune; M. A. Shepherd; D. J. Hatch; S. C. Jarvis; J. L. Gaunt; K. W. T. Goulding (Biology and Fertility of Soils, 2000)

Nanoscale topography of the basement membrane underlying the corneal epithelium of the rhesus macaque - G. A. Abrams; S. L. Goodman; P. F. Nealey; M. Franco; C. J. Murphy (Cell and Tissue Research, 2000)

Probiotics: from myth to reality. Demonstration of functionality in animal models of disease and in human clinical trials - Colum Dunne; Lisa Murphy; Sarah Flynn; Liam O'Mahony; Sile O'Halloran; Maria Feeney; Darrin Morrissey; Gerardine Thornton; Gerald Fitzgerald; Charles Daly; Barry Kiely; Eamonn M. M. Quigley; et al. (Antonie van Leeuwenhoek, 1999)

Human–environment interactions in South Florida's Everglades region: Systems of ecological degradation and restoration - William D. Solecki; John Long; Christine C. Harwell; Victoria Myers; Ezra Zubrow; Tom Ankersen; Christopher Deren; Camille Feanny; Richard Hamann; Lewis Hornung; Celeste Murphy; George Snyder (Urban Ecosystems, 1999)

The use of image analysis to study developmental variation in micropropagated potato (Solanum tuberosum L.) plants - A. C. Cassells; B. Kowalski; D. M. Fitzgerald; G. A. Murphy (Potato Research, 1999)

Chemical Ozone Loss in the Arctic Winter 1994/95 as Determined by the Match Technique - M. Rex; P. Von Der Gathen; G.O. Braathen; N.R.P. Harris; E. Reimer; A. Beck; R. Alfier; R. Krüger-carstensen; M. Chipperfield; H. De Backer; D. Balis; F. O'Connor; et al. (Journal of Atmospheric Chemistry, 1999)

Plant root-bacterial interactions in biological control of soilborne diseases and potential extension to systemic and foliar diseases - J.W. Kloepper; R. Rodríguez-Kábana; G.W. Zehnder; J.F. Murphy; E. Sikora; C. Fernández (Australasian Plant Pathology, 1999)

Microscopic observations of bacterial sorption in soil cores - A. C. Fisk; S. L. Murphy; R. L. Tate III (Biology and Fertility of Soils, 1998)

Short-term effects of nitrogen on methane oxidation in soils - P. Tlustos; T. W. Willison; J. C. Baker; D. V. Murphy; D. Pavlikova; K. W. T. Goulding; D. S. Powlson (Biology and Fertility of Soils, 1998)

Genotype/phenotype correlation in affected individuals of a family with a deletion of the entire coding sequence of the connexin 32 gene - P. J. Ainsworth; C. F. Bolton; B. C. Murphy; J. A. Stuart; A. F. Hahn (Human Genetics, 1998)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

A mini drivepoint sampler for measuring pore water solute concentrations in the hyporheic zone of sand‐bottom streams - John H. Duff; Fred Murphy; Chrsistopher C. Fuller; Frank J. Triska; Judson W. Harvey; Alan P. Jackman (Limnology and Oceanography, 1998)
A new method for collecting pore‐water samples in gravel streambeds is presented. We developed a mini drivepoint solution sampling (MINIPOINT) technique to collect pore‐water samples at 2.5‐cm vertical resolution. The sampler consisted of six small‐diameter stainless steel drivepoints arranged in a 10‐cm‐diameter circular array. In a simple procedure, the sampler was installed in the streambed to preset drivepoint depths of 2.5, 5.0, 7.5, 10.0, 12.5, and 15.0 cm. Sampler performance was evaluated in the Shingobee River, Minnesota, and Pinal Creek, Arizona, by measuring the vertical gradient of chloride concentration in pore water beneath the streambed that was established by the uninterrupted injection to the stream for 3 d. Pore‐water samples were withdrawn from all drivepoints simultaneously. In the first evaluation, the vertical chloride gradient was unchanged at withdrawal rates between 0.3 and 4.0 ml min − but was disturbed at higher rates. In the second evaluation, up to 70 ml of pore water was withdrawn from each drivepoint at a withdrawal rate of 2.5 ml min −1 without disturbing the vertical chloride gradient. Background concentrations of other solutes were also determined with MINIPOINT sampling. Steep vertical gradients were present for biologically reactive solutes such as DO, NH 4 + , NO 3 − , and dissolved organic C in the top 20 cm of the streambed. These detailed solute profiles in the hyporheic zone could not have been determined without a method for close interval vertical sampling that does not disturb natural logic mixing between stream water and groundwater.

p21 cip1 rescues human mesenchymal stem cells from apoptosis induced by low-density culture - C. van den Bos; Shawn Silverstetter; Mary Murphy; Timothy Connolly (Cell and Tissue Research, 1998)

Interrelationships of fish and channel environmental conditions with aquatic macrophytes in an Argentine irrigation system - O. A. Fernández; K. J. Murphy; A. López cazorla; M. R. Sabbatini; M. A. Lazzari; J. C. J. Domaniewski; J. H. Irigoyen (Hydrobiologia, 1998)

Methane fluxes and nitrogen dynamics from a drained fenland peat - T. W. Willison; J. C. Baker; D. V. Murphy (Biology and Fertility of Soils, 1998)

A Study of Ozone Laminae Using Diabatic Trajectories, Contour Advection and Photochemical Trajectory Model Simulations. - S. J. Reid; M. Rex; P. Von Der Gathen; I. Fløisand; F. Stordal; G. D. Carver; A. Beck; E. Reimer; R. Krüger-Carstensen; L. L. De Haan; G. Braathen; V. Dorokhov; et al. (Journal of Atmospheric Chemistry, 1998)

Oleosins prevent oil-body coalescence during seed imbibition as suggested by a low-temperature scanning electron microscope study of desiccation-tolerant and -sensitive oilseeds - O. Leprince; A. C. van Aelst; H. W. Pritchard; D. J. Murphy (Planta, 1997)

Gender comparison of peak oxygen uptake: repetitive box lifting versus treadmill running - Bradley C. Nindl; Marilyn A. Sharp; Robert P. Mello; Valerie J. Rice; Michelle M. Murphy; John F. Patton (European Journal of Applied Physiology, 1997)

Behavioral, physiological and neuroendocrine responses in healthy volunteers to m -chlorophenylpiperazine ( m -CPP) with and without ondansetron pretreatment - A. Broocks; Nathaniel C. Briggs; Teresa A. Pigott; James L. Hill; Stephanie K. Canter; Teresa J. Tolliver; Deborah Baldemore; D. L. Murphy (Psychopharmacology, 1997)

Synchrony in egg-laying and reproductive success of neighboring common murres, Uria aalge - E. C. Murphy; J. H. Schauer (Behavioral Ecology and Sociobiology, 1996)

SUMMER MOISTURE AVAILABILITY OVER EUROPE IN THE HADLEY CENTRE GENERAL CIRCULATION MODEL BASED ON THE PALMER DROUGHT SEVERITY INDEX - P. D. JONES; M. HULME; K. R. BRIFFA; C. G. JONES; J. F. B. MITCHELL; J. M. MURPHY (International Journal of Climatology, 1996)

Ac novachip: a new potato cultivar with excellent chip quality after long storage and reconditioning - H. De Jong; G. C. C. Tai; A. M. Murphy; T. R. Tarn; J. H. E. Thorpe; W. J. Arsenault; R. H. Bagnall; H. W. Platt; D. A. Young (American Journal of Potato Research, 1995)

Ac belmont: a new early-maturing potato cultivar with short dormancy - T. R. Tarn; H. De Jong; A. M. Murphy; G. C. C. Tai; W. J. Arsenault; J. H. E. Thorpe; R. H. Bagnall; H. W. Platt; D. A. Young; H. T. Davies (American Journal of Potato Research, 1995)

Ac chaleur: a new early-maturing cultivar with excellent table quality - H. De Jong; T. R. Tarn; A. M. Murphy; G. C. C. Tai; R. H. Bagnall; W. J. Arsenault; J. H. E. Thorpe; H. W. Platt; D. A. Young; H. T. Davies (American Journal of Potato Research, 1995)

Ac brador: a new late-maturing cultivar with a high degree of field resistance to late blight - T. R. Tarn; G. C. C. Tai; A. M. Murphy; H. De Jong; H. W. Platt; R. H. Bagnall; W. J. Arsenault; J. H. E. Thorpe; D. A. Young; H. T. Davies (American Journal of Potato Research, 1995)

Analysis of sites of foot and mouth disease virus persistence in carrier cattle via the polymerase chain reaction - M. L. Prato Murphy; R. F. Meyer; C. Mebus; A. A. Schudel; M. Rodriguez (Archives of Virology, 1994)

Association Business - David Curwen; Ronald Knight; Therese M. Work; Hugh J. Murphy; Pete Weingartner; John Ojala; Gary Franc; Roger Brook; Tom German; Sam Thorton; John Bamberg; John C. Wallace; et al. (American Journal of Potato Research, 1993)

The Potato Association of America 75th Annual Meeting Spokane, Washington, U.S.A. - David Curwen; Pete Weingartner; Ronald Knight; Therese M. Work; Hugh J. Murphy; Steven B. Johnson; Richard Zink; Leigh Morrow; A. R. Mosley; Rod Davidson; Thoms Owings; Don Halseth; et al. (American Journal of Potato Research, 1991)

Evolutionary study on the coxsackievirus A 24 variant causing acute hemorrhagic conjunctivitis by oligonucleotide mapping analysis of RNA genome - K. Miyamura; N. Takeda; M. Tanimura; T. Ogino; S. Yamazaki; C. -W. Chen; K. -H. Lin; S. Y. Lin; A. Ghafoor; M. Yin-Murphy (Archives of Virology, 1990)

Electron microscopic and antigenic studies of uncharacterized viruses. II. Evidence suggesting the placement of viruses in the familyBunyaviridae - H. G. Zeller; N. Karabatsos; Ch. H. Calisher; J. -P. Digoutte; C. B. Cropp; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Electron microscopic and antigenic studies of uncharacterized viruses. III. Evidence suggesting the placement of viruses in the familyReoviridae - H. G. Zeller; N. Karabatsos; C. H. Calisher; J. -P. Digoutte; C. B. Cropp; F. A. Murphy; R. E. Shope (Archives of Virology, 1989)

Campbell 14: A verticillium resistant round white potato variety - A. F. Reeves; C. E. Cunningham; R. L. Nickeson; R. V. Akeley; H. J. Murphy; F. E. Manzer; R. H. True (American Journal of Potato Research, 1985)

Sunrise: An early maturing, golden nematode resistant, round, white potato variety - A. F. Reeves; R. V. Akeley; C. E. Cunningham; H. J. Murphy; R. H. True; F. E. Manzer (American Journal of Potato Research, 1985)

Yankee Supreme: A new bruise-resistant potato variety - A. F. Reeves; R. V. Akeley; C. E. Cunningham; R. L. Nickeson; H. J. Murphy; R. H. True; F. E. Manzer (American Journal of Potato Research, 1984)

Life members announced - Donald C. Nelson; Hugh J. Murphy (American Journal of Potato Research, 1982)

Delta Gold: A new potato variety with yellow flesh, high solids and high quality for baking and processing - A. F. Reeves; R. E. Webb; D. C. Merriam; H. J. Murphy; F. E. Manzer; R. H. True (American Journal of Potato Research, 1980)

Viruses isolated from reptiles: Identification of three new members of the familyRhabdoviridae - T. P. Monath; C. B. Cropp; Christina L. Frazier; F. A. Murphy; Sylvia G. Whitfield (Archives of Virology, 1979)

Host range mutants of an influenza A virus - C. Scholtissek; B. R. Murphy (Archives of Virology, 1978)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)

Errata - R. V. Akeley; H. J. Murphy; R. C. Cetas (American Journal of Potato Research, 1971)

Abnaki: A new high-yielding potato variety resistant to verticillium wilt and leaf roll - R. V. Akeley; H. J. Murphy; R. C. Cetas (American Journal of Potato Research, 1971)

Effect of tetrachloronitrobenzene (fusarex) on emergence and yield of potatoes. Part III. — Northeast - H. J. Murphy; M. J. Goven; J. C. Campbell; A. Hawkins; J. D. Harrington; S. L. Dallyn (American Journal of Potato Research, 1969)

s of papers presented at the Fifty-Second Annual Meeting of The Potato Association of America - J. A. Crozier; P. J. Ito; Puente De La Fermin; S. J. Peloquin; P. Severino; E. C. Doll; D. R. Christenson; A. R. Wolcott; Hawkins Arthur; F. D. Howard; Herman Timm; W. J. Flocker; et al. (American Journal of Potato Research, 1968)

Effect of tetrachloronitrobenzene (Fusarex) on emergence and yield of potatoes. Part II. — Northeast - H. J. Murphy; M. J. Goven; J. C. Campbell; C. F. Everett; J. D. Harrington; R. L. Sawyer (American Journal of Potato Research, 1968)

Effect of physiological maturity and storage temperature on emergence and yield of potatoes - H. J. Murphy; F. E. Manzer; M. J. Goven; D. C. Merriam (American Journal of Potato Research, 1967)

Effect of three viruses on yield, specific gravity, and chip color of potatoes in Maine - H. J. Murphy; M. J. Goven; D. C. Merriam (American Journal of Potato Research, 1966)

s of papers presented at the 50th Anniversary Meeting of The Potato Association of America and 13th National Potato Utilization Conference Perkins Inn, Riverhead, New York July 15, 16, 17, 18, 1963 - Glenn D. Boyd; Calderon Peter; Ora Smith; L. R. Mattick; John C. Campbell; R. C. Cetas; Carl O. Davis; Smith Ora; C. H. Dearborn; F. H. Drazga; R. K. Eskew; F. B. Talley; et al. (American Journal of Potato Research, 1963)

Minutes of Executive Committee Meeting, Annual Business Meeting, Committee reports and Financial Report - L. C. Young; Richard L. Sawyer; Hugh J. Murphy; J. W. Scannell; John C. Campbell; Walter C. Sparks; Ora Smith; William B. Raymer; R. H. Treadway; J. C. Campbell; Arthur Hawkins; R. G. Rowberry; et al. (American Journal of Potato Research, 1962)

s of papers presented at the Forty-Third annual meeting of The Potato Association of America - R. H. Bagnall; D. A. Young; Barrel R. Bienz; G. D. Brill; J. C. Campbell; G. R. Blake; Paul N. Carpenter; George O. Estes; Harold W. Gausman; Harold W. Gausman; Hawkins Arthur; Henning P. Hansen; et al. (American Journal of Potato Research, 1959)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)